Evolutionary Prevalence of the Electrostatic Switch Mechanism in P-type ATPases - Nikita S. Badve; Alyssa V. Buda; Jonas A. Káral; Zhitong Li; Taylah L. Percival; Sofia Y. Wardman; Sophia G. Tran; Simon Y. W. Ho; Ronald J. Clarke (The Journal of Membrane Biology, 2026)

Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

Thinking through compassionate conservation: A staged case study of black-footed ferret recovery - Liv Baker; William T. Borrie; Adam P.A. Cardilini; William S. Lynn; Shelley M. Alexander; Dror Ben-Ami; Gavin T. Bonsen; Simon Coghlan; Barbara J. King; Christine M. Reed; Francisco J. Santiago-Ávila; Kristen A. Walker; et al. (Biological Conservation, 2026)

Dietary lemon essential oil mitigates metalaxyl-induced oxidative stress, hematological disruptions, and immunotoxicity in Nile tilapia (Oreochromis niloticus) with associated changes in splenic MAPK-and caspase-related gene expression - Elsayed M. Younis; Afaf N. Abdel Rahman; Tarek Khamis; Abdelwahab A. Abdelwarith; Simon J. Davies; Faozi S. Shamlol; Nehal A. Younis; Rowida E. Ibrahim; Gehad E. Elshopakey (Research in Veterinary Science, 2026)

Abundant and diverse Pb nanospheres in polyphase Eoarchean zircon from the Odesa Quarry, Ukrainian Shield - Monika A. Kusiak; Simon A. Wilde; Richard Wirth; Leonid Shumlyanskyy; Bożena Gołębiowska; Martin J. Whitehouse (Chemical Geology, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Growth, Digestive Enzyme Activities, Antioxidant Properties, and Intestinal Histology of Nile Tilapia ( Oreochromis niloticus ) Fed Diets Supplemented With Garlic Nanoparticles - Sami Alaa Sami; Ashraf Y. El‐Dakar; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohammed F. El Basuini; Shymaa M. Shalaby; Mohamed M. Rashad; Simon J. Davies; Mohamed F. Abdel‐Aziz (New Zealand Journal of Marine and Freshwater Research, 2026)
This work may be the first of its kind to assess the effects of varying inclusion levels of garlic nanoparticles (NPsG) as feed additives on growth and physiological indices in Nile tilapia ( Oreochromis niloticus ). Garlic contains an organosulfur compound called allicin that can promote growth and strengthen the immune system by stimulating appetite and the intestinal flora, thus enhancing energy utilization. Nanotechnology provides new tools in aquaculture nutrition, including increasing the ability of fish to absorb nutrients rapidly and the effectiveness of feed additives by enhancing their bioavailability compared to their bulk form. Five concentrations of NPsG (0, 150, 300, 600, or 1200 mg/kg) were evaluated by their addition to a basal diet (30% crude protein). 225 juveniles with an initial weight of 3.92 g ± 0.42 (SE) were randomly divided into 15 cages of polyethylene. The cage had dimensions of length: width: height (100:40:60 cm) and was continuously aerated using a 2 HP air blower with air stones. After 42 days, feeding results revealed that NPsG supplementation had significant effects ( p < 0.05) on improving the performance, physiological indicators, and histomorphometry of the intestine in comparison with the control. Fish that were fed a dietary supplement of 600 mg/kg of NPsG exhibited the highest specific growth rate (2.80%/day), along with elevated levels of intestinal enzymes lipase, amylase, and proteases (212.40, 15.00, and 318.60 U/g of intestine, respectively) and the lowest malondialdehyde level (81 nmol/g of liver tissue). This group was followed by fish fed a diet of 300 mg/kg of NPsG, which did not significantly differ from those fed 600 mg/kg of NPsG in superoxide dismutase, total antioxidant capacity, and histomorphometry of intestine villi. Finally, the complete dose–response recommendation (benefit at 300–600 mg/kg and detriment at 1200).

Implementing area-based management of vulnerable marine ecosystems in areas beyond national jurisdiction: A South Pacific case study - Ashley A. Rowden; Fabrice Stephenson; Martin Cryer; Carolyn J. Lundquist; Owen F. Anderson; Matthew Bennion; Andrew Biggerstaff; Tiffany Bock; Tom Brough; Lee Georgeson; Alexandra Macdonald; Marco Milardi; et al. (Ocean & Coastal Management, 2026)

Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Anti-environmental political agendas, firearm deregulation and illegal hunting in Brazil - Hani R. El Bizri; Thais Queiroz Morcatty; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Kacie Henson; Camila Alvez Islas; Gabriel Favero Massocato; Arnaud L.J. Desbiez; João Vitor Campos-Silva; Daniel Zani La Laina; et al. (Biological Conservation, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Opportunities to improve detection of genetic predisposition for ovarian cancer applying the Tumor-First workflow - Vera M. Witjes; Joanne A. de Hullu; Angela van Remortele; Lilian Vreede; Michiel Simons; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg (Familial Cancer, 2026)
Genetic testing in ovarian carcinoma (OC) patients is very important for patients and their relatives. The Tumor-First workflow uses a tumor DNA test to stratify germline testing for hereditary cancer predisposition as well as treatment options with PARP inhibitors. This workflow is adopted and successfully implemented nationwide. Here, we evaluated recent tumor DNA testing rates in the Netherlands to identify untested OC patient groups and optimize tumor DNA testing rates. OC patients diagnosed in 2023 or 2024 were selected from the Netherlands Cancer Registry. We analyzed patient characteristics associated with the likelihood of tumor DNA testing using multivariable logistic regression. Tumor-First testing was performed for 1765 out of the 2221 (79%) OC patients. Patients diagnosed with advanced stage OC were more likely to receive tumor DNA testing (OR = 2.5, p < 0.001) than those with low-stage disease. Compared with patients who underwent surgery as primary treatment, those who received chemotherapy or no primary treatment were less likely to be tested (OR = 0.21 and OR = 0.07, respectively, p < 0.001). Patients who died within 100 days were less likely to receive testing (OR = 0.57, p = 0.003). Patients without resection after diagnosis on biopsy/cytology had the lowest Tumor-First testing rates (58% vs. 87–95%, χ2 p < 0.001). Tumor-First testing rates are high. However, OC patients that do not undergo a resection are less likely to undergo testing. With these data strategies to identify hereditary cancer predisposition in patients and their relatives can be further improved.

Thermal stress restructures volatile gas emissions from the model cnidarian Aiptasia - Maggie Wuerz; Caitlin A. Lawson; Clinton A. Oakley; Malcolm Possell; Arthur R. Grossman; Virginia M. Weis; David J. Suggett; Simon K. Davy (Coral Reefs, 2026)
Coral bleaching events, in which symbionts are lost from host tissues, have become more frequent and severe because of climate change—specifically, elevated temperatures. How such events impact biogenic volatile organic compound (BVOC) emissions, compounds that can function as metabolic signalling elements, remains underexplored. Here we used gas chromatography coupled with mass spectrometry (GC–MS) to characterise the suite of BVOCs (collectively the ‘volatilome’) from the model sea anemone Exaiptasia diaphana (‘Aiptasia’) under three temperatures (control: 25 °C; sub-bleaching: 30 °C; and bleaching: 33.5 °C), both without symbionts (aposymbiotic) and when populated by its native dinoflagellate symbiont, Breviolum minutum . The volatilome of symbiotic anemones during bleaching at an elevated temperature was distinct from that at lower temperatures, with high dimethyl sulphide (DMS), eucalyptol, and 1-iodododecane levels at the higher temperature. In comparison, the volatilome of aposymbiotic anemones at sub-bleaching temperature produced the most differentially abundant BVOCs, including 2-phenyl-3-methyl-pyrrolo(2,3-b)pyrazine, acetone, and naphthalene. Symbiotic anemones had 12-fold more ‘core volatiles’ (BVOCs in all biological replicates across all temperature treatments) than aposymbiotic anemones (48 vs . 4 BVOCs); during thermal stress, the symbiotic anemone volatilomes retained their compound richness, whereas the richness of aposymbiotic anemone volatilomes decreased. These observations suggest that symbiotic dinoflagellates enhance BVOC diversity and abundance and may confer a degree of metabolic stability to the intact symbiosis (i.e. ‘holobiont'). Such changes in metabolic outputs can inform our understanding of how coral holobionts respond to increasing seawater temperatures, enable targeted studies of BVOC function, and facilitate the development of biomarkers indicative of coral reef health.

Freshwater biodiversity in a rapidly changing Arctic: An expert horizon scan of key research questions - Joseph M. Culp; Michael Power; Kirsten S. Christoffersen; Willem Goedkoop; Kimmo K. Kahilainen; Milla Rautio; Fernando Chaguaceda; Marie-Pier Hébert; Sanne M. Moedt; Dermot Antoniades; Simon Belle; Daniel Bolnick; et al. (Ambio, 2026)
Arctic freshwater biodiversity is rapidly changing due to climate warming, resource extraction, infrastructure development, and landscape transformation. To improve understanding, predict future responses, and inform policy formulation, research needs must be clearly identified. Using a horizon scan survey, Arctic freshwater experts from government, international agencies, and Indigenous Peoples identified 77 biodiversity research questions with 17 highlighted as most important for near term assessment. These questions span nine thematic categories: biodiversity and taxonomic challenges, hydrological change, productivity and food webs, ecosystem connectivity, methods, monitoring and assessment, permafrost change, winter ecology, anthropogenic development, and Indigenous Knowledge. Climate change emerged as the major driver among all categories and research questions. A key priority identified was the urgent need for long-term, harmonized monitoring programs among Arctic countries. Multiple knowledge gaps detected suggest that circumpolar research collaborations are required to tackle these issues.

Prioritizing Shark, Ray, and Chimaera Conservation in Rapidly Changing Polar Waters - Vanessa B. Bettcher; Amanda Batlle‐Morera; Peter M. Kyne; Ryan Charles; Emiliano García‐Rodríguez; Christoph A. Rohner; Asia O. Armstrong; Margaret O’Leary Amsler; Natalia V. Chernova; Brynn M. Devine; Andrey V. Dolgov; Meghan M. Donovan; et al. (Global Change Biology, 2026)
Climate‐driven alterations in sea‐ice dynamics and shifting fishing activity are reshaping ecosystems across the Arctic and Antarctic, yet conservation‐relevant information for chondrichthyans (sharks, rays, and chimaeras) remains limited. We present the first assessment of Important Shark and Ray Areas (ISRAs) across Polar Waters, integrating species distributions, extinction risk, critical habitat evidence, spatial protection coverage, apparent fishing effort (2013–2018 vs. 2019–2024), and sea‐ice concentration trends. Of 86 chondrichthyan species reported from Polar Waters, only 15 (17.4%) had sufficient evidence to meet the ISRA Criteria, and 28 (32.6%) are threatened with extinction. We identified 35 ISRAs (27 Arctic; 8 Antarctic) covering 0.75% of the Polar Waters region. ISRAs were delineated predominantly based on data from scientific fishing surveys and harvest fisheries. Most Antarctic ISRAs were delineated under Criterion B—Range Restricted, reflecting endemism and scarce life‐history evidence. Major knowledge gaps persist, particularly for highly adapted Polar Species (10 species) and deepwater taxa (72.1% of regional chondrichthyan fauna). Between 2013 and 2024, the spatial footprint of fishing expanded in both poles for trawlers and longliners, despite stable or declining fishing hours in some fleets. Concurrent areas of increasing fishing effort and decreasing sea‐ice concentration remained minimal. However, apparent fishing effort overlapped with most ISRAs, indicating ongoing fishing pressure in critical habitats. Marine Protected Area (MPA) coverage remains uneven: 8.2% of Arctic ISRA spatial extent overlaps MPAs (0.8% no‐take), compared with 43.8% in the Antarctic (14.8% no‐take), with insufficient effective coverage in areas beyond national jurisdiction. These results reveal substantial mismatches between chondrichthyan critical habitats, fishing exposure, and existing protection measures. Integrating ISRAs into existing management frameworks, such as Target 3 of the Global Biodiversity Framework, High Seas Treaty mechanisms, and fisheries governance bodies, will be essential to safeguard vulnerable polar chondrichthyans as sea‐ice concentration declines and exposure risk increases.

Soil cultivation for potatoes. A global survey of cultivation practices - Mark A. Stalham; Shaunagh Slack; Ryan Barrett; Ranjan Bhattacharyya; Karina M.V. Cavalieri-Polizeli; Rosario Fuentes del Río; Iain Kirkwood; John E. McPhee; Simon McWilliam; Mark J. Pavek; Mehdi Rahmati; Lautaro Rios; et al. (Soil and Tillage Research, 2026)

“Going Flat” After Mastectomy: A Social Media Analysis of Patient Perspectives and Educational Needs - Gabrielle Knauer; Tamara Lalovic; Catherine Simon; Richard J. Bleicher; Adam Walchak; Sameer A. Patel; Austin D. Williams (Journal of Cancer Education, 2026)
Aesthetic flat closure (AFC) is a surgical option following mastectomy that aims to create a smooth chest wall. Although formally recognized by the National Cancer Institute in 2020, patients continue to report challenges in accessing AFC. Social media platforms may serve as an important source of support and education for patients considering this option. We characterized patient perspectives and experiences related to AFC through analysis of discussions on Reddit and TikTok. Using the search term “flat,” posts from the r/breastcancer forum were reviewed within Reddit’s 1,000 post-and-comment visibility limit. AI-assisted thematic analysis was used to identify recurring discussion themes. TikTok was searched using the terms “going flat,” “going flat mastectomy,” and “aesthetic flat closure.” A total of 370 Reddit posts and 74 TikTok posts met inclusion criteria for relevance to AFC. Posts were most often neutral in tone; however negative sentiment was nearly three times more common on Reddit than TikTok (28.9% vs. 11%). On Reddit, the most common area of discussion was comparison of AFC with other post-mastectomy reconstructive options. “Flat denial,” defined as neglecting to perform a true AFC either intentionally or inadvertently, appeared more frequently on Reddit (8.4% vs. 4.0%). AI analysis identified recurring themes including flat denial, inadequate counseling, and misinformation regarding AFC. While discussions surrounding AFC were often neutral or positive, concerns regarding inadequate information, patient counseling, and flat denial persist. These findings highlight the need for greater surgeon familiarity with AFC and more comprehensive patient education on post-mastectomy options.

Diet of juvenile skipjack herring Alosa chrysochloris : Ontogenetic shifts, predator–prey size ratios and mouth gape allometry - Joshua P. Egan; Peter J. Hundt; Neil P. Rude; Jason A. DeBoer; Benjamin J. Lubinski; Kristopher A. Maxson; Levi E. Solomon; Andrya L. Whitten Harris; Andrew M. Simons (Journal of Fish Biology, 2026)
The skipjack herring Alosa chrysochloris inhabits Gulf of Mexico drainages, primarily the Mississippi River Basin, and estuarine environments in the Gulf of Mexico. The trophic ecology of the skipjack herring is poorly understood, therefore we quantified the length, mouth gape and gut contents of juvenile skipjack herring from the Mississippi River (fish n = 6), Illinois River (fish n = 181) and Ohio River (fish n = 255) and tested for changes in diets and predator–prey size ratios during ontogeny. We identified statistically significant changes in prey type consumption during ontogeny. Aquatic insects dominated the diets of skipjack herring 40 mm SL were primarily composed of fishes. The most prevalent fish species consumed by skipjack herring were invasive bigheaded carps Hypophthalmichthys spp. and preliminary evidence indicated that inter‐annual variation in the consumption of bigheaded carps was driven by variation in juvenile bigheaded carp abundance. Additional research is needed to determine if the enhancement of native skipjack herring populations could be used as a tool to limit bigheaded carp population sizes. Skipjack herring SL and mouth gape were both significantly positively correlated with maximum, median and minimum sizes of prey consumed. There were allometric changes in the mouth gape of juvenile skipjack herring, with the ratio of mouth gape to SL increasing until ~80 mm SL, then gradually declining. Maximum mouth gape to SL ratios corresponded to substantial increases in the consumption of fishes, indicating that mouth gape allometry may facilitate the ontogenetic transition to piscivory in the skipjack herring. This study improves our understanding of skipjack herring ecology and provides data that can be incorporated into future ecological and evolutionary research, such as the development of food web models.

Stomatal Decoupling From Photosynthesis Under High Temperatures Is Consistent With Stomatal Optimisation - Simon R. G. Jones; Georg Wohlfahrt; Andrew D. Friend; Peter J. Franks; Alexander W. Cheesman; Lucas A. Cernusak; Haoyu Diao; Xiaolong Feng; Josef Urban; Tyeen Taylor; Martijn Slot; Lina M. Mercado; et al. (Global Change Biology, 2026)
Stomatal pores on plant leaves regulate the gain of carbon through photosynthesis and the loss of water through transpiration. Through their responses to environmental conditions, stomata can constrain plant productivity and transpiration fluxes, exerting a strong control on climate feedbacks over land. Although mechanistic modelling of stomata remains a challenge, semi‐empirical and optimisation models have been successfully applied to improve the simulation of land‐atmosphere fluxes of water and carbon. Optimisation approaches assume that some aspect of plant function, such as photosynthesis or growth rate, is optimised with respect to an environmental constraint, such as available soil water. Both optimisation models and semi‐empirical models predict that stomatal conductance will increase in concert with rising photosynthetic rates as temperatures approach a thermal optimum, beyond which declines in both photosynthesis and stomatal conductance are expected. However, a growing number of experiments have found that while photosynthesis declines beyond its thermal optimum, stomatal conductance often continues to increase at high temperatures. Early modelling work suggests that this phenomenon can be captured and explained by an optimal thermoregulation strategy via increased evaporative cooling at the leaf surface. However, many stomatal conductance models that are embedded within climate and Earth System Models do not correctly account for this feedback and so cannot capture observed decoupling. Here, we demonstrate that if leaf temperature is calculated iteratively outside the optimisation scheme, as is commonly done in Earth System Models, stomatal decoupling will not be captured. However, by calculating leaf temperature in parallel with optimal stomatal conductance, we find that we are able to capture observed decoupling and improve predicted leaf temperature and gas exchange. Correctly implementing the leaf energy balance equation within stomatal optimisation models will be essential for capturing high temperature responses of forests across the globe.

Contrasting cryptofaunal responses to seabird nutrient inputs illuminate coral reef productivity pathways - Laura‐Li Jeannot; Ruth E. Dunn; M. Joyce P. Velos; Gareth J. Williams; Cassandra E. Benkwitt; Nicholas A. J. Graham; Simon J. Brandl (Ecology, 2026)
Nutrients moving across ecosystems can propagate through food webs via distinct trophic pathways. Their integration into food webs is often mediated by small, abundant taxa that channel subsidies from primary producers to higher trophic levels. On coral reefs, cryptobenthic fishes and invertebrates can fill these roles, yet their responses to allochthonous nutrients are poorly understood. We compared cryptofaunal communities and associated trophic dynamics across nutrient‐rich islands with intact seabird populations and nutrient‐poor rat‐infested islands in the Chagos Archipelago, Indian Ocean. Specifically, we evaluated how the presence of seabird colonies influenced cryptofaunal nutrient assimilation, biomass, structure, and isotopic niche dynamics, and how these shifts propagated to mesopredators and higher order piscivorous and invertivorous fishes. Most cryptobenthic fishes and some invertebrates showed nutrient enrichment near seabird colonies. Although the isotopic niches of cryptobenthic fishes and invertebrates overlapped, niche widths diverged in nutrient‐rich environments, with invertebrates exhibiting broader niches and cryptobenthic fishes remaining comparatively constrained, reflecting differential access to shared resources. Mixing models also reflected a shift toward cryptobenthic fishes in the diet of a mixed carnivore near seabird colonies. Community patterns revealed strong asymmetries: Nutrient‐rich reefs supported twice the amount of cryptobenthic fish biomass and a 10‐fold increase in larger piscivorous fish productivity, while reefs near rat‐infested islands were characterized by relatively greater cryptic invertebrate biomass and higher invertivore productivity. Taken together, these results suggest that cryptobenthic fishes' capacity to capitalize on seabird nutrients may allow them to exert competitive dominance and top‐down control over invertebrates in nutrient‐rich environments, thereby amplifying piscivorous pathways, while nutrient‐poor environments appear to favor invertebrates and their consumers. Rather than reflecting uniform biomass loss under rat invasion, these patterns indicate a shift in trophic routing from fish‐mediated to invertebrate‐mediated energy channels. Our findings demonstrate that cross‐ecosystem nutrient vectors do not simply enhance reef productivity but reorganize trophic structure. Therefore, invasive species that sever these linkages can drive the emergence of alternative food‐web configurations with distinct energetic pathways.

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Thermal infrared and ultraviolet remote sensing of sulfur dioxide gas emitted during the 2018 lower East Rift Zone eruption of Kīlauea, Hawaiʻi - Andrea Gabrieli; Christoph Kern; Allan Lerner; Vincent J. Realmuto; Simon Carn; Patricia A. Nadeau; Robert Wright; John N. Porter (Bulletin of Volcanology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Omega-3 and omega-6 polyunsaturated fatty acids in neurodevelopment and prematurity: Correcting imbalances and closing the Preterm PUFA Gap - Simon C. Dyall; J. Thomas Brenna; Susan E. Carlson; Michael A. Crawford; Camilia R. Martin; Norman Salem (Progress in Lipid Research, 2026)

Mycobacterium avium complex in captive swamp wallabies (Wallabia bicolor): a case series highlighting liver, lymphoid and bone predilection - Andreu Masdefiol Garriga; Stephanie M. Mota; Barbara Ferreira; Simon J. Girling; Liam A. Wilson (Journal of Comparative Pathology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Correction: Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Repeatable methods to establish and maintain cultures of Antarctic bdelloid rotifers - Melanie D. Borup; Catherine K. King; Simon J. Wotherspoon; Kerrie M. Swadling; John A. E. Gibson (Hydrobiologia, 2026)

Structural characterisation of a fucose-rich acidic extracellular polysaccharide produced by Lindavia intermedia in New Zealand lakes - Cara A. Luiten; Ian M. Sims; Tracey J. Bell; Peter T. Northcote; A. Jonathan Singh; Andrew R. Lewis; Guilherme L. Sassaki; Phil M. Novis; Marc Schallenberg; Simon F.R. Hinkley (Algal Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Thermomechanics coupling to Monte Carlo particle transport on unstructured mesh geometries using Cardinal - Mahmoud Eltawila; Pierre-Clément A. Simon; Guillaume L. Giudicelli; Helen Brooks; Nicholas Wozniak; April J. Novak (Annals of Nuclear Energy, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Heterogeneity in seed traits: an overlooked breeding opportunity - Luqman B. Safdar; Ian D. Fisk; Rahul A. Bhosale; Simon Griffiths; Malcolm J. Hawkesford; Scott A. Boden; M. John Foulkes (Trends in Plant Science, 2026)

Fennel essential oil as a natural feed additive to mitigate heat stress in broilers: Effects on growth, physiological and immunological responses, and intestinal morphology - Samar A. Tolba; Shimaa A. Amer; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Gehad E. Elshopakey; Noura A. Abd-Allah; Rehab Reda; Rehab I. Hamed; Gehan K. Saleh; Gehan N. Alagmy; Simon J. Davies; et al. (Journal of Thermal Biology, 2026)

Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Origins and environmental impacts of distal rhyolitic tephra layers on Chatham Island, New Zealand - Anna L. Miller; Simon J. Barker; Katherine A. Holt; Stephen B. Piva; Colin J. N. Wilson (Journal of Quaternary Science, 2026)
Chatham Island, ~700 km east of mainland New Zealand, preserves several macroscopic tephra beds, sourced from the central Taupō Volcanic Zone (TVZ) some 850 km away. These layers, often enclosed within peat, provide insights into the eruptive characteristics, timing and paleoenvironmental impacts of large explosive rhyolitic eruptions in a distal setting. We report the nature, origins and impacts of these tephras by documenting bulk and centimetric‐scale stratigraphic changes in glass shard geochemistry and millimetric‐scale changes in pollen assemblages in the enclosing peats. Three layers are investigated: the ~25.5 ka Kawakawa–Ōruanui Tephra (KOT), the ~345 ka Rangitawa Tephra and one newly discovered tephra. The KOT shows no stratigraphic variability in glass composition throughout ~15 cm thickness. The Rangitawa Tephra contains three glass populations that were deposited sequentially throughout the eruption and further link this tephra to the Whakamaru supereruption. The new tephra has two glass populations and is matched to the ~322 ka Matahina caldera‐forming eruption. High‐resolution sampling of peat bracketing the KOT and Rangitawa Tephra reveals marked changes in local vegetation following the deposition of both tephras. The nature of the changes varies between events and can be explained by differing paleoenvironmental settings, climate and/or tephra thickness.

Thermal Stress‐Induced Alterations to Oxylipin Signal Receptors in the Cnidarian–Dinoflagellate Symbiosis - Andrea G. Gamba; Clinton A. Oakley; Immy A. Ashley; Arthur R. Grossman; Virginia M. Weis; David J. Suggett; Simon K. Davy (Environmental Microbiology, 2026)
The continuous exchange of molecular signals between partners in the cnidarian–dinoflagellate symbiosis is fundamental for maintaining a healthy relationship. This homeostasis is affected by rising seawater temperatures resulting from climate change (i.e., coral bleaching), though little is known about how these molecular signals are altered. Here, we investigated the localisation and abundance of four receptors in the sea anemone Exaiptasia diaphana (‘Aiptasia’) exposed to thermal stress. Using immunohistochemistry, we examined Transient Receptor Potential channel A1 (TRPA1), Prostaglandin E2 receptors 2 (EP2) and 4 (EP4) and Glutamate receptor ionotropic kainate 2 (GRIK2). TRPA1, EP2 and EP4 are involved in oxylipin‐mediated signalling via hydroxyoctadecadienoic acid (HODE) and prostaglandin E2 (PGE2), while GRIK2, part of the ionotropic glutamate receptor (iGluR) family, has been linked to chemosensory perception in invertebrates. All four receptors were detected in both gastrodermis and epidermis across treatments. While EP4 abundance was unaffected, EP2 increased significantly at 31°C and 34°C in both tissue layers. TRPA1 abundance increased at 34°C in both layers, and GRIK2 increased at 31°C in the gastrodermis and at 34°C in both layers. These results suggest that lipid signalling pathways are thermally modulated, potentially contributing to symbiosis dysfunction and bleaching.

Corrigendum to “Eoarchean low δ18O zircon indicates emergent land at 3.73 Ga” [Precambrian Res. 408 (2024) 107416] - Piotr Król; Monika A. Kusiak; Martin J. Whitehouse; Daniel J. Dunkley; Simon A. Wilde (Precambrian Research, 2026)

Improved management of base metal mine tailings impoundment and receiving environment sulfur risks: Nature-based solutions - Lauren E. Twible; James L.S. Arrey; Yunyun Yan; Tara E. Colenbrander Nelson; Kelly J. Whaley-Martin; Chad Jarolimek; Josh J. King; Simon Apte; Lesley A. Warren (Journal of Environmental Management, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Low foliar nitrogen and elevated defensive metabolites in the invasive weed Calluna vulgaris (heather) may impair biocontrol agent performance - D. Paul Barrett; Maria A. Minor; Paul Peterson; Simon V. Fowler; Arvind K. Subbaraj; David J. Lun; Andrea Clavijo McCormick (Biological Invasions, 2026)
Introducing insect biocontrol agents to manage invasive plants is an effective and sustainable management option. However, biocontrol agents sometimes fail to establish or are ineffective in the new range. Heather beetle Lochmaea suturalis, (Thomson, 1866) (Coleoptera: Chrysomelidae) sourced from the United Kingdom (UK), was introduced into New Zealand’s North Island Central Plateau (CP) to control invasive Calluna vulgaris (L.) Hull (heather). The beetle was difficult to establish and the few populations that did, achieved poor population growth rates and expansion in contrast to the rapid rates associated with its conspecifics in the UK. We hypothesize that low soil nutrients such as nitrogen and phosphorous (N and P) on the CP may be linked to changes in C. vulgaris’ primary nutritional and secondary defensive metabolites, leading to poor beetle performance. Testing this hypothesis involved application of N and P to soil in C. vulgaris field plots, measurement of foliar N and Carbon (C), plus using non-targeted metabolomics, exploring differences in the primary and secondary metabolites between treatments. Raising soil nutrients amplified several primary metabolites including N-based amino acids and concomitantly reduced the majority of phenylpropanoids, a secondary metabolite group containing many defensive compounds. This work seeks to better understand, how abiotic conditions in a new environment, influence invasive plant metabolism, potentially altering the efficiency of foliage assimilation which may impair biocontrol agent establishment and effectiveness. Such understanding may be applied to mitigate potential foliar deficiencies at release sites and contribute to improving success rates of biocontrol as a management strategy for invasive plants.

Drivers of Viral Diversity and Sharing in Marine Mammals - Matthew J. Arnold; Laura M. Bergner; Haris Malik; Mariel ten Doeschate; Nicholas J. Davison; Andrew Brownlow; Nardus Mollentze; Simon A. Babayan; Daniel G. Streicker (Molecular Ecology, 2026)
Knowledge of viral infection in marine mammals, a group severely threatened by human activity, is largely limited to the pathology and epidemiology of few endemic viruses. The recent emergence in marine mammals of high‐consequence viruses, such as H5N1 avian influenza and rabies, underscores the importance of understanding the ecology of viral transmission in these species. Metatranscriptomic approaches now enable relatively unbiased characterisation of full viral communities that can reveal ecological and evolutionary drivers of infection. We sequenced RNA from 15 marine mammal species (42 pools, 237 tissues, 128 animals) sampled in Scotland through the Scottish Marine Animal Strandings Scheme. Viral sequences were detected in 41 of 42 pools, representing more than 120 distinct viral taxonomic units (vOTUs). Virus host network analysis showed that viral communities were partly structured by host taxonomy, with clear differences between seals and cetaceans. However, vOTUs were frequently shared between species, mirroring reported ecological interactions, including cross‐order sharing between seals and cetaceans. Generalised linear models showed no effect of host taxonomy on viral richness. Instead, age was the strongest predictor: juvenile pools contained roughly twice as many viral taxa as adults and more than neonates, indicating that changing population demography may impact viral transmission in marine mammals. These results provide a basis for understanding how anthropogenic stressors may exacerbate viral transmission in marine mammals and demonstrate the increasing practicality of using genomics to understand ecological and evolutionary drivers of virus infection in natural populations.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Effects of Microbial Biomass and Mineral Premixes on Growth Performance and Nutrient Utilisation in Penaeus monodon Fed Low Fishmeal Diets - Ha H. Truong; Matthew R. P. Briggs; Barney M. Hines; Nicholas A. Bourne; Artur N. Rombenso; Cedric J. Simon (Fishes, 2026)
The growth performance of Penaeus monodon is often reduced when fishmeal is extensively replaced with terrestrial ingredients. This study evaluated the efficacy of a marine microbial biomass, NovaqPro™ (NQ), and inorganic mineral premixes in improving the performance of low fishmeal diets. Diets containing soybean meal, soy protein concentrate, and bloodmeal were formulated with fishmeal limited to 6%. Treatments included 10% NQ, an experimental inorganic mineral premix, a commercial mineral premix, and their combinations added to the low fishmeal control. A high fishmeal diet was also assessed as a benchmark of performance. NQ supplementation significantly improved shrimp growth, increasing weight gain by 78.7% compared with the low fishmeal control (2.77 vs. 1.55 g shrimp−1) and numerically improved by 25.3% compared with the high fishmeal diet (2.21 g shrimp−1). Similar responses were observed for FCR where NQ diets (1.47–1.68), as well as the high fishmeal diet (1.59), were superior to that of the control diet (2.02). Growth improvements were associated with increased feed intake and higher retention of protein and gross energy. In contrast, mineral premix supplementation did not improve growth, and weight gain was numerically reduced relative to the low fishmeal control. The NQ diet showed higher apparent digestibility of calcium, phosphorus, and magnesium compared with the high fishmeal diet. These results demonstrate that NQ is an effective mitigation strategy to reduce growth limitations associated with low fishmeal diets in P. monodon, without the need for additional inorganic mineral supplementation.

Possible dickinsoniomorphs from the latest Ediacaran Nama Group, southern Namibia - Brandt M. Gibson; Joshua H.F.L. Davies; Simon A.F. Darroch; Ajani Bissick; Andrea Boscaini; Galen P. Halverson; Frederick J. Hilgen; Peter R. Liberty; Johnathan A. Sorrentino; Bianca R. Spiering; Patricia Vickers-Rich; Marc Laflamme (Precambrian Research, 2026)

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Computational Modeling of Flow in an in Vitro Cerebrovascular Model Under Pulsatile Conditions with Experimental Validation - Boyang Su; Brent A. Craven; Cody J. Kubicki; Daniel Khalil; Scott D. Simon; Keefe B. Manning (Cardiovascular Engineering and Technology, 2026)
Purpose Computational fluid dynamics (CFD) has been widely used to understand various cardiovascular diseases such as acute ischemic stroke (AIS), which occurs when a blood clot lodges in the cerebrovasculature and obstructs blood flow that may lead to brain damage or death. Compared with medical imaging, CFD can predict hemodynamics and clot migration, which are crucial in better understanding the biomechanics of AIS. To rely on computational modeling, however, the simulations need to be validated by comparing with experiments Methods In this study, we develop an in vitro experimental model of pulsatile flow in the aorta and cerebrovasculature. The model was filled with a blood analog fluid and pulsatile flow was driven by a piston pump to generate realistic physiological flow conditions. Experimental measurements of the time-varying pressure and flow rate were acquired and are used to validate corresponding CFD simulations Results CFD predictions of the time-averaged pressure at the outlets are shown to be within 8% of the experimental measurements, while the time-averaged flow rate is within 1%. Conclusions This work demonstrates a promising capability for modeling embolus migration and lodging in the brain. Future work will validate simulations of clot migration that may be used to better understand AIS biomechanics and treatment options.

Assessing the intensity of Late Quaternary humid phases in the Nefud Desert, northern Arabia - Richard Clark‐Wilson; Simon J. Armitage; Ian Candy; Paul S. Breeze; Nick A. Drake; Huw S. Groucutt; Abdullah M. Alsharekh; Faisal Al‐Jibreen; Michael D. Petraglia; David B. Ryves (Journal of Quaternary Science, 2026)
The climate history of the major dryland zones of the world, such as the Saharo–Arabian Desert belt, plays a key role in the dispersal of early humans through these intermittently inhospitable regions. Here, we assess the relative intensity of Late Quaternary humid phases in northern Arabia through lithological, geochemical, palaeoecological and geochronological analysis of three sediment sequences in the Nefud Desert. Two sequences are marl beds that accumulated in perennial, groundwater‐fed lake systems during two distinct humid phases that occurred in MIS 5e and MIS 5a. The third records sediment accumulation within an ephemeral lake system during the terminal Pleistocene/early Holocene. The altitude of the two MIS 5 deposits indicates that the water table must have reached altitudes of >929 m ASL (MIS 5e) and >922 m ASL (MIS 5a). In contrast, the sedimentary characteristics of the early Holocene sequence imply that, during this interval, the water table was

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

From spontaneous apple fermentations to Calvados: Insights into its aromatic complexity - B. Misery; P. Legendre; J.-P. Simon; V. Bouchart; H. Guichard; A. Sesboue; J.-M. Laplace; M. Cretenet (International Journal of Food Microbiology, 2026)

Guidelines for producing integrated 210Pb and 14C age-models - Joan-Albert Sanchez-Cabeza; Marco A. Aquino-López; Maarten Blaauw; Ana Carolina Ruiz-Fernández; Johanna L.J. Jupin; Lysanna Anderson; Clarke A. Knight; Marie Rhondelle Champagne; Nicole K. Sanderson; Simon Goring; J. Andrés Christen (Earth-Science Reviews, 2026)

Compassionate conservation practice: supporting diverse conservation actions but context matters - Adam P.A. Cardilini; Liv Baker; William S. Lynn; William T. Borrie; Shelley M. Alexander; Dror Ben-Ami; Simon Coghlan; Tristan Derham; Oded Keynan; Barbara J. King; Christine M. Reed; Erin A. Ryan; et al. (Biological Conservation, 2026)

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

Access to agricultural lands influences the effects of seasonal drought on early growth and juvenile body mass in a large herbivore - Noa Rigoudy; Nicolas Morellet; Arnaud Bonnet; Nicolas Cebe; Simon Chamaillé-Jammes; Yannick Chaval; Jean-Michel Gaillard; Bruno Lourtet; Joël Merlet; Jean-Luc Rames; A. J. Mark Hewison (Oecologia, 2026)

Basking sharks (Cetorhinus maximus) in the Northeast Atlantic show high occurrence of parasitism by sea lamprey (Petromyzon marinus) - Fiona S. A. Bracken; Zenia Sherman; Emmett M. Johnston; Nick J. Pfeiffer; Nick Massett; Ken M. O’Sullivan; Shane Wasik; Simon D. Berrow; Mary Kelly-Quinn; Jens Carlsson (Hydrobiologia, 2026)
Sea lamprey ( Petromyzon marinus ) are anadromous fish that spend one to two years as haematophagous ectoparasites in marine environments. This study provides the first quantitative insight into their feeding phase, which remains poorly understood. We investigate the occurrence of P. marinus feeding on basking sharks ( Cetorhinus maximus ) in the Northeast Atlantic. Between 2011 and 2020, 775 records of basking sharks were collected via video, photographs and written observations. After quality control, 434 records were analysed. Of these, 41.8% showed lampreys attached. The number of lampreys per shark ranged from one to eight, with an average of 1.9 (± 1.4 SD). Lampreys were significantly more likely to attach to the ventral surface, although attachment site was not linked to shark sex. We discuss mechanisms of attachment, as well as the role of shark migratory behaviour and olfactory cues from coastal aggregations that may increase opportunities for P. marinus to attach. This study provides the first evidence of a significant ecological association between the two species, suggesting C. maximus may be a preferred or more accessible host. These findings offer new insight into lamprey ecology and may inform understanding of how this species could respond to future environmental change.

A method to identify positive tipping points to accelerate low-carbon transitions and actions to trigger them - Timothy M. Lenton; Thomas W. R. Powell; Steven R. Smith; Frank W. Geels; Floor Alkemade; Martina Ayoub; Pete Barbrook-Johnson; Scarlett Benson; Fenna Blomsma; Chris A. Boulton; Joshua E. Buxton; Sara M. Constantino; et al. (Sustainability Science, 2026)
Meeting the Paris Agreement to limit global warming to “well below 2 °C” requires a radical acceleration of action, as the global economy is decarbonising at least five times too slowly. Tipping points, where low-carbon transitions become self-propelling, could be key to achieving the necessary acceleration. We deem these normatively ‘positive’, because they can limit considerable, inequitable harms from global warming and help achieve sustainability. Some positive tipping points, such as the UK’s elimination of coal power, have already been reached at national and sectoral scales. The challenge now is to credibly identify further potential positive tipping points, and the actions that can bring them forward, whilst avoiding wishful thinking about their existence, or oversimplification of their nature, drivers, and impacts. Hence, we propose a methodology for identifying potential positive tipping points, assessing their proximity, identifying the factors that can influence them, and the actions that can trigger them. Building on relevant research, this ‘identifying positive tipping points’ (IPTiP) methodology aims to establish a common framework that we invite fellow researchers to help refine, and practitioners to apply. To that end, we offer suggestions for further work to improve it and make it more applicable.

Spaceborne estimates of canopy temperature and soil moisture predict daily and annual subalpine tree growth - Eli W. Estey; Jan U.H. Eitel; Lee A. Vierling; Grace L. Peven; Kerry A. Cawse-Nicholson; Simon J. Hook; Kevin L. Griffin (Agricultural and Forest Meteorology, 2026)

Recycling of ash particles during highly explosive eruptions: multiple glass populations in the 1.8 ka Taupō tephra - Simon J. Barker; Stephen B. Piva; Colin J. N. Wilson; David J. Lowe; Bruce L. A. Charlier; Alan R. Orpin (Bulletin of Volcanology, 2025)

Two contrasting swamp forest succession pathways in central Congo Basin peatlands - Donna Hawthorne; Ian T. Lawson; Greta C. Dargie; Nicholas T. Girkin; Bart Crezee; William Hiles; George E. Biddulph; Yannick E. Bocko; Arnoud Boom; Corneille E.N. Ewango; Yannick Garcin; Pauline Gulliver; et al. (Quaternary Science Reviews, 2025)

Fracture analysis of the lithium-bearing Cligga Head granite: Impacts on critical mineral mobilisation and fluid flow - Andrew J.M. Evans; Natalie J.C. Farrell; David A. Neave; Margaret E. Hartley; David Healy; John P. Waters; Tara R. McElhinney; Joshua J. Shea; Nico Bigaroni; Simon A. Hunt (Journal of Structural Geology, 2025)

Halogenated persistent organic pollutants in selected processed small fish species from Ghana - L. Uhr; J. Pucher; A. Atter; A. Jahnke; A. Jährmann; M. Kjellevold; K. Simon; L. Wessels; M. Yamamoto; A. Lüth (Food Chemistry, 2025)

Integrated valuation of instrumental and relational values of marine protected areas in the United Arab Emirates - Jasper O. Kenter; Simon J. Pittman; Marina Antonopoulou; Balagopal Menon; Kostantinos A. Stamoulis; Maitha M. Al Hameli; Daniel Mateos-Molina (Ecosystem Services, 2025)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

The impacts of novel lyophilized milk fermented with potential probiotic Lactobacillus sp. on the physiological indicators, meat characteristics, blood parameters, and gene expression in weaned rabbits - Ebrahim Elkhtab; Ali Osman; Rania M. Y. Heakel; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ahmed A. Aly; Mohamed H. Abdel Aal; Islam Sabeq; Shimaa A. Amer; Simon J. Davies; Tharwat A. Imbabi (Tropical Animal Health and Production, 2025)

First dinosaur remains from Serbia: Sauropod and theropod material from the uppermost Cretaceous (Maastrichtian) of Osmakovo - Zoran Marković; Miloš Milivojević; Richard J. Butler; Paul M. Barrett; Simon Wills; Andrew A. van de Weerd; Wilma Wessels; Predrag Radović (Cretaceous Research, 2025)

Bryde's whale ( Balaenoptera edeni ) occurrence and foraging behaviour along the east coast of Australia - Vanessa Pirotta; Daniele Cagnazzi; Brett Dixon; Simon Millar; Jessica Millar; Greg Pickering; Paul A. Butcher; Karen A. Stockin; Katharina J. Peters (New Zealand Journal of Marine and Freshwater Research, 2025)
Despite their global occurrence in warm‐temperate waters and their suspected non‐migratory lifestyle, Bryde's whales ( Balaenoptera edeni spp.) are considered the least‐known large baleen whale species. In Australian waters, information on their distribution, ecology and behaviour is scarce. This study documents Bryde's whale occurrence and foraging behaviours along the Australian East Coast using opportunistic citizen science sightings via drone aerial photography, vessel and land‐based observations. We observed foraging in both shallow (seafloor visible, beach and breaking waves present) and deep waters. We observed a range of foraging behaviours including lunge feeding (exhibited by individual whales and in pairs), sub‐surface and surface skim feeding (shallow waters only) and described multispecies associations. We describe a potentially novel feeding behaviour in shallow waters, where Bryde's whales are feeding directly within or behind the surf break ( shallow water surf feeding ). We quantify the presence of mother‐calf pairs in Australian waters, highlighting the use of these waters for potential calving. This study provides insights into Bryde's whale occurrence and foraging behaviour in both shallow and deep waters of eastern Australia.

Correction to: Effects of neonicotinoids and fipronil on non-target invertebrates - L. W. Pisa; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; C. A. Downs; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; M. McField; C. A. Morrissey; D. A. Noome; et al. (Environmental Science and Pollution Research, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Oxylipin signalling in a coral-dinoflagellate symbiosis - Andrea G. Gamba; Saki Harii; Frederic Sinniger; Clinton A. Oakley; Arthur R. Grossman; Virginia M. Weis; David J. Suggett; Simon K. Davy (Coral Reefs, 2025)
The symbiotic relationship of cnidarians with dinoflagellates of the family Symbiodiniaceae is based on host-symbiont recognition processes and continuous molecular exchange between partners. However, the molecular signals involved are unresolved. Oxylipin signalling plays a pivotal role in mediating various cellular processes, including inflammation and molecular signalling. Its function in the cnidarian-dinoflagellate symbiosis, including its potential role in inter-partner molecular communication, remains unclear. Here, prostaglandin EP2 receptors 2 (EP2) and 4 (EP4) were localised and quantified using immunohistochemistry in the tissues of the coral Acropora sp. aff. tenuis . Both coral larvae and polyps of juvenile colonies were examined when in symbiosis with one of their two native dinoflagellate symbionts, Cladocopium goreaui and Durusdinium trenchii , during early (3 days) and later (30 days) stages of symbiosis establishment (relative to aposymbiotic corals). EP2 and EP4 were present in both the gastrodermis and epidermis of larvae and polyps, regardless of their symbiotic state. Abundance of EP2 and EP4 was affected by symbiotic state, symbiont identity, coral life-stage, and the age of the symbiosis. Specifically, D. trenchii , but not C. goreaui , decreased host EP2 levels in larvae and polyps, and EP4 levels in coral polyps. Conversely, C. goreaui , but not D. trenchii , decreased EP4 levels in coral larvae. This research enhances our understanding of oxylipin pathway regulation in the coral-dinoflagellate symbiosis across various life-stages, and in response to different symbiont species, laying the groundwork for deeper exploration into the molecular signalling mechanisms that underlie this symbiosis and the influence of coral metamorphosis on these mechanisms.

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

“Wood-lover paralysis”: Describing a toxidrome with symptoms of weakness caused by some lignicolous “wood-loving” Psilocybe mushrooms - Simon A. Beck; Caine Barlow; Liam Engel; Monica J. Barratt (Toxicon, 2025)

Unravelling the pedogenetic development of forest soils in Northern Patagonia, Argentina - Alois Simon; Ernesto J. Reiter; Franz Zehetner; María Florencia Urretavizcaya; Virginia Alonso; Gabriel A. Loguercio; Franz Ottner; Helge Walentowski (CATENA, 2025)

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

Understanding and Predicting Population Response to Anthropogenic Disturbance: Current Approaches and Novel Opportunities - Cassie N. Speakman; Sarah Bull; Sarah Cubaynes; Katrina J. Davis; Sébastien Devillard; John M. Fryxell; Cara A. Gallagher; Elizabeth A. McHuron; Kévan Rastello; Isabel M. Smallegange; Roberto Salguero‐Gómez; Elsa Bonnaud; et al. (Ecology Letters, 2025)
Effective conservation of biodiversity depends on the successful management of wildlife populations and their habitats. Successful management, in turn, depends on our ability to understand and accurately forecast how populations and communities respond to human‐induced changes in their environments. However, quantifying how these stressors impact population dynamics remains challenging. Another significant hurdle at this interface is determining which quantitative approach(es) are most appropriate given data types, constraints and the intended purpose. Here, we provide a cross‐taxa overview of key methodological approaches (e.g., matrix population models) and model elements (e.g., energetics) that are currently used to model the effects of anthropogenic disturbance on wildlife populations. Specifically, we discuss how these modelling approaches differ in their key assumptions, in their structure and complexity, in the questions they are best poised to address and in their data requirements. Our intention is to help overcome some of the methodological biases that might persist across taxonomic specialisations, identify new opportunities to address existing modelling challenges and improve scientific understanding of the direct and indirect impacts of anthropogenic disturbance. We guide users through the identification of appropriate model configurations for different management purposes, while also suggesting key priorities for model development and integration.

Comparing the modulatory effect of fennel powder and fennel extract nanoparticles on growth, immunity and histopathological changes of Nile tilapia - Shaimaa A.A. Ahmed; Abdelhakeem El-Murr; Yasser Abd Elhakim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Mohamed M. Metwally; Amany Abd El Aziz Gharib; Enas N.M. Khalil (Aquaculture, 2025)

Range‐Wide Genomic Analysis Reveals Regional and Meta‐Population Dynamics of Decline and Recovery in the Grey Seal - Morgan L. McCarthy; Kristina M. Cammen; Sandra M. Granquist; Rune Dietz; Jonas Teilmann; Charlotte Bie Thøstesen; Simon Kjeldgaard; Mia Valtonen; Mervi Kunnasranta; Bjørn Munro Jenssen; Markus P. Ahola; Britt‐Marie Bäcklin; et al. (Molecular Ecology, 2025)
Wildlife populations globally have experienced widespread historical declines due to anthropogenic and environmental impacts, yet for some species, contemporary management and conservation programmes have enabled recent recovery. The impacts of decline and recovery on genomic diversity and, vice versa, the genetic factors that contribute to conservation success or failure are rich areas for inquiry, with implications for shaping how we manage species into the future. To comprehensively characterise these processes in natural systems requires range‐wide sampling and international collaboration, particularly for species with wide dispersal capabilities, broad geographic distributions, and complex regional metapopulation dynamics. Here, we present the first range‐ and genome‐wide population genomic analysis of grey seals based on 3812 nuclear SNPs genotyped in 188 samples from 17 localities. Our analyses support the existence of three main grey seal populations centred in the NW Atlantic, NE Atlantic and Baltic Sea, and point to the existence of previously unrecognised substructure within the NE Atlantic. We detected remarkably low levels of genetic diversity in the NW Atlantic population, and demographic analyses revealed a turbulent history of NE Atlantic and Baltic Sea grey seals, with bottlenecks in the Middle Ages and the 20th century due to hunting and habitat alterations. We found some localities deviated from isolation by distance patterns, likely reflecting wide‐scale metapopulation dynamics associated with recolonisation and recovery in regions where they were historically extirpated. We identify at least six grey seal genetic populations and reveal marked genetic effects of past declines and recent recovery across the species' range.

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

Assessment of heavy metal pollution from flooded rice farms in Hadejia LGA of Jigawa State Nigeria: an impact of climate change - J. Simon; E. A. Ibanga; E. P. Inyang; H. G. Kama; K. O. Momoh; S. Bello; A. G. Yisa (Environmental Monitoring and Assessment, 2025)

Whale shark residency and small-scale movements around oil and gas platforms in Qatar - Steffen S. Bach; David P. Robinson; Mohammed Y. Al Jaidah; Simon J. Pierce; Prasad Thoppil; Christoph A. Rohner (Frontiers in Marine Science, 2025)
Whale sharks seasonally aggregate near oil and gas platforms in Qatar to feed on fish spawn, creating one of the world’s largest aggregations of the species. We used passive acoustic telemetry to examine their fine-scale movements, residency, and seasonality and investigate whether the platforms influence their space use in this area. Tags had a mean retention of 161 ± 186 days (standard deviation, SD) and 32 of the 117 tags were recorded in multiple years in the acoustic array (21 stations). Most detections were recorded from May to September, confirming that this whale shark aggregation is seasonal. Whale sharks stayed up to 77 consecutive days in the array (mean = 16 ± 12.51 days) and had a mean residency index R max of 0.31. Although most detections (65%) were made at a single receiver located near a platform, here designated P1, an ‘open water’ receiver near this location also had a high proportion of total detections (8.5%). Receivers at other platforms, located away from this specific site, had relatively few detections. The distance from P1, identified as the center of the aggregation, was the main explanatory variable in a GAM. Whale shark aggregations were routinely observed feeding on tuna spawn at the surface at this location, with the eggs (and hence whale sharks) moving with the current through the day, and moving through the array as they did so. Whale sharks then swam against the current in the late afternoon and at night to relocate back to near the presumed tuna spawning site, close to P1, again in the early morning. Rather than being generally associated with platforms, whale sharks were clearly associated with a specific feeding location close to P1. Our results highlight the importance of this small feeding area for whale sharks, which face a high threat level in the region.

Evaluating public exposure to airborne particulates from major incident fires: A back trajectory plume modelling approach - Simon D. Griffiths; Helen M. King; Justine Wilkinson; Frank J. Kelly; Jane A. Entwistle; Michael E. Deary (Journal of Hazardous Materials, 2025)

Behavioral and neurological responses of Oreochromis niloticus to chronic cyclic hypoxia: mechanistic insights into hypoxia-responsive genes, pro-inflammatory and apoptotic pathways: role of camel whey protein hydrolysate - Amany Abdel-Rahman Mohamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Rowida E. Ibrahim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Abd Elhakeem El-Murr; Simon J. Davies; Yasmina M. Abd-Elhakim (Veterinary Research Communications, 2025)

Genome-wide association analysis identifies seven loci conferring resistance to multiple wheat foliar diseases, including brown and yellow rust resistance originating from Aegilops ventricosa - Keith A. Gardner; Bethany Love; Pauline Bansept-Basler; Tobias Barber; Simon Berry; Nick Bird; Finn Borum; Lesley Boyd; James K. M. Brown; Ruth Bryant; Paul Fenwick; David Feuerhelm; et al. (Theoretical and Applied Genetics, 2025)
We assembled a European bread wheat ( Triticum aestivum L.) association mapping panel ( n = 480) genotyped using a 90,000 feature single nucleotide polymorphism array, with the aim of identifying genetic loci controlling resistance to four fungal diseases: yellow (stripe) rust (YR), brown (leaf) rust (BR), Septoria tritici blotch (ST) and powdery mildew (PM). Simulations showed our panel to have good power to detect genetic loci, with > 50% probability of identifying loci controlling as little as 5% of the variance when heritability was 0.6 or more. Using disease infection data collected across 31 trials undertaken in five European countries, genome-wide association studies (GWAS) identified 34 replicated genetic loci (20 for YR, 12 for BR, two for PM, 0 for ST), with seven loci associated with resistance to two or more diseases. Construction and analysis of eight bi-parental populations enabled two selected genetic loci, yellow rust resistance locus YR_2A010 (chromosome 2A) and YR_6A610 (6A), to be independently cross-validated, along with the development of genetic markers to track resistance alleles at these loci. Notably, the chromosome 2A yellow and brown rust resistance locus corresponds to the 2N v S introgression from the wild wheat species, Aegilops ventricosa . We found evidence of strong selection for 2N v S over recent breeding history, being present in 48% of the most recent cultivars in our panel. Collectively, we define the genetic architectures controlling resistance to major fungal diseases of wheat under European field environments, and provide resources to exploit these for the development of new wheat cultivars with improved disease resistance.

Movements and habitat use of reef manta rays around the Mozambique Channel Island of Mayotte, Southwestern Indian Ocean - Christoph A. Rohner; Stephanie K. Venables; Anna M. Knochel; Joshua M. Rambahiniarison; Vyctoria Marillac; Clémentine Cardon; Naomi Scholten; Simon J. Pierce; Jeremy J. Kiszka (Environmental Biology of Fishes, 2025)

Antiviral siRNA delivered using attenuated, anthrax toxin protects cells from the cytopathic effects of Zika virus - Benedita K. L. Feron; Timothy Gomez; Natalie C. Youens; Nourhan A. M. Mahmoud; Hadeer K. S. Abdelrahman; Joachim J. Bugert; Simon C. W. Richardson (Virus Genes, 2025)
Curative drugs are needed for the treatment of viral infections. Small interfering (si)RNA offer such a prospect but require the development of safe, effective and non-hepatotropic subcellular delivery systems. Here, 5 candidate siRNA molecules targeting defined sequences within the Zika Virus (ZIKV) genome were assayed for their ability to reduce ZIKV induced cytopathic effects in vitro. The protection of Huh-7 cells from ZIKV cytopathic effects was recorded after electroporation and the siRNA Feron-Zv2, resulting in 122.7 ± 5.3% cell viability ( n = 3 ± standard error of the mean (SEM), 100 nM siRNA) after exposure to ZIKV relative to a virus treated control (35.2 ± 7.1% cell viability ( n = 3 ± SEM)). Protection of BHK-21 cells was recorded after transfection with an attenuated anthrax toxin containing an RNA binding domain. Treatment with Feron-Zv4 resulted in 75.1 ± 2.9% cell viability ( n = 3 ± SEM, 25 nM siRNA) after exposure to ZIKV. This protection was mirrored by a system containing octameric PA where a maximum of 86.2 ± 4.4% cell viability was reported ( n = 3 ± SEM, 75 nM siRNA) after treatment with Feron-Zv2. Scrambled siRNA afforded no measurable protection. Here we report for the first time that siRNA delivered by either attenuated anthrax toxin or octamer forming ATx can protect mammalian cells from ZIKV cytopathic effects.

Investigating the impact of camel whey protein hydrolysate on cyp1a1 and keap1/nrf2 expression in hypoxic stress-affected liver tissue of Oreochromis niloticus - Amany Abdel-Rahman Mohamed; Afaf A. Kishta; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Yasmina M. Abd-Elhakim; Rowida E. Ibrahim; Mohamed M. M. Metwally; Tarek Khamis; Ali Osman; Simon J. Davies; Mohamed A. Elbealy (Journal of Comparative Physiology B, 2025)

Changes in behaviour and serotonergic system of Atlantic salmon (Salmo salar) fry related to different levels of black soldier fly larvae meal inclusion in the diet: Exploring the use of nutritional enrichment for its use as positive welfare in aquaculture - Mauro Chivite-Alcalde; Monica Betancor; Benjamin G J Clokie; Ahmed Elsheshtawy; Emma McDonald; Carlos Ramírez-Rodríguez; Miha Pipan; Simon A. MacKenzie; Sonia Rey Planellas (Applied Animal Behaviour Science, 2025)

The impact of betalains and organic selenium on the physiological responses, blood metabolites, redox status, and semen quality of heat-stressed rabbits - Tharwat A. Imbabi; Eman H. Halawa; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Dina A. Selim; Mohamed H. Abdel Aal; Lamiaa M.M. EL-Maghraby; Abdalla El-Hadary; Shimaa A. Amer; Simon J. Davies; Mohamed S. Basiouny; Mahmoud Sitohy; et al. (Animal Feed Science and Technology, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Submerged Corridors of Ancient Gene Flow in an Island Amphibian - Miranda B. Sherlock; Mark Wilkinson; Simon T. Maddock; Ronald A. Nussbaum; Julia J. Day; Jeffrey W. Streicher (Molecular Ecology, 2025)
Many island archipelagos sit on shallow continental shelves, and during the Pleistocene, these islands were often connected as global sea levels dropped following glaciation. Given a continental shelf only 30–60 m below sea level, the terrestrial biota of the Seychelles Archipelago likely dispersed amongst now isolated islands during the Pleistocene. Hypogeophis rostratus is an egg‐laying, direct‐developing caecilian amphibian found on 10 islands in the granitic Seychelles. Despite the seemingly limited dispersal abilities of this salt‐intolerant amphibian, its distribution on multiple islands suggests likely historic dispersal across now submerged continental shelf corridors. We tested for the genetic signature of these historic corridors using fine‐scale genomic data (ddRADseq). We found that genomic clusters often did not correspond to islands in the archipelago and that isolation‐by‐distance patterns were more consistent with gene flow across a continuous landscape than with isolated island populations. Using effective migration surfaces and ancestral range expansion prediction, we found support for contemporary populations originating near the large southern island of Mahé and dispersing to northern islands via the isolated Frégate island, with additional historic migration across the flat expanse of the Seychelles bank. Collectively, our results suggest that biogeographic patterns can retain signals from Pleistocene ‘palaeo‐islands’ and that present‐day islands can be thought of as hosting bottlenecks or transient refugia rather than discrete genetic units. Thus, the signatures of gene flow associated with palaeo‐islands may be stronger than the isolating effects of contemporary islands in terrestrial species distributed on continental shelf islands.

Genomic Analysis Reveals a New Cryptic Taxon Within the Anopheles gambiae Complex With a Distinct Insecticide Resistance Profile in the Coast of East Africa - Sophia H. Mwinyi; Kelly L. Bennett; Sanjay C. Nagi; Bilali Kabula; Johnson Matowo; David Weetman; Francesco Baldini; Simon A. Babayan; Martin J. Donnelly; Chris S. Clarkson; Fredros O. Okumu; Alistair Miles (Molecular Ecology, 2025)
Anopheles mosquitoes are major malaria vectors, encompassing several species complexes with diverse life histories, transmission risks and insecticide resistance profiles that challenge malaria control efforts. This study investigated the genetic structure and insecticide resistance profiles of Anopheles gambiae complex mosquitoes in Tanzania. We analysed whole‐genome sequence data of 300 mosquitoes collected between 2012 and 2015 across four regions in northern Tanzania and identified An. gambiae s.s., An. arabiensis and a distinct taxonomic group that was previously unknown. This distinct taxon has a unique profile of genetic diversity and appears restricted to the coastal region, and we refer to it as the Pwani molecular form. Analysis of insecticide resistance based on target‐site mutations and copy number variations (CNV) showed that these markers were strikingly absent from the Pwani molecular form in contrast to other taxa. Our analysis also revealed a pattern of geographical isolation in the An. gambiae s.s. populations, with samples from the north‐western site (Muleba) clustering separately from those collected in the north‐eastern site (Muheza). These geographically isolated subpopulations also had differing resistance and selection profiles, with An. gambiae s.s. from the north‐western site showing genomic evidence of higher resistance to pyrethroids compared with the north‐eastern population. Conversely, An. arabiensis showed no geographical population structuring, with a similar insecticide resistance profile across all sampling locations, suggesting unrestricted gene flow. Our findings underscore the need to incorporate genetic data into malaria vector surveillance and control decisions and could inform the development and deployment of new interventions.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Earth's most needed uncultivated aquatic prokaryotes - Sophie A. Simon; Vera Aschmann; Annika Behrendt; Michael Hügler; Lisa M. Engl; Marion Pohlner; Sönke Rolfes; Thorsten Brinkhoff; Bert Engelen; Martin Könneke; Luis M. Rodriguez-R; Till L.V. Bornemann; et al. (Water Research, 2025)

Ultraviolet radiation vs air filtration to mitigate virus laden aerosol in an occupied clinical room - Shane A. Landry; Milan Jamriska; Vinay J. Menon; Leo Yi Yang Lee; Isabelle Magnin-Bougma; Dinesh Subedi; Jeremy J. Barr; Jason Monty; Kevin Kevin; Ajith Gunatilaka; Michelle Delaire; Guy B. Marks; et al. (Journal of Hazardous Materials, 2025)

Late Cenozoic intensification of deoxygenation in the Pacific Ocean - Katrina Nilsson-Kerr; Babette A.A. Hoogakker; Dharma A. Reyes Macaya; Helge A. Winkelbauer; Elliott Hamilton; Simon Chenery; Catherine V Davis; Melanie J. Leng (Earth and Planetary Science Letters, 2025)

Alleviative potential of dietary essential oils against nickel toxicity triggers neurobehavioral abnormalities, biochemical dysfunction, and histopathological alterations in Nile tilapia - Shaimaa A. A. Ahmed; Ali Adel Ali Ahmed; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Mai Farag Saad; Simon J. Davies; Rowida E. Ibrahim; Asmaa Edrees (Veterinary Research Communications, 2025)

Ameliorative potential of Populus alba leaf powder against hexaflumuron exposure in Nile tilapia: immune-antioxidant, biochemical, histological, and transcriptomic analysis - Rowida E. Ibrahim; Mohamed F. M. Farag; Mohammed S. Sobh; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Shefaa M. Bazeed; Aya Elgamal; Tarek Khamis; Simon J. Davies; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Carbonate alkalinity induces stress responses and renal and metabolic disorders in Nile tilapia: mitigation by camel whey protein hydrolysate diet - Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Amany Abdel-Rahman Mohamed; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Yasmina M. Abd-Elhakim (Fish Physiology and Biochemistry, 2025)

Correction to: Persistent declines in sightings of manta and devil rays (mobulidae) at a global hotspot in southern mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)

Persistent declines in sightings of manta and devil rays (Mobulidae) at a global hotspot in southern Mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)
Mobulid rays are among the most vulnerable of chondrichthyans to overexploitation by fisheries due to their low population growth rates. In locations where catch data are lacking, long-term sightings data can provide valuable insight to infer population trends and status. We recorded underwater sighting data of reef manta rays ( Mobula alfredi ), oceanic manta rays ( M. birostris ), and shorthorned pygmy devil rays ( M. kuhlii ) between 2003 and 2023 in the waters off Praia do Tofo in the Inhambane Province, southern Mozambique, one of the major global hotspots for these rays. We modelled sightings data using a hierarchical generalised linear mixed model framework to account for a suite of environmental variables when examining temporal trends. Raw trend models including only ‘year’ as a predictor showed a 99% decline in sightings of reef manta rays, a 92.5% decline in oceanic manta ray sightings, and an 81.3% decline in devil ray sightings over the 20-year study period. The declining trends persisted for reef and oceanic manta rays once a suite of temporal and environmental variables were accounted for, indicating that the declines were driven by external factors not tested in the models. For shorthorned pygmy devil rays, models that incorporated environmental variables did not retain year as a significant predictor and showed a reduced overall decline in sightings of 36.5%. This indicates that the tested predictors were responsible for approximately half of the observed decline. Anthropogenic factors, particularly fisheries mortality, are likely to have played a significant role in the declining sightings of these three Threatened species. Improved conservation and management measures at a national and international level are critical to prevent further declines, which may otherwise lead to localised extinction.

Seed Production and 22 Years of Climatic Changes in an Everwet Neotropical Forest - Jason Vleminckx; J. Aaron Hogan; Margaret R. Metz; Liza S. Comita; Simon A. Queenborough; S. Joseph Wright; Renato Valencia; Milton Zambrano; Nancy C. Garwood (Ecology Letters, 2025)
Examining the cues and drivers influencing seed production is crucial to better understand forest resilience to climate change. We explored the effects of five climatic variables on seed production over 22 years in an everwet Amazonian forest, by separating direct effects of these variables from indirect effects mediated through flower production. We observed a decline in seed production over the study period, which was primarily explained by direct effects of rising nighttime temperatures and declining average vapour pressure deficits. Higher daytime temperatures were positively related to seed output, mainly through a flower‐mediated effect, while rainfall effects on seed production were more nuanced, showing either positive or negative relationships depending on the seasonal timing of rains. If these trends continue, they are likely to lead to significant changes in forest dynamics, potentially impacting both forest structure and species composition.

Non-serous ovarian cancer in PTEN Hamartoma Tumor Syndrome: additional evidence for increased risk - Ane J. Schei-Andersen; Vera M. Witjes; Janet R. Vos; Arjen R. Mensenkamp; Anne van Altena; Jolanda Schieving; Michiel Simons; Janneke H. M. Schuurs-Hoeijmakers; Muriel A. Adank; Liselotte P. van Hest; Yvette van Ierland; Mirjam de Jong; et al. (Familial Cancer, 2025)
Increased hereditary cancer risk is one of the hallmarks of PTEN Hamartoma Tumor Syndrome (PHTS) which is caused by a pathogenic germline variant in PTEN . Case reports and some cohort studies have described ovarian cancer (OC) in PHTS patients. Previously, we observed an enrichment of non-serous OC in PHTS compared to sporadic cases (3% vs 1%). However, ovarian cancer is currently not considered a PHTS-related cancer. The aim of this study was to describe five PHTS patients with a pathogenic germline variant in PTEN with non-serous OC. Three of the non-serous OCs were mucinous carcinomas (49, 51 and 52 years) and two were malignant germ cell tumors (8 and 15 years) and all were diagnosed before genetic testing and PHTS diagnosis. In addition to OC, the described patients developed other PHTS-related benign and malignant lesions. We provide further evidence that non-serous ovarian cancer, especially mucinous, endometrioid and malignant germ cell tumors should be further investigated as potential PHTS-related cancers.

Associations between metabolomic scores and clinical outcomes in hospitalized COVID-19 patients - Jens A. Venema; Anna Kuranova; Daniele Bizzarri; Simon P. Mooijaart; Angele P. M. Kerckhoffs; Kitty Slieker; Evertine J. Abbink; Harmke A. Polinder-Bos; Eline Slagboom; Geeske Peeters; Jacobijn Gussekloo; Karel G. M. Moons; et al. (GeroScience, 2025)
The disease course and outcome of COVID-19 greatly varies between individuals. To explore which biological systems may contribute to this variation, we examined how individual metabolites and three metabolic scores relate to COVID-19 outcomes in hospitalized COVID-19 patients. The metabolome of 346 patients was measured using the 1H-NMR Nightingale platform. The association of individual metabolomic features and multi-biomarker scores, i.e. MetaboHealth, MetaboAge, and Infectious Disease Score (IDS) (higher scores reflect poorer health), with in-hospital disease course, long-term recovery, and overall survival were analyzed. Higher values for the metabolites phenylalanine (HR = 1.33, CI = 1.14–1.56), glucose (HR = 1.37, CI = 1.16–1.62) and lactate (HR = 1.38, CI = 1.16–1.63) were associated with mortality. For all three metabolic scores, higher scores were significantly associated with higher odds of a poorer in-hospital disease course (MetaboHealth: OR = 1.61, CI = 1.29–2.02; ΔMetaboAge: OR = 1.42, CI = 1.16–1.74; IDS: OR = 1.55, 1.25–1.93) and with overall survival (MetaboHealth: HR = 1.57, CI = 1.28–1.92; ΔMetaboAge: HR = 1.34, CI = 1.15–1.57; IDS: HR = 1.56, CI = 1.27–1.93). MetaboHealth and ΔMetaboAge showed a stronger association in younger patients (< 70 yrs.) than older patients. No clear patterns were found in associations between the three scores and measures of long-term recovery. In conclusion, the heterogeneity in disease course after SARS-COV2 infection may be explained either by generic biological frailty reflected by the three metabolomics scores or by glycemic control (glucose, lactate) and respiratory distress (phenylalanine).

The role of greenspace in vitamin D status: cross-sectional, observational evidence from the UK Biobank - Chinonso Christian Odebeatu; Darsy Darssan; Joana A. Revez; Charlotte Roscoe; Phu Do; Simon Reid; Nicholas J. Osborne (International Journal of Hygiene and Environmental Health, 2025)

Compassionate conservation in practice: A values-driven, interdisciplinary, pluralistic, and deliberative community - William S. Lynn; Liv Baker; William T. Borrie; Adam P.A. Cardilini; Shelley M. Alexander; Simon Coghlan; Paul Cryer; Gavin T. Bonsen; Tristan T. Derham; Oded Keynan; Christine M. Reed; Sophie Riley; et al. (Biological Conservation, 2025)

Quantifying impacts of seabird bycatch using genetic assignment: A case study of black-footed albatross in U.S. fisheries - Jessie N. Beck; Diana S. Baetscher; Claire Tobin; Scott V. Edwards; Simon Yung Wa Sin; Shannon Fitzgerald; Vanessa J. Tuttle; John Peschon; Wesley A. Larson (Biological Conservation, 2025)

Postglacial Recolonization of the Southern Ocean by Elephant Seals Occurred From Multiple Glacial Refugia - Andrew A. Berg; Megan Askew; Frederik V. Seersholm; Alexander J. F. Verry; A. Rus Hoelzel; Andreanna Welch; Karen Greig; Richard Walter; Michael Knapp; Axel Barlow; Johanna L. A. Paijmans; Jonathan M. Waters; et al. (Global Change Biology, 2025)
The Southern Ocean is warming more rapidly than other parts of our planet. How this region's endemic biodiversity will respond to such changes can be illuminated by studying past events through genetic analyses of time‐series data sets, including historic and fossil remains. Archaeological and subfossil remains show that the southern elephant seal ( Mirounga leonina ) was common along the coasts of Australia and New Zealand in the recent past. This species is now mostly confined to sub‐Antarctic islands and the southern tip of South America. We analyzed ancient seal samples from Australia (Tasmania), New Zealand and the Antarctic mainland to examine how southern elephant seals have responded to a changing climate and anthropogenic pressures during the Holocene. Our analyses show that these seals formed part of a broader Australasian lineage, comprising seals from all sampled locations from the south Pacific sector of the Southern Ocean. Our study demonstrates that southern elephant seal populations have dynamically altered both range and population sizes under climatic and human pressures over surprisingly short evolutionary timeframes for such a large, long‐lived mammal.

Dietary Prunus armeniaca augments antioxidant-immune-capacity, absorptive function, and growth and upregulates nutrient transporters and immune-regulatory genes of Oreochromis niloticus - Afaf N. Abdel Rahman; Sara T. Elazab; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2025)

Evaluating the effectiveness of badger vaccination combined with cattle test-and-removal in managing Bovine Tuberculosis: Insights from a two-host and multi-route transmission model - You Chang; Stefan Widgren; Mart C.M. de Jong; Jamie A. Tratalos; Simon J. More; Nienke Hartemink (Preventive Veterinary Medicine, 2025)

Deep-sea drilling of the 13°30′ N oceanic core complex: Assessing links between fluid flow, metal enrichment and seafloor massive sulfide deposit formation near Semenov-1 - Andrew J. Martin; Bramley J. Murton; Christopher J. MacLeod; John W. Jamieson; Isobel I. Yeo; Sven Petersen; Katie A. McFall; Simon Allerton; Anna Lichtschlag; Christian Bishop; Acer Figueroa; Szu-Ying Lai (Lithos, 2025)

Dietary deacetylated chitin nanoparticles confer protection against diazinon toxicity in male African catfish: evaluation of immune-biochemical, antioxidant, and reproductive profiles - Hiam Elabd; Heba H. Mahboub; Heba S. Hamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samar Kamel; Amany Ramah; Sahar H. Orabi; Sherif M. Shawky; Simon J. Davies; Zeinab Hassan (Fish Physiology and Biochemistry, 2025)

Physiological, biochemical, apoptosis-linked gene expression, and histopathological insights in Nile catfish subjected to toxicity by magnetite nanogel - Yasmina K. Mahmoud; Shaimaa A. A. Ahmed; Heba H. Mahboub; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Ahmed A. Elnegiry; Sherif M. Shawky; Sahar H. Orabi; Sameh H. Ismail; Simon J. Davies; Mahmoud I. M. Darwish (Fish Physiology and Biochemistry, 2025)

Correction to: Influence of astaxanthin‑enriched Haematococcus pluvialis microalgae on the growth efficacy, immune response, antioxidant capacity, proinflammatory cytokines, and tissue histomorphology of hybrid red tilapia - Elsayed A. A. Eldessouki; Gehad E. Elshopakey; Samia Elbahnaswy; Medhat S. Shakweer; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Amira Mili; Yasmin M. Abd El‑Aziz; Sameh A. Abdelnour; El‑Sayed Hemdan Eissa (Aquaculture International, 2025)

Potential of using kidney bean (Phaseolus vulgaris L) protein hydrolysate as a plant protein supplement in Nile tilapia (Oreochromis niloticus) diets: effects on growth, hematology, histology, and blood biochemical parameters - Shimaa A. Amer; Rowida E. Ibrahim; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Simon J. Davies; Medhat S. Shakweer (Aquaculture International, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

An interdisciplinary approach to improving conservation outcomes for parasites - Timothy M. Brown; Alison M. Dunn; Rupert J. Quinnell; Ellen Clarke; Andrew A. Cunningham; Simon J. Goodman (Conservation Biology, 2025)
Parasites represent a significant proportion of Earth's biodiversity and play important roles in the ecology and biology of ecosystems and hosts, making them an important target for conservation. Despite increasing calls to prioritize protection for parasites in the academic literature, they remain undervalued and underrepresented in global biodiversity conservation efforts, not least due to the perception that the interests of parasite and host conservation are opposing and the common misconception that parasites are a threat, rather than a benefit, to conservation. We considered whether taking an interdisciplinary approach to parasite conservation research will generate novel insights and solutions concerning why and how parasite conservation should be practiced for the benefit of parasites, their hosts, ecosystems, and people. We argue that 2 of the main barriers to more widespread parasite conservation are the knowledge gap concerning the role of sociocultural factors affecting the willingness to enact parasite conservation and the lack of a consistent and cohesive philosophical basis for parasite conservation. Possible sociocultural barriers to parasite conservation include misconceptions of the risks posed by parasites, taxonomic bias, differences in conservation values, economic constraints, and technical challenges. The use of social science can generate insights into levels of awareness and support for parasite conservation and improve understanding of how human values and attitudes mediate conservation practices concerning parasites. Such knowledge will have a critical role in addressing sociocultural barriers and improving support for parasite conservation. Issues with the current philosophical basis for parasite conservation include contradictory accounts of which parasites merit conservation, insufficient explanation of how different conservation values apply to parasite biodiversity, and the existence of a false antagonism between host and parasite conservation. Greater engagement with philosophical work on environmental ethics and biological unitization will strengthen existing arguments for parasite conservation and will support conservation decision‐making processes.

Retraction notice to “The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological/immunohistochemical investigation of gills” [Aquaculture 584 (2024) 740639] - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2025)

Lead toxicity in African catfish: Promising role of magnetite nanogel against etho-neurological alterations, antioxidant suppression, gene toxicity, and histopathological/ immunohistochemical disruptions - Afaf N. Abdel Rahman; Heba H. Mahboub; Rasha M.M. Ezz-Eldin; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Tarek Khamis; Enas K. Aziz; Walaa A.A. Basha; Ibrahim Elmaghraby; Simon J. Davies; Sameh H. Ismail; Yasmin A. Reyad (Aquaculture, 2025)

Effect of short-term dopamine reduction on insulin sensitivity and post-prandial insulin and glucose responses in Standardbred horses - Nicolas C. Galinelli; Nicholas J. Bamford; Madison L. Erdody; Tobias Warnken; Melody A. de Laat; Martin N. Sillence; Patricia A. Harris; Simon R. Bailey (Domestic Animal Endocrinology, 2025)

Physiological and metabolic effects of short-term dopamine reduction in healthy horses using a tyrosine hydroxylase inhibitor (alpha-methyl-para-tyrosine) - Nicolas C. Galinelli; Nicholas J. Bamford; Madison L. Erdody; Tobias Warnken; Melody A. de Laat; Martin N. Sillence; Patricia A. Harris; Simon R. Bailey (Domestic Animal Endocrinology, 2025)

The Breeding Bird Survey of the United Kingdom - Dario Massimino; Stephen R. Baillie; Dawn E. Balmer; Richard I. Bashford; Richard D. Gregory; Sarah J. Harris; James J. N. Heywood; Leah A. Kelly; David G. Noble; James W. Pearce‐Higgins; Michael J. Raven; Kate Risely; et al. (Global Ecology and Biogeography, 2025)
Motivation Information on species' population trends is essential to assess species' conservation status, make informed environmental decisions and ultimately reduce biodiversity loss. Robust population trends require a long‐term monitoring programme, often using citizen scientists, that ideally generates representative and unbiased data from the study area. Here we present the dataset of the Breeding Bird Survey, the main scheme for monitoring the population changes of common and widespread breeding birds in the United Kingdom, which achieves this through a randomised sampling scheme and defined field methodology. We also describe the modelling approach used to calculate the population trends, which are the main output of the survey. Main Types of Variable Contained The main published dataset contains 7,070,577 records detailing counts of 217 bird species in 7010 grid cells over 30 years. Data for 78 species that are currently regarded as too sensitive to be released at fine resolution are omitted. As an illustration of the main use of this dataset, we provide population change estimates for 119 bird species. Spatial Location and Grain Grid squares (1 × 1 km) are randomly selected using a stratified sampling scheme throughout the United Kingdom, Isle of Man and Channel Islands. Data in a grid square are collected along two 1‐km‐long transects which are subdivided into 200‐m‐long sections. Time Period and Grain Data have been collected every year since 1994, with two major disruptions in 2001 and 2020, when people's movements were nationally restricted. Grid squares are surveyed twice a year during the main breeding season (April to June). Here we present the data collected from 1994 to 2023. Major Taxa Studied and Level of Measurement Bird species. Software Format Data are supplied as comma‐separated text files.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Cross-cutting studies of per- and polyfluorinated alkyl substances (PFAS) in Arctic wildlife and humans - Rainer Lohmann; Khaled Abass; Eva Cecilie Bonefeld-Jørgensen; Rossana Bossi; Rune Dietz; Steve Ferguson; Kim J. Fernie; Philippe Grandjean; Dorte Herzke; Magali Houde; Mélanie Lemire; Robert J. Letcher; et al. (Science of The Total Environment, 2024)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

Effects of dietary Arthrospira platensis phycocyanin on growth, fatty acid assessment of breast muscles, hematobiochemical, immunological responses, and hepatic histomorphology in broiler chickens - Shimaa A. Amer; Amany Behairy; Amr A. Moustafa; Azhar Eltanahy; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Ahmed Gouda; Simon J. Davies; Samar A. Tolba (Journal of Applied Phycology, 2024)

Tetracycline and Oxacillin Act Synergistically on Biofilms and Display Increased Efficacy In Vivo Against Staphylococcus aureus - Amy K. Tooke; Rebecca E. Hodges; Josie F. Pyrah; Kenneth W. Bayles; Stephen A. Renshaw; Simon J. Foster (Current Microbiology, 2024)
Oxacillin (bactericidal) and tetracycline (bacteriostatic) are clinically relevant antibiotics that are routinely prescribed to treat Staphylococcus aureus infections but not conventionally used in combination. There is an urgent need for treatment regimens that can act upon biofilms during infection, associated with chronic infections on indwelling devices, as well as acute planktonic (systemic) infection. Here we show that in an in vitro model oxacillin and tetracycline act synergistically against S. aureus UAMS-1 biofilms, reducing the concentration of both antibiotics necessary to eradicate an established biofilm. Using an in vivo zebrafish larval infection model with S. aureus NewHG, they display improved bacterial clearance compared to each drug alone and can counteract a loss of host phagocytes, an important innate defence against S. aureus . In these cases, the bacteriostatic nature of tetracycline enhances rather than dampens the bactericidal action of oxacillin, although an exact mechanism remains to be elucidated. We suggest a dual therapy could be of clinical use against biofilm-forming S. aureus and has a potential use in patients with a compromised immune system.

Antagonistic Effect of Zinc Oxide Nanoparticles Dietary Supplementation Against Chronic Copper Waterborne Exposure on Growth, Behavioral, Biochemical, and Gene Expression Alterations of African Catfish, Clarias gariepinus (Burchell, 1822) - Shaimaa A. A. Ahmed; Rowida E. Ibrahim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Khaled Yehia Faroh; Samar A. El Gamal; Shereen Badr; Tarek Khamis; Abdallah Tageldein Mansour; Simon J. Davies; Mohamed ElHady (Biological Trace Element Research, 2024)

Microbial Sulfur Pathways and Outcomes in Tailings Impoundments: A Mesocosm Study - Jay Gordon; Simon C. Apte; Tara E. Colenbrander Nelson; Kelly J. Whaley-Martin; Lauren E. Twible; LinXing Chen; Felicia Liu; Samantha McGarry; Jillian F. Banfield; Lesley A. Warren (Mine Water and the Environment, 2024)

Life in the margins: the effect of immersion/emersion and tidal cycle on the North Atlantic limpet Patella vulgata protein synthesis rates - Ignacio A. Cienfuegos; Benjamin J. Ciotti; Richard A. Billington; Paul A. Sutton; Simon G. Lamarre; Keiron P. P. Fraser (Journal of Comparative Physiology B, 2024)

Evaluating the effectiveness & costs of strategies post-eradication to monitor for freedom from BVDV infection in Ireland - Jonas Brock; Maria Guelbenzu-Gonzalo; Martin Lange; Jamie A. Tratalos; Damien Barrett; Liz Lane; Simon J. More; David A. Graham; Hans-Hermann Thulke (Agricultural Systems, 2024)

Escaping the cohort of concern: in vitro experimental evidence supports non-mutagenicity of N-nitroso-hydrochlorothiazide - R. D. Gandhi; S. Hickert; Y. Hoevelmann; C. D. Mee; J. Schlingemann; A. Adams; A. Blanazs; S. Simon; J. Elloway; L. Rigger; A. Teasdale; C. V. Beaumont; et al. (Archives of Toxicology, 2024)

Camel whey protein hydrolysate diet mitigates alkaline stress–induced biochemical disorders and restores the target of rapamycin, MAPK pathway, and autophagy-related gene expression in Nile tilapia - Rowida E. Ibrahim; Gehad E. Elshopakey; Mohamed Y. M. Aly; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Yasmina M. Abd-Elhakim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Amany Abdel-Rahman Mohamed (Aquaculture International, 2024)

Using moringa (Moringa oleifera) seed protein hydrolysate as a dietary protein supplement modulates hemato-biochemical indices, antioxidant response, and tissue histo-morphology of Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Shimaa A. Amer; Nasreddin R. Rhouma; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Heba M. Abdel-Ghany; Gehad E. Elshobaky; Mahmoud M. El-Saber; Ali Osman; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Efficacy of the dietary Malva parviflora leaves in modulating immune-antioxidant functions, resistance to Candida albicans and Streptococcus agalactiae infection, digestive/absorptive capacity, and growth of Nile tilapia (Oreochromis niloticus) - Afaf N. Abdel Rahman; Yasmin A. Reyad; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Nehal Abd EL-Mageed; Afaf A. Kishta; Asmaa Yaseen; Simon J. Davies; Rowida E. Ibrahim (Aquaculture International, 2024)

Influence of astaxanthin-enriched Haematococcus pluvialis microalgae on the growth efficacy, immune response, antioxidant capacity, proinflammatory cytokines, and tissue histomorphology of hybrid red tilapia - Elsayed A. A. Eldessouki; Gehad E. Elshopakey; Samia Elbahnaswy; Medhat S. Shakweer; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Amira Mili; Yasmin M. Abd El-Aziz; Sameh A. Abdelnour; El-Sayed Hemdan Eissa (Aquaculture International, 2024)

The influence of various doses of Moringa oleifera extract on the antioxidant trait, cytokines, reproductive hormones performance, and gonadal histological profiles of Nile tilapia - Fatma Abdel-monem Gad; Mahamoud Abdelghaffar Emam; Ramy M. Shourbela; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Heba H. Mahboub; Hiam Elabd (Aquaculture International, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Oxylipin Receptors and Their Role in Inter‐Partner Signalling in a Model Cnidarian‐Dinoflagellate Symbiosis - Andrea G. Gamba; Clinton A. Oakley; Immy A. Ashley; Arthur R. Grossman; Virginia M. Weis; David J. Suggett; Simon K. Davy (Environmental Microbiology, 2024)
Oxylipin signalling is central in biology, mediating processes such as cellular homeostasis, inflammation and molecular signalling. It may also facilitate inter‐partner communication in the cnidarian‐dinoflagellate symbiosis, though this aspect remains understudied. In this study, four oxylipin receptors were characterised using immunohistochemistry and immunoblotting in the sea anemone Exaiptasia diaphana (‘Aiptasia’): Prostaglandin E2 receptor 2 (EP2) and 4 (EP4), Transient Receptor Potential cation channel A1 (TRPA1) and Glutamate Receptor Ionotropic, Kainate 2 (GRIK2). Receptor abundance and localisation were compared between aposymbiotic anemones and symbiotic anemones hosting either native Breviolum minutum or non‐native Durusdinium trenchii . All receptors were localised to the putative symbiosome of freshly isolated symbionts, suggesting a role in host‐symbiont crosstalk. EP2, EP4 and TRPA1 abundance decreased in the gastrodermis of anemones hosting B . minutum , indicating potential downregulation of pathways mediated by these receptors. In contrast, GRIK2 abundance increased in anemones hosting D . trenchii in both the epidermis and gastrodermis; GRIK2 acts as a chemosensor of potential pathogens in other systems and could play a similar role here given D . trenchii 's reputation as a sub‐optimal partner for Aiptasia. This study contributes to the understanding of oxylipin signalling in the cnidarian‐dinoflagellate symbiosis and supports further exploration of host‐symbiont molecular signalling.

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Interconnectivity can be as important as habitat type in explaining carbon stocks in the coastal lagoons of arid regions - Stephen Carpenter; Kostantinos A. Stamoulis; Daniel Mateos-Molina; Simon J. Pittman; Marina Antonopoulou; Himansu S. Das; Claire Evans (Science of The Total Environment, 2024)

Restorative function of offshore longline mussel farms with ecological benefits for commercial crustacean species - Thomas Stamp; Simon J. Pittman; Luke A. Holmes; Adam Rees; Benjamin J. Ciotti; Harry Thatcher; Peter Davies; Alice Hall; Georgia Wells; Anna Olczak; Emma V. Sheehan (Science of The Total Environment, 2024)

Increasing oil content in Brassica oilseed species - Randall J. Weselake; David A. Fell; Xiaoyu Wang; Simon Scofield; Guanqun Chen; John L. Harwood (Progress in Lipid Research, 2024)

Climate vulnerability of Nothofagus pumilio, Nothofagus dombeyi and Austrocedrus chilensis in northern Patagonia’s temperate forests - Ernesto J. Reiter; Robert Weigel; Helge Walentowski; Gabriel A. Loguercio; Jonas Fierke; Ariel F. Neri Winter; Alois Simon; Martyna M. Kotowska; Natalia Z. Joelson; Marina Caselli; Christoph Leuschner (Forest Ecology and Management, 2024)

The Current State of Biotransformation Science – Industry Survey of In Vitro and In Vivo Practices, Clinical Translation, and Future Trends - John P. Savaryn; Kevin Coe; Matthew A. Cerny; Kevin Colizza; Patricia Moliner; Lloyd King; Bin Ma; Jim Atherton; Adam Auclair; Mark T. Cancilla; Marsha Eno; Ulrik Jurva; et al. (Pharmaceutical Research, 2024)

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Intertidal seagrass extent from Sentinel-2 time-series show distinct trajectories in Western Europe - Bede Ffinian Rowe Davies; Simon Oiry; Philippe Rosa; Maria Laura Zoffoli; Ana I. Sousa; Oliver R. Thomas; Dan A. Smale; Melanie C. Austen; Lauren Biermann; Martin J. Attrill; Alejandro Roman; Gabriel Navarro; et al. (Remote Sensing of Environment, 2024)

Hexaflumuron insecticide exposure induces behavior alterations, hemato-biochemical disorders, antioxidant-immune dysfunction, and histopathological alterations in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Basma A. Elshafey; Simon J. Davies; Afaf N. Abdel Rahman (Veterinary Research Communications, 2024)

Modulating the growth, immune/antioxidant traits, immune-related genes, and resistance to Aeromonas veronii infection in Oreochromis niloticus reared under high stocking densities by dietary Lavandula angustifolia essential oil - Mohamed ElHady; Shimaa A. Amer; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Tarek Khamis; Ehab E. Nabawy; Simon J. Davies; Shaimaa A. A. Ahmed (Aquaculture International, 2024)

Toxicological insight of magnetite nanogel: neuro-ethological, hepato-renal, antioxidant, and histopathological traits in Clarias gariepinus - Samar Kamel; Shaimaa A. A. Ahmed; Asmaa Elsayyad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohamed Shaalan; Mohamed M. S. Gaballa; Heba H. Mahboub; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Zeinab Hassan (Aquaculture International, 2024)
Assessment of acute toxicity of magnetic nanogel (MNG) is crucial to conclude the safe applicable dose and to warrant its application in aquaculture. Therefore, the current study is a novel step to assess behavior, neuro-stress response, hepato-renal, oxidative, and histopathological variations produced by MNG’ acute toxicity in Clarias gariepinus . Two experiments were conducted: the first was a determination of the 96-h lethal concentration 50 (LC 50 ) of MNG in C. gariepinus . Meanwhile, the second was an assessment of the toxicological impacts of three different concentrations of MNG in C. gariepinus following a 10-day exposure period and a subsequent 10-day depuration trial. One hundred and eighty fish were allotted to four groups exposed to 0, 1/10, 1/8, or 1/5 96-h LC 50 of MNG. The outcomes exhibited that 96-h LC 50 of MNG for C. gariepinus was 44 mg/L. The subjected group to MNG induced a concentration-dependent elevation in the serum values of cortisol, alanine transaminase, aspartate transaminase, urea, and creatinine following MNG exposure. Marked elevation in the oxidative stress indicators (catalase (CAT), glutathione S-transferase activity (GST), and superoxide dismutase (SOD)) was also evident. Meanwhile, the value of the neurological biomarker, acetylcholinesterase (AChE), was markedly reduced in a concentration-dependent way. These biochemical changes were complemented by pathological alterations in the hepato-renal architecture. Interestingly, in response to the 10-day depuration period, most of the tested parameters were eliminated in C. gariepinus exposed to 1/10 of LC 50 . Conclusively, MNG can induce numerous adverse effects only at higher doses (1/5 and 1/8 of LC 50 ). Meanwhile, the lowest tested concentration of MNG (1/10 of LC 50 ) was safe for application in aquaculture practices with only mild disruptions in the bio-indices. In addition, a retrieval period of 10 days was sufficient to renovate these alterations only in fish exposed to the same concentration.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - Hani R. El Bizri; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Lauren Coad; Thais Queiroz Morcatty; Gabriel Favero Massocato; Arnaud L. J. Desbiez; João Vitor Campos‐Silva; Daniel Zani La Laina; José Maurício Barbanti Duarte; et al. (Conservation Biology, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km 2 . Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well‐managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

P19-28 Exposure data to cosmetic products of consumers presenting atopic dermatitis - M.P. Berrada Gomez; A. Bernard; P. Roch-Simon; H. Bondarenko; P.-J. Ferret (Toxicology Letters, 2024)

Genomic SNPs resolve the phylogeny of an ancient amphibian island radiation from the Seychelles - Miranda B. Sherlock; Jeffrey W. Streicher; David J. Gower; Simon T. Maddock; Ronald A. Nussbaum; Oommen V. Oommen; Ana Serra Silva; Julia J. Day; Mark Wilkinson (Molecular Phylogenetics and Evolution, 2024)

Rainfall variability and deciduous-evergreen coexistence in tropical forests - Andrew J. Muehleisen; Naomi B. Schwartz; Simon M. Stump; A. Carla Staver (Theoretical Ecology, 2024)

Every breath you take: High concentration of breathable microplastics in indoor environments - L. Maurizi; L. Simon-Sánchez; A. Vianello; A.H. Nielsen; J. Vollertsen (Chemosphere, 2024)

The significance of Paleoarchean granitoids from the Saglek Block, Labrador, Canada - Tanmay Keluskar; Monika A. Kusiak; Daniel J. Dunkley; Simon A. Wilde; Martin J. Whitehouse; Keewook Yi; Shinae Lee (Precambrian Research, 2024)

The alleviative effect of Bacillus subtilis-supplemented diet against Vibrio cholerae infection in Nile tilapia (Oreochromis niloticus) - Omnia A. Elewasy; Amira S. Elrafie; Neveen A. Rasheed; Sara H. Adli; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Rowida E. Ibrahim (Veterinary Research Communications, 2024)

The therapeutic role of Azadirachta indica leaves ethanolic extract against detrimental effects of Aeromonas veronii infection in Nile tilapia, Oreochromis niloticus - Hesham A. Khalifa; Esraa Sharawy; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Rowida E. Ibrahim; Shimaa A. Amer; Simon J. Davies; Azza M. A. Abo-Elmaaty (Fish Physiology and Biochemistry, 2024)

Effects of dietary Hyphaene thebaica powder on reproductive performance, physiological parameters, growth, and disease resistance in Clarias gariepinus - Alshimaa A. Khalil; Shimaa A. Amer; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

The performance of metabolomics-based prediction scores for mortality in older patients with solid tumors - Yara van Holstein; Simon P. Mooijaart; Mathijs van Oevelen; Floor J. van Deudekom; Dina Vojinovic; Daniele Bizzarri; Erik B. van den Akker; Raymond Noordam; Joris Deelen; Diana van Heemst; Nienke A. de Glas; Cynthia Holterhues; et al. (GeroScience, 2024)
Prognostic information is needed to balance benefits and risks of cancer treatment in older patients. Metabolomics-based scores were previously developed to predict 5- and 10-year mortality (MetaboHealth) and biological age (MetaboAge). This study aims to investigate the association of MetaboHealth and MetaboAge with 1-year mortality in older patients with solid tumors, and to study their predictive value for mortality in addition to established clinical predictors. This prospective cohort study included patients aged ≥ 70 years with a solid malignant tumor, who underwent blood sampling and a geriatric assessment before treatment initiation. The outcome was all-cause 1-year mortality. Of the 192 patients, the median age was 77 years. With each SD increase of MetaboHealth, patients had a 2.32 times increased risk of mortality (HR 2.32, 95% CI 1.59–3.39). With each year increase in MetaboAge, there was a 4% increased risk of mortality (HR 1.04, 1.01–1.07). MetaboHealth and MetaboAge showed an AUC of 0.66 (0.56–0.75) and 0.60 (0.51–0.68) for mortality prediction accuracy, respectively. The AUC of a predictive model containing age, primary tumor site, distant metastasis, comorbidity, and malnutrition was 0.76 (0.68–0.83). Addition of MetaboHealth increased AUC to 0.80 (0.74–0.87) ( p = 0.09) and AUC did not change with MetaboAge (0.76 (0.69–0.83) ( p = 0.89)). Higher MetaboHealth and MetaboAge scores were associated with 1-year mortality. The addition of MetaboHealth to established clinical predictors only marginally improved mortality prediction in this cohort with various types of tumors. MetaboHealth may potentially improve identification of older patients vulnerable for adverse events, but numbers were too small for definitive conclusions. The TENT study is retrospectively registered at the Netherlands Trial Register (NTR), trial number NL8107. Date of registration: 22–10-2019.

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Eoarchean low δ18O zircon indicates emergent land at 3.73 Ga - Piotr Król; Monika A. Kusiak; Martin J. Whitehouse; Daniel J. Dunkley; Simon A. Wilde (Precambrian Research, 2024)

Histopathological characterization and grading of chronic enterocolitis in Sulawesi crested macaques (Macaca nigra) - Yannick Van de Weyer; Mark R. Howard; Mark F. Stidworthy; Alberto R. Barbon; Julian Chantrey; Stamatios A. Tahas; Ethan Wrigglesworth; Lewis J. Rowden; Amanda Guthrie; Simon Spiro (Journal of Comparative Pathology, 2024)

Enhancing Assessments of Coastal Wetland Migration Potential with Sea-level Rise: Accounting for Uncertainty in Elevation Data, Tidal Data, and Future Water Levels - Nicholas M. Enwright; Michael J. Osland; Hana R. Thurman; Claire E. McHenry; William C. Vervaeke; Brett A. Patton; Davina L. Passeri; Jason M. Stoker; Richard H. Day; Bethanie M. Simons (Estuaries and Coasts, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Reflections on the life and work of Richard Abbott (1945–2024) - Mark A. Chapman; Simon J. Hiscock; Janis Antonovics; Spencer C. H. Barrett; Adrian C. Brennan; Jianquan Liu (Molecular Ecology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Using luminescence dating to constrain lake sediment records: A new age model for the 1.38 Ma lake Malawi drill core, Eastern Africa - Laura C. Streib; Simon J. Armitage; Christopher A. Scholz (Quaternary Science Reviews, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Recommendations for the safe use of direct oral anticoagulants in patients with cirrhosis based on a systematic review of pharmacokinetic, pharmacodynamic and safety data - Maaike M. E. Diesveld; Daniëlle W. M. Jacobs- Pijnenburg; Rianne A. Weersink; Ina Barzel; Joost P. H. Drenth; Ton Lisman; Herold J. Metselaar; Margje H. Monster-Simons; Midas B. Mulder; Eline Okel; Katja Taxis; Sander D. Borgsteede (European Journal of Clinical Pharmacology, 2024)

Oscillation rheology, calorimetry and computed tomography: A practical toolkit combination of qualification for real poly(ethylene terephthalate) waste - L. Simon-Stőger; A. Kovács; M. Szigeti; J. Bobek-Nagy; R. Kurdi; Cs. Varga (Journal of Cleaner Production, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Artichoke (Cynara scolymus) leaf extract abates the neurotoxic and neurobehavioral outcomes of fluoride in Nile tilapia (Oreochromis niloticus) via balancing oxidative stress, inflammation, apoptosis, and acetylcholinesterase activity - Asmaa Elsayyad; Yasmin A. Reyad; Basma A. Elshafey; Enas K. Aziz; Mohamed M.M. Metwally; Yasmina M. Abd-Elhakim; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Simon J. Davies; Walaa El-Houseiny; Ahmed H. Arisha; Hanan A. Ghetas (Aquaculture, 2024)

Effect of early peptide diets on European sea bass (Dicentrarchus labrax) skeletal development - A. Printzi; S. Jodet; V. Fournier; S. Collet; L. Madec; V. Simon; J.-L. Zambonino-Infante; G. Koumoundouros; D. Mazurais (Aquaculture, 2024)

Retracted: The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological / immunohistochemical investigation of gills - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2024)

When will the Glomerular Filtration Rate in Former Preterm Neonates Catch up with Their Term Peers? - Yunjiao Wu; Karel Allegaert; Robert B. Flint; Sebastiaan C. Goulooze; Pyry A. J. Välitalo; Matthijs de Hoog; Hussain Mulla; Catherine M. T. Sherwin; Sinno H. P. Simons; Elke H. J. Krekels; Catherijne A. J. Knibbe; Swantje Völler (Pharmaceutical Research, 2024)
Aims Whether and when glomerular filtration rate (GFR) in preterms catches up with term peers is unknown. This study aims to develop a GFR maturation model for (pre)term-born individuals from birth to 18 years of age. Secondarily, the function is applied to data of different renally excreted drugs. Methods We combined published inulin clearance values and serum creatinine (Scr) concentrations in (pre)term born individuals throughout childhood. Inulin clearance was assumed to be equal to GFR, and Scr to reflect creatinine synthesis rate/GFR. We developed a GFR function consisting of GFR birth (GFR at birth), and an Emax model dependent on PNA (with GFR max , PNA 50 (PNA at which half of $${GFR}_{max}$$ GFR max is reached) and Hill coefficient). The final GFR model was applied to predict gentamicin, tobramycin and vancomycin concentrations. Result In the GFR model, GFR birth varied with birthweight linearly while in the PNA-based Emax equation, GA was the best covariate for PNA 50 , and current weight for GFR max . The final model showed that for a child born at 26 weeks GA, absolute GFR is 18%, 63%, 80%, 92% and 96% of the GFR of a child born at 40 weeks GA at 1 month, 6 months, 1 year, 3 years and 12 years, respectively. PopPK models with the GFR maturation equations predicted concentrations of renally cleared antibiotics across (pre)term-born neonates until 18 years well. Conclusions GFR of preterm individuals catches up with term peers at around three years of age, implying reduced dosages of renally cleared drugs should be considered below this age.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

The interior climate and its microclimatic variation of temperate forests in Northern Patagonia, Argentina - Alois Simon; Jonas Fierke; Ernesto J. Reiter; Gabriel A. Loguercio; Steffi Heinrichs; Birgitta Putzenlechner; Natalia Z. Joelson; Helge Walentowski (International Journal of Biometeorology, 2024)
Knowledge on mesoclimatic zonation and microclimatic variations within mountain forest ecosystems is crucial for understanding regional species turnover and effects of climate change on these systems. The temperate mountain forests in the Andean region of South America are among the largest and contiguous natural deciduous forest areas in the world. Due to their pronounced disturbance regime and different successional stages, a climatic zonation combined with the characterisation of its microclimatic variation is important to identify thresholds of species occurrences. We used micro-loggers to measure air temperature and relative humidity for one year at 40 measurement locations along longitudinal and elevation gradients in mountain forests in Northern Patagonia, Argentina. Our results unveil mesoclimatic patterns within these forests characterised by variations in temperature and vapour pressure deficit along the elevational gradient in general, but also at different times of the year. For example, Austrocedrus chilensis and Nothofagus dombeyi forests differed mainly by temperature and its diurnal range in the warmest months of the year. Also, differences between forest stands and gaps were more pronounced in the warmest months of the year and at lower elevations, with up to 2.5 K higher temperatures in the second half of the day in gaps. We found clear indications that shrubland of Nothofagus antarctica representing a successional stage after disturbances alters the mesoclimatic pattern, favouring forest fire ignition. Such mesoclimatic variations have a major influence on tree species turnover and ecological processes within these forest ecosystems. The findings contribute to our understanding of the complex interplay between topography, climate, and vegetation in shaping the spatial patterns of species occurrences.

Nano-selenium impacts on growth performance, digestive enzymes, antioxidant, immune resistance and histopathological scores of Nile tilapia, Oreochromis niloticus against Aspergillus flavus infection - El-Sayed Hemdan Eissa; Walaa K. Bazina; Yasmin M. Abd El-Aziz; Nadia A. Abd Elghany; Wesam A. Tawfik; Monga I. Mossa; Ola Hasan Abd El Megeed; Nadia N. B. Abd El-Hamed; Adel F. El-Saeed; Ehab El-Haroun; Simon J. Davies; Oliver J. Hasimuna; et al. (Aquaculture International, 2024)
The present study examined the impacts of varying amounts of selenium nanoparticles (Se-NPs) as a natural antioxidant and metabolic regulator on growth performance, antioxidant capacity, digestive enzymes and immune resistance of Oreochromis niloticus challenged to Aspergillus flavus infection. For 60 days, fish were fed the experimental diet of 30% crude protein up to apparent satiation three times a day. Se-NPs were added to the control diet at different levels of 0.0 (control), 0.5 (T1), 1.0 (T2) and 1.5 (T3) mg/kg diet to fed monosex Nile tilapia fingerlings with average initial weight (4.5 ± 0.5 g). Fish were randomly distributed in 12 tanks 100 L at a density of 20 fish per tank after 2-week acclimation to represent four treatments in triplicates. The results indicated that the growth indices, feed efficiency and survival rate were significantly enhanced ( P P Aspergillus flavus , a decreasing mortality rate was observed, which clearly shows that selenium nanoparticles boosted the fish’s immune response at T2. The intestinal morphology as villus length, villus width, muscular fibres layer thickness and absorption intestinal zone after challenged with A. flavus infection were considerably enhanced ( P P

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Fractionation and characterisation of pectin-rich extracts from garlic biomass - Piyachat Sunanta; Sarana Rose Sommano; Cara A. Luiten; Mahdieh Ghofrani; Ian M. Sims; Tracey J. Bell; Susan M. Carnachan; Simon F.R. Hinkley; Vassilis Kontogiorgos (Food Chemistry, 2024)

Denitrification, anammox, and DNRA in oligotrophic continental shelf sediments - Henry L. S. Cheung; Jenny R. Hillman; Conrad A. Pilditch; Candida Savage; Isaac R. Santos; Ronnie N. Glud; Francisco J. A. Nascimento; Simon F. Thrush; Stefano Bonaglia (Limnology and Oceanography, 2024)
Continental shelf sediments are considered hotspots for nitrogen (N) removal. While most investigations have quantified denitrification in shelves receiving large amounts of anthropogenic nutrient supply, we lack insight into the key drivers of N removal on oligotrophic shelves. Here, we measured rates of N removal through denitrification and anammox by the revised‐isotope pairing technique (r‐IPT) along the Northeastern New Zealand shelf. Denitrification dominated total N 2 production at depths between 30 and 128 m with average rates (± SE) ranging from 65 ± 28 to 284 ± 72 μ mol N m −2 d −1 . N 2 production by anammox ranged from 3 ± 1 to 28 ± 11 μ mol N m −2 d −1 and accounted for 2–19% of total N 2 production. DNRA was negligible in these oligotrophic settings. Parallel microbial community analysis showed that both Proteobacteria and Planctomycetota were key taxa driving denitrification. Denitrification displayed a negative correlation with oxygen penetration depth, and a positive correlation with macrofauna abundance. Our denitrification rates were comparable to oligotrophic shelves from the Arctic, but were lower than those from nutrient‐rich Pacific and Atlantic shelves. Based on our results and existing IPT measurements, the global shelf denitrification rate was reassessed to be 53.5 ± 8.1 Tg N yr −1 , equivalent to 20 ± 2% of marine N removal. We suggest that previous estimates of global shelf N loss might have been overestimated due to sampling bias toward areas with high N loads in the Northern Hemisphere.

Experiences of emotional eating in an Acceptance and Commitment Therapy based weight management intervention (SWiM): A qualitative study - Laura Kudlek; Rebecca A. Jones; Carly Hughes; Robbie Duschinsky; Andrew Hill; Rebecca Richards; Megan Thompson; Ann Vincent; Simon J. Griffin; Amy L. Ahern (Appetite, 2024)

Unravelling multiple thermotectonic events accommodated by the Highland Boundary Fault: Insights from K–Ar dating - Lucy McKay; Simon J. Kemp; Graham A. Leslie; Andrew Todd; Zoe K. Shipton; Rebecca J. Lunn; John Booth (Journal of Structural Geology, 2024)

Stream ecosystem puzzle: understanding how water column and sediment variables shape macroinvertebrate patterns in some Afrotropical streams - Simon Action; Francis O. Arimoro; Fulbert A. G. J. Assie; Diana Nantege; Gilbert Ndatimana; Unique N. Keke (Environmental Monitoring and Assessment, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Use of moringa protein hydrolysate as a fishmeal replacer in diet of Oreochromis niloticus: Effects on growth, digestive enzymes, protein transporters and immune status - Shimaa A. Amer; Afaf N. Abdel Rahman; Mohamed ElHady; Ali Osman; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Amr A. Moustafa; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2024)

The anti-bacterial efficacy of zinc oxide nanoparticles synthesized by Nelumbo nucifera leaves against Clostridium perfringes challenge in Oreochromis niloticus - Rowida E. Ibrahim; Moustafa M.S. Fouda; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Gamal A. Salem; Ahmed Asaid Elkady; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture, 2024)

Feeding and biological differences induce wide variation in legacy persistent organic pollutant concentrations among toothed whales and polar bear in the Arctic - Adam F. Pedersen; Rune Dietz; Christian Sonne; Robert J. Letcher; Anna M. Roos; Malene Simon; Aqqalu Rosing-Asvid; Steven H. Ferguson; Melissa A. McKinney (Science of The Total Environment, 2024)

The immunosuppressive, growth-hindering, hepatotoxic, and oxidative stress and immune related-gene expressions-altering effects of gibberellic acid in Oreochromis niloticus: A mitigation trial using alpha-lipoic acid - Walaa El-Houseiny; Ahmed H. Arisha; Amany Behairy; Mohamed M.M. Metwally; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Simon J. Davies; Bayan A. Hassan; Yasmina M. Abd-Elhakim (Pesticide Biochemistry and Physiology, 2024)

Nelumbo nucifera synthesized selenium nanoparticles modulate the immune-antioxidants, biochemical indices, and pro/anti-inflammatory cytokines pathways in Oreochromis niloticus infected with Aeromonas veronii - Rowida E. Ibrahim; Gehad Elshobaky; Mohamed ElHady; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nasreddin R. Rhouma; Suzan K. Murad; Engy Mohamed Mohamed Yassin; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Demographic mechanisms and anthropogenic drivers of contrasting population dynamics of hummingbirds - Simon G. English; Scott Wilson; Qing Zhao; Christine A. Bishop; Alison J. Moran (Biological Conservation, 2024)

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Tagging of Atlantic bluefin tuna off Ireland reveals use of distinct oceanographic hotspots - Camille M.L.S. Pagniello; Niall Ó Maoiléidigh; Hugo Maxwell; Michael R. Castleton; Emilius A. Aalto; Jonathan J. Dale; Robert J. Schallert; Michael J.W. Stokesbury; Ronán Cosgrove; Simon Dedman; Alan Drumm; Ross O'Neill; et al. (Progress in Oceanography, 2023)

Aquaculture governance: five engagement arenas for sustainability transformation - Stefan Partelow; Furqan Asif; Christophe Béné; Simon Bush; Aisa O Manlosa; Ben Nagel; Achim Schlüter; Vishnumurthy M Chadag; Afrina Choudhury; Steven M Cole; Richard S Cottrell; Stefan Gelcich; et al. (Current Opinion in Environmental Sustainability, 2023)

Potential role of dietary Boswellia serrata resin against mancozeb fungicide-induced immune-antioxidant suppression, histopathological alterations, and genotoxicity in Nile tilapia, Oreochromis niloticus - Afaf N. Abdel Rahman; Dalia E. Altohamy; Gehad E. Elshopakey; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nora M. Elseddawy; Aya Elgamal; Shefaa M. Bazeed; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquatic Toxicology, 2023)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Multi-habitat carbon stock assessments to inform nature-based solutions for coastal seascapes in arid regions - Stephen Carpenter; Claire Evans; Simon J. Pittman; Marina Antonopoulou; Ivonne Bejarano; Himansu S. Das; Mona Möller; Kate Peel; Fatin Samara; Kostantinos A. Stamoulis; Daniel Mateos-Molina (Frontiers in Marine Science, 2023)
Coastal ecosystems are integral to global carbon cycling and are increasingly recognised for their role in mitigating climate change. Within these ecosystems, the dynamics of carbon storage are diverse, varying significantly across different habitats. However, existing management strategies often focus predominantly on vegetated habitats neglecting the contributions of non-vegetated areas. We address this knowledge gap by providing a quantitative spatial assessment of carbon storage across coastal seascapes varying in plant biomass. Our comprehensive multi-habitat inventory of carbon stocks in the United Arab Emirates confirmed that mangroves are the largest carbon-storing habitat per hectare (94.3 t/ha), followed by saltmarshes (63.6 t/ha), microbial mats (51.6 t/ha), mudflats (46.8 t/ha), seagrass (32.5 t/ha), and coastal sabkha (31.0 t/ha).Mean carbon content in the top 50 cm of mangrove soils (53.9 t/ha) was similar to saltmarshes (52.7 t/ha), microbial mats (51.6 t/ha), and mudflats (46.8 t/ha). We highlight the importance of including non-vegetated habitats in carbon accounting and management strategies. Our findings suggest that a more context-specific whole-system approach is essential for guiding effective ecosystem management and designing ecologically meaningful Nature-based Solutions (NbS). Adopting this broader perspective in NbS can ensure more comprehensive conservation and restoration outcomes, which not only protect and enhance blue carbon ecosystems but also contribute to broader ecological and social benefits. This approach is pivotal for advancing our understanding of interconnected coastal ecosystems and their role in climate change mitigation.

Northerly range expansion and first confirmed records of the smalltooth sand tiger shark, Odontaspis ferox , in the United Kingdom and Ireland - David J. Curnick; Rob Deaville; Jenny R. Bortoluzzi; Luke Cameron; Jeanette E. L. Carlsson; Jens Carlsson; Haley R. Dolton; Cat A. Gordon; Phil Hosegood; Alicia Nilsson; Matthew W. Perkins; Kevin J. Purves; et al. (Journal of Fish Biology, 2023)
Three Odontaspis ferox (confirmed by mtDNA barcoding) were found in the English Channel and Celtic Sea in 2023 at Lepe, UK (50.7846, −1.3508), Kilmore Quay, Ireland (52.1714, −6.5937), and Lyme Bay, UK (50.6448, −2.9302). These are the first records of O. ferox in either country, and extend the species' range by over three degrees of latitude, to >52° N. They were ~275 (female), 433 (female), and 293 cm (male) total length, respectively. These continue a series of new records, possibly indicative of a climate change−induced shift in the species' range.

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Resource selection by New York City deer reveals the effective interface between wildlife, zoonotic hazards and humans - Meredith C. VanAcker; Vickie L. DeNicola; Anthony J. DeNicola; Sarah Grimké Aucoin; Richard Simon; Katrina L. Toal; Maria A. Diuk‐Wasser; Francesca Cagnacci (Ecology Letters, 2023)
Although the role of host movement in shaping infectious disease dynamics is widely acknowledged, methodological separation between animal movement and disease ecology has prevented researchers from leveraging empirical insights from movement data to advance landscape scale understanding of infectious disease risk. To address this knowledge gap, we examine how movement behaviour and resource utilization by white‐tailed deer ( Odocoileus virginianus ) determines blacklegged tick ( Ixodes scapularis ) distribution, which depend on deer for dispersal in a highly fragmented New York City borough. Multi‐scale hierarchical resource selection analysis and movement modelling provide insight into how deer's movements contribute to the risk landscape for human exposure to the Lyme disease vector– I. scapularis . We find deer select highly vegetated and accessible residential properties which support blacklegged tick survival. We conclude the distribution of tick‐borne disease risk results from the individual resource selection by deer across spatial scales in response to habitat fragmentation and anthropogenic disturbances.

Alpha-lipoic acid suppresses gibberellic acid nephrotoxicity in Nile tilapia (Oreochromis niloticus) via modulating oxidative stress, inflammation, cytokine production, and apoptosis - Walaa El-Houseiny; Ahmed H. Arisha; Mohamed M.M. Metwally; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Simon J. Davies; Bayan A. Hassan; Yasmina M. Abd-Elhakim (Pesticide Biochemistry and Physiology, 2023)

Effect of urbanization and parasitism on the gut microbiota of Darwin's finch nestlings - Gabrielle Solomon; Ashley C. Love; Grace J. Vaziri; Johanna Harvey; Taylor Verrett; Kiley Chernicky; Shelby Simons; Lauren Albert; Jaime A. Chaves; Sarah A. Knutie (Molecular Ecology, 2023)
Host‐associated microbiota can be affected by factors related to environmental change, such as urbanization and invasive species. For example, urban areas often affect food availability for animals, which can change their gut microbiota. Invasive parasites can also influence microbiota through competition or indirectly through a change in the host immune response. These interacting factors can have complex effects on host fitness, but few studies have disentangled the relationship between urbanization and parasitism on an organism's gut microbiota. To address this gap in knowledge, we investigated the effects of urbanization and parasitism by the invasive avian vampire fly ( Philornis downsi ) on the gut microbiota of nestling small ground finches ( Geospiza fuliginosa ) on San Cristóbal Island, Galápagos. We conducted a factorial study in which we experimentally manipulated parasite presence in an urban and nonurban area. Faeces were then collected from nestlings to characterize the gut microbiota (i.e. bacterial diversity and community composition). Although we did not find an interactive effect of urbanization and parasitism on the microbiota, we did find main effects of each variable. We found that urban nestlings had lower bacterial diversity and different relative abundances of taxa compared to nonurban nestlings, which could be mediated by introduction of the microbiota of the food items or changes in host physiology. Additionally, parasitized nestlings had lower bacterial richness than nonparasitized nestlings, which could be mediated by a change in the immune system. Overall, this study advances our understanding of the complex effects of anthropogenic stressors on the gut microbiota of birds.

Kidney bean protein hydrolysate as a fish meal replacer: Effects on growth, digestive enzymes, metabolic functions, immune-antioxidant parameters and their related gene expression, intestinal and muscular gene expression - Rowida E. Ibrahim; Samar A. Tolba; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Shimaa I. Shalaby; Ali Osman; Tarek Khamis; Mohamed A. Eissa; Simon J. Davies; Shimaa A. Amer (Aquaculture, 2023)

Experiences of emotional eating during an acceptance and commitment therapy based intervention to support weight loss maintenance (SWiM): A qualitative study - Laura Kudlek; Rebecca A. Jones; Carly Hughes; Robbie Duschinsky; Andrew Hill; Rebecca Richards; Simon J. Griffin; Amy Ahern (Appetite, 2023)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Call type repertoire of killer whales ( Orcinus orca ) in Iceland and its variation across regions - Anna Selbmann; Volker B. Deecke; Olga A. Filatova; Ivan D. Fedutin; Patrick J. O. Miller; Malene Simon; Ann E. Bowles; Thomas Lyrholm; Claire Lacey; Edda E. Magnúsdóttir; William Maunder; Paul J. Wensveen; et al. (Marine Mammal Science, 2023)
Killer whales ( Orcinus orca ) have group‐specific call repertoires that can be used to track groups and populations using passive acoustic monitoring. To provide a detailed description of the Icelandic killer whale repertoire and its variation, we analyzed acoustic data collected in five locations between 1985 and 2016. Calls were classified manually, and CART and random forest analyses were employed to validate the manual classification. A total of 91 call categories (including call types and subtypes) were defined. Most call categories were recorded in more than one location, with the highest proportion shared between herring grounds in Vestmannaeyjar (South) and Breiðafjörður (West). However, both locations included call categories that were not recorded elsewhere in Iceland. Recordings from past herring wintering grounds in eastern Iceland included few call categories that matched other locations. Sample sizes from Reykjanes (Southwest) and Skjálfandi (North) were small and did not include unique call categories. The relative occurrence of call categories in Vestmannaeyjar changed little over a 14‐year period (2002–2016), although shorter‐term changes between years were observed that appeared to correlate to changes in individuals identified. This comparison of acoustic repertoires provides valuable information on the social structure and movement patterns of herring‐eating killer whales around Iceland.

P25-06: Exposure data of makeup products for patients undergoing cancer treatments - P. Roch-Simon; A. Bernard; J. Nonni; C. Guevara; M.-P. Berrada-Gomez; P.-J. Ferret (Toxicology Letters, 2023)

P20-01: First certified reference materials (CRMs) to improve the reliability of biological toxins detection, identification and quantification - R. Zeleny; K. Busschots; B. Kampa; S. Worbs; M. Skiba; B. Dorner; T. Van Nieuwenhuysen; A. Puustinen; P. Vanninen; C. Rasetti-Escargueil; M.-A. Nahori; E. Lemichez; et al. (Toxicology Letters, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

How greenhouse horticulture in arid regions can contribute to climate-resilient and sustainable food security - Simon Goddek; Oliver Körner; Karel J. Keesman; Mark A. Tester; Ryan Lefers; Luuk Fleskens; Alyssa Joyce; Erik van Os; Amit Gross; Rik Leemans (Global Food Security, 2023)

Maturation of Paracetamol Elimination Routes in Preterm Neonates Born Below 32 Weeks of Gestation - Yunjiao Wu; Swantje Völler; Elke H. J. Krekels; Daniëlla W. E. Roofthooft; Sinno H. P. Simons; Dick Tibboel; Robert B. Flint; Catherijne A. J. Knibbe (Pharmaceutical Research, 2023)
Purpose Despite being off-label, intravenous paracetamol (PCM) is increasingly used to control mild-to-moderate pain in preterm neonates. Here we aim to quantify the maturation of paracetamol elimination pathways in preterm neonates born below 32 weeks of gestation. Methods Datasets after single dose (rich data) or multiple doses (sparse data) of intravenous PCM dose (median (range)) 9 (3–25) mg/kg were pooled, containing 534 plasma and 44 urine samples of PCM and metabolites (PCM–glucuronide, PCM–sulfate, PCM–cysteine, and PCM–mercapturate) from 143 preterm neonates (gestational age 27.7 (24.0–31.9) weeks, birthweight 985 (462–1,925) g, postnatal age (PNA) 5 (0–30) days, current weight 1,012 (462–1,959) g. Population pharmacokinetic analysis was performed using NONMEM® 7.4. Results For a typical preterm neonate (birthweight 985 g; PNA 5 days), PCM clearance was 0.137 L/h, with glucuronidation, sulfation, oxidation and unchanged renal clearance accounting for 5.3%, 73.7%, 16.3% and 4.6%, respectively. Maturational changes in total PCM clearance and its elimination pathways were best described by birthweight and PNA. Between 500–1,500 g birthweight, total PCM clearance increases by 169%, with glucuronidation, sulfation and oxidation clearance increasing by 347%, 164% and 164%. From 1–30 days PNA for 985 g birthweight neonate, total PCM clearance increases by 167%, with clearance via glucuronidation and oxidation increasing by 551%, and sulfation by 69%. Conclusion Birthweight and PNA are the most important predictors for maturational changes in paracetamol clearance and its glucuronidation, sulfation and oxidation. As a result, dosing based on bodyweight alone will not lead to consistent paracetamol concentrations among preterm neonates.

Mineral nutrition in penaeid shrimp - Ha H. Truong; Barney M. Hines; Maurício G. Emerenciano; David Blyth; Sarah Berry; Tansyn H. Noble; Nicholas A. Bourne; Nicholas Wade; Artur N. Rombenso; Cedric J. Simon (Reviews in Aquaculture, 2023)
This review summarises the current knowledge of mineral nutrition for penaeid shrimp. It investigates how the aquatic environment and the lifecycle of shrimp affect requirements and the role that minerals play in shrimp health. Methods of supplying minerals via either water or to feed, and novel ways of supplementing minerals within feed, are discussed. The requirements for individual minerals are summarised with recommendations for minimum levels of dietary inclusion for semi‐intensive and intensive commercial shrimp culture presented where data permits. Estimates of dietary requirement remain broad for most minerals for the main shrimp production species ( Penaeus vannamei , Penaeus monodon and Penaeus japonicus ), with some essential minerals remaining unstudied (Table 2 in Section 5.10). Mineral nutrition will become more important as intensification and diversification of production systems provide new challenges to shrimp aquaculture.

Neem seed protein hydrolysate as a fishmeal substitute in Nile tilapia: Effects on antioxidant/immune pathway, growth, amino acid transporters-related gene expression, and Aeromonas veronii resistance - Afaf N. Abdel Rahman; Shimaa A. Amer; Shimaa R. Masoud; Mahmoud M. El-Saber; Ali Osman; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Tarek Khamis; Rowida E. Ibrahim (Aquaculture, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Trouble in the tropics: Pathogen spillover is a threat for native stingless bees - Fernando A. Fleites-Ayil; Luis A. Medina-Medina; José Javier G. Quezada Euán; Eckart Stolle; Panagiotis Theodorou; Simon Tragust; Robert J. Paxton (Biological Conservation, 2023)

Acute mancozeb-fungicide exposure induces neuro-ethology disruption, health disorders, and immune-oxidative dysfunction in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Mohamed A. Elbealy; Gamal A. Salem; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Ahmed Asaid Elkady; Simon J. Davies; Afaf N. Abdel Rahman (Aquatic Toxicology, 2023)

Melatonin Influences Terpenoid Indole Alkaloids Biosynthesis and 5′ Upstream-Mediated Regulation of Cell wall Invertase in Catharanthus roseus - S. A. Sheshadri; M. J. Nishanth; Bindu Simon (Journal of Plant Growth Regulation, 2023)

When and where are livestock climate-smart? A spatial-temporal framework for comparing the climate change and food security synergies and tradeoffs of Sub-Saharan African livestock systems - Leah A. Germer; Corina E. van Middelaar; Simon J. Oosting; Pierre J. Gerber (Agricultural Systems, 2023)

Bacterial Co-Infection as a Potential Threat to Farmed Flathead Grey Mullet (Mugil cephalus): Phenotypic and Molecular Diagnosis, Histopathology, Immunity Response, and In Vitro Antibacterial Evaluation - Samia Elbahnaswy; Gehad E. Elshopakey; Medhat S. Shakweer; Elsayed A. A. Eldessouki; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Simon J. Davies; Mai A. M. El-Son (Fishes, 2023)
Vibrio alginolyticus, Vibrio chlorea, and Enterococcus cloacae were the main bacterial pathogens investigated during recurrent episodes of mortalities among farmed flathead grey mullet (Mugil cephalus) in the Bahar El-Baqar area, Sharqia governorate, Egypt, during the summer season in 2021. Nevertheless, the contamination of water with heavy metals was evaluated. In this study, a total number of sixty moribund and freshly dead Mugil cephalus were examined clinically and upon post-mortem. Then, the bacterial isolates were subjected to bacteriological phenotypic examination, 16S rRNA gene sequencing, and antibiotic sensitivity testing. Histopathological screening and the immunity response of naturally infected M. cephalus were also implemented. In areas where bacterial strains were recovered in a high percentage, water contamination with Cu, Fe, and Ni was higher than the permissible limit. The results showed a high similarity (99–100%) to Vibrio and E. cloacae strains using phylogenetic analysis of 16S rRNA. Most isolates exhibited sensitivity to florfenicol, ciprofloxacin, and norfloxacin, while they were resistant to erythromycin and amoxicillin. Hemorrhage, oedema, hemosiderosis, and melanomacrophage activation in most affected tissues of infected M. cephalus were detected by light microscopy. Nevertheless, higher levels of AST and ALT, as well as serum inflammatory markers, CRP, and lysozyme activity, were shown in infected fish. There were higher MDA levels, along with a reduction of GSH, SOD, and catalase, in the gills and brain of infected M. cephalus, compared to the control fish. Our obtained data confirmed the high prevalence of Vibrio serovars and E. cloacae in infected grey mullets, describing their histopathological alterations, higher inflammatory response, and oxidative stress impact. These results could be useful indicators for understanding the pathogenesis of these pathogens in correlation with water parameter deterioration. Thus, the emergence of Vibrio and E. cloacae species in this study threatens the brackish water aquaculture industry in Egypt and poses a public health concern.

Insights from an AIMBE Workshop: Diversifying Paths to Academic Leadership - Beth L. Pruitt; Naomi C. Chesler; Rena Seltzer; Omolola Eniola-Adefeso; Susan S. Margulies; Maritza Salazar Campo; Scott I. Simon; Michele J. Grimm; Sarah Mandell; Andrew Alleyne; Jennifer L. West; Tejal A. Desai (Biomedical Engineering Education, 2023)
The American Institute for Medical and Biological Engineering (AIMBE) hosted a virtual symposium titled “Diversifying Paths to Academic Leadership” on January 27 and 28, 2022. The symposium sought to educate the community on the opportunities for and impact of leadership by biomedical engineering faculty, to encourage and invite women faculty, especially women of color, to consider and prepare to pursue leadership roles, to educate faculty on the expectations and duties of these roles, and to highlight experiences and paths to leadership of women engineering leaders. Here we review the main outcomes of the symposium to provide perspective on (1) personal visioning and positioning for leadership, (2) negotiating for success in leadership positions, and (3) leadership strategies for success specific to women faculty and where applicable, faculty of color.

Millimetre‐scale pollen analysis of non‐varved lacustrine sediments from Onepoto maar palaeolake, Auckland, reveals distal vegetation responses and landscape recovery following the ~25.5‐ka Ōruanui supereruption, New Zealand - Stephen B. Piva; Simon J. Barker; Rewi M. Newnham; Andrew B. H. Rees; Colin J. N. Wilson; Lionel Carter; Nels A. Iverson; Benjamin Läuchli; Paul C. Augustinus (Journal of Quaternary Science, 2023)
The ~25.5‐ka Ōruanui supereruption (Taupō volcano, New Zealand) erupted >1100 km 3 of pyroclastic material during the Last Glacial Maximum. The impacts of this event on climate and the New Zealand environment remain unresolved, particularly on ecological timescales. Using sediment cores from Onepoto maar palaeolake, Auckland (~240 km upwind from source), we have analysed pollen assemblages at contiguous 1‐mm intervals, around an intact 3‐cm layer of the Kawakawa‐Ōruanui Tephra to resolve and assess post‐eruption vegetation impacts and landscape recovery. Sediments immediately above the tephra record a decline in the relative abundance of the dominant canopy species of Fuscospora , and concurrent increase in the abundances of grasses, herbs, ferns and shrubs. These changes reflect a brief (

Stable isotope ecology and interspecific dietary overlap among dolphins in the Northeast Atlantic - Tessa Plint; Mariel T.I. ten Doeschate; Andrew C. Brownlow; Nicholas J. Davison; Georg Hantke; Andrew C. Kitchener; Fred J. Longstaffe; Rona A. R. McGill; Cornelia Simon-Nutbrown; Clayton R. Magill (Frontiers in Marine Science, 2023)
Dolphins are mobile apex marine predators. Over the past three decades, warm-water adapted dolphin species (short-beaked common and striped) have expanded their ranges northward and become increasingly abundant in British waters. Meanwhile, cold-water adapted dolphins (white-beaked and Atlantic white-sided) abundance trends are decreasing, with evidence of the distribution of white-beaked dolphins shifting from southern to northern British waters. These trends are particularly evident in Scottish waters and ocean warming may be a contributing factor. This mobility increases the likelihood of interspecific dietary overlap for prey among dolphin species previously separated by latitude and thermal gradients. Foraging success is critical to both individual animal health and overall population resilience. However, the degree of dietary overlap and plasticity among these species in the Northeast Atlantic is unknown. Here, we characterise recent (2015-2021) interspecific isotopic niche and niche overlap among six small and medium-sized delphinid species co-occurring in Scottish waters, using skin stable isotope composition ( δ 13 C and δ 15 N), combined with stomach content records and prey δ 13 C and δ 15 N compiled from the literature. Cold-water adapted white-beaked dolphin have a smaller core isotopic niche and lower dietary plasticity than the generalist short-beaked common dolphin. Striped dolphin isotopic niche displayed no interspecific overlap, however short-beaked common dolphin isotopic niche overlapped with white-beaked dolphin by 30% and Atlantic white-sided dolphin by 7%. Increasing abundance of short-beaked common dolphin in British waters could create competition for cold-water adapted dolphin species as a significant portion of their diets comprise the same size Gadiformes and high energy density pelagic schooling fish. These priority prey species are also a valuable component of the local and global fishing industry. Competition for prey from both ecological and anthropogenic sources should be considered when assessing cumulative stressors acting on cold-water adapted dolphin populations with projected decline in available habitat as ocean temperatures continue to rise.

The Challenge of Global Aflatoxins Legislation with a Focus on Peanuts and Peanut Products: A Systematic Review - Julie P. Meneely; Oluwatobi Kolawole; Simon A. Haughey; Sarah J. Miller; Rudolf Krska; Christopher T. Elliott (Exposure and Health, 2023)
Globally, of all mycotoxins, aflatoxins present a significant threat to human and animal health and has resulted in the introduction of strict food regulatory limits to protect public health. A systematic review, was performed to elucidate the rationale applied in establishing aflatoxin standards and evaluate the economic impacts of these. The focus was peanuts, a principal trading commodity susceptible to aflatoxin contamination. Results revealed that although regulations are established in many countries, there is huge disparity in the maximum limits applied due to different methodologies used when considering exposure assessment. Moreover, in countries most affected by aflatoxin contamination in peanuts, few, if any standards exist. In the case of risk assessments, knowledge gaps identified include the impact of climate change on peanut aflatoxin contamination, the role of aflatoxins in child stunting, Kwashiorkor and immunomodulation and a lack of occurrence and exposure data in many developing countries from contaminated peanuts. Few quantitative studies evaluating the impact of aflatoxin regulations on trade exist and evidence is lacking in terms of what happens to exports that do not meet regulatory requirements. Evidence does suggest a lack of knowledge of the extent of the aflatoxin problem, associated health risks and mitigation strategies in developing countries. A hugely important factor that needs to be highlighted is that while there is a fundamental right for sufficient, safe, nutritious food, in many cases in low-income and lower middle-income countries there exists an incredibly difficult and complex trade-off between food security and food safety.

The role of irradiance in controlling coralline algal calcification - Erik C. Krieger; Wendy A. Nelson; Johan Grand; Eric C. Le Ru; Sarah J. Bury; Amelie Cossais; Simon K. Davy; Christopher E. Cornwall (Limnology and Oceanography, 2023)
Coralline algae are an essential element of benthic ecosystems throughout the ocean's photic zone. Yet, the role of light in shaping the physiology of coralline algae from cold‐water, low‐light habitats is poorly understood. Here, we assess the calcification physiology of five cool temperate coralline algae in response to different irradiance levels over 3 months. We show that in contrast to current models focused on warmer water species, previously observed enhancement of calcification rates by photosynthesis is largely limited to lower irradiances, and that the removal of CO 2 from the calcifying fluid is not the underlying mechanism of this enhancement. Instead, this most likely occurs via two processes: (1) increased ion pumping rates to elevate the calcium carbonate saturation state in the calcifying fluid; and (2) a higher daytime pH in the diffusion boundary layer that raises calcifying fluid pH. However, as irradiance increases, ion pumping becomes increasingly saturated limiting further enhancements. Our results also suggest the existence of two calcification strategies in coralline algae and indicate that magnesium incorporation is determined by the magnesium to calcium ratio in the calcifying fluid ([Mg] CF /[Ca] CF ). This study adds to our mechanistic understanding of calcification in coralline algae and fills in much needed knowledge about the role of light in controlling their physiology.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Assignment of tracks from tagged Atlantic bluefin tuna Thunnus thynnus to potential stocks using behavioural differences and habitat partitioning - Simon Dedman; Emilius A. Aalto; Michael J. W. Stokesbury; Robert J. Schallert; Michael R. Castleton; Barbara A. Block (Frontiers in Marine Science, 2023)
Introduction Atlantic bluefin tuna (ABT) are large, migratory pelagic predators of high economic importance. ABT are currently managed as two independent stocks assigned to discrete spawning areas (Gulf of Mexico, and Mediterranean); however, stock overlap outside spawning areas makes accurate assignment of catch to stock-of-origin difficult. Methods Within this two-stock paradigm, we characterised stock-specific spatial distributions and behaviours by comparing habitat usage and vertical movement behaviours of 118 electronically tagged adult ABT spatially assigned to the GOM and Med spawning grounds. These spatial and behavioural differences were used in tests to probabilistically assign unknown individuals (which did not visit the GOM/Med spawning areas) to a stock. Results This new methodological approach using existing tag data, enables increased assignment of a track to a potential stock, to be achieved before genetic assignments. We identified certain markedly different movement patterns, range extents, depth use preferences (and associated area usage), migration directness and speeds, corresponding distance from shore, and mesopelagic-layer visitation. The probabilistic assignment approach had 97% in-bag testing accuracy, then assigned 190 individuals to a stock, doubling the number of assigned stock-of-origin tracks in our dataset, and potentially revealing novel movement and behaviour patterns among pre-spawning-age ABT. Discussion This approach can be easily adapted to other study species, more stocks, and different testing variables, hopefully serving as a useful addition to the fisheries management toolkit.

Comparative Study on Ginger Powder and Ginger Extract Nanoparticles: Effects on Growth, Immune–Antioxidant Status, Tissue Histoarchitecture, and Resistance to Aeromonas hydrophila and Pseudomonas putida Infection in Oreochromis niloticus - Shaimaa A. A. Ahmed; Abdelhakeem El-Murr; Yasser Abd Elhakim; Mohamed M. Metwally; Amany Abd El Aziz Gharib; Shimaa A. Amer; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Simon J. Davies; Enas N. M. Khalil (Fishes, 2023)
A 10 week feeding trial was conducted to evaluate the potential effects of ginger powder (GP) and ginger extract nanoparticles (GNPs) on the growth parameters, digestive enzymes (lipase and amylase) activities, blood hematology, blood biochemical indices, immune indices (interleukin 10, immunoglobulin M, nitric oxide, and lysozymes), antioxidant activity, histological characteristics of kidney, spleen, liver, and intestine, and resistance to Aeromonas hydrophila or Pseudomonas putida infection in Nile tilapia, Oreochromis niloticus. Fish (n = 225, 27.01 ± 0.15 g) were stocked in 15 glass tanks (50 × 40 × 60 cm) and randomly allocated to five experimental treatments (TRTs) in triplicate (15 fish/replicate, 45 fish/TRT), consisting of five isocaloric–isonitrogenous diets. The treatments comprised the basal diet (1) without any additives (control group, CON), (2) with 0.5% GP (GP0.5), (3) with 1% GP (GP1), (4) with 0.5% GNPs (GNPs0.5), and (5) with 1% GNPs (GNPs1). Fish were manually fed to satiety three times a day (at 9 a.m., 12 p.m., and 2 p.m.). Fish were weighed at the start of the experiment, then the body weight, weight gain, feed intake, and feed conversion ratio were determined at the end of the experiment. At the end of the feeding period, 15 fish/TRT were intraperitoneally inoculated with two pathogenic bacterial strains (A. hydrophila or P. putida) in two separate challenge tests. Blood samples were collected from each TRT at two aliquots for hematological and biochemical analysis at the end of the feeding period. A significant improvement in fish growth was observed in GP and GNPs TRTs compared to the control group. There were no significant changes in the total amount of feed intake/fish in response to the experimental diets. Diets enriched with GNPs, particularly the GNPs1 TRT, resulted in a significant increase (p

Synthetic Microfiber Material Influences Ingestion by Freshwater Worms - Sarah A. Martinez; Conner J. Simon; Risa A. Cohen (Bulletin of Environmental Contamination and Toxicology, 2023)

The Anthropocene as an epoch is distinct from all other concepts known by this term: a reply to Swindles et al. (2023) - Martin J. Head; Colin N. Waters; Jan A. Zalasiewicz; Anthony D. Barnosky; Simon D. Turner; Alejandro Cearreta; Reinhold Leinfelder; Francine M.G. McCarthy; Daniel de B. Richter; Neil L. Rose; Yoshiki Saito; Davor Vidas; et al. (Journal of Quaternary Science, 2023)

Neritic larval fish assemblages across the Texas shelf in the northwestern Gulf of Mexico following Hurricane Harvey - Shannan McAskill; James M. Tolan; Glenn A. Zapfe; Simon J. Geist (Fisheries Oceanography, 2023)
Fall is an important time of year for fish recruitment in the Gulf of Mexico, with many commercially and recreationally important species spawning during this period. Changes in temperature and salinity regimes through seasonally abnormal freshwater input may change spawning patterns and displace larvae. Such an event occurred off the coast of Galveston Bay, Texas, when a freshwater flood plume formed from unprecedented rainfall related to Hurricane Harvey at the end of August 2017. This study investigated the effects of a large‐scale flood plume on larval fish assemblages, collected at nearshore and shelf zones 1 and 2 months after Hurricane Harvey. Samples from 2017 were compared to historical datasets collected by NOAA Fisheries in September (2000–2004 and 2006–2016) and October (2000–2012). Evidence of lowered water temperature and salinity was found in both September and October 2017. Larval community composition changed along cross‐shelf gradients and with increasing distance from shore. We also found evidence of 2017 assemblages differing from historical data, with the September 2017 assemblage more closely resembling those from October historical samples. Observed differences in 2017 assemblages were most likely explained by an earlier onset in fall sciaenid spawning, suggesting that decreases in water temperature occurring during hurricanes have the potential to alter fish spawning patterns.

Long‐term trajectories of non‐native vegetation on islands globally - Anna Walentowitz; Bernd Lenzner; Franz Essl; Nichola Strandberg; Alvaro Castilla‐Beltrán; José María Fernández‐Palacios; Svante Björck; Simon Connor; Simon G. Haberle; Karl Ljung; Matiu Prebble; Janet M. Wilmshurst; et al. (Ecology Letters, 2023)
Human‐mediated changes in island vegetation are, among others, largely caused by the introduction and establishment of non‐native species. However, data on past changes in non‐native plant species abundance that predate historical documentation and censuses are scarce. Islands are among the few places where we can track human arrival in natural systems allowing us to reveal changes in vegetation dynamics with the arrival of non‐native species. We matched fossil pollen data with botanical status information (native, non‐native), and quantified the timing, trajectories and magnitude of non‐native plant vegetational change on 29 islands over the past 5000 years. We recorded a proportional increase in pollen of non‐native plant taxa within the last 1000 years. Individual island trajectories are context‐dependent and linked to island settlement histories. Our data show that non‐native plant introductions have a longer and more dynamic history than is generally recognized, with critical implications for biodiversity baselines and invasion biology.

Impact of Streptococcus agalactiae Challenge on Immune Response, Antioxidant Status and Hepatorenal Indices of Nile Tilapia: The Palliative Role of Chitosan White Poplar Nanocapsule - Afaf N. Abdel Rahman; Sameh H. Ismail; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samah S. Khalil; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Simon J. Davies; Rowida E. Ibrahim (Fishes, 2023)
A new insight into the synthesis of the herbal plant (White poplar, Poplus alba) leave extract using chitosan nanocapsule was studied. The in vitro antibacterial activity of chitosan white poplar nanocapsule (CWPNC) against Streptococcus agalactiae (S. agalactiae) was determined. About 120 fish were categorized for 7 days into four groups. The first and second (CWPNC) groups were treated with 0 mg/L and 3 mg/L CWPNC in the water, respectively, without being challenged; the first group was a control. The third (S. agalactiae) and fourth (CWPNC + S. agalactiae) groups were treated with 0 and 3 mg/L CWPNC, respectively, and challenged with S. agalactiae (0.5 × 107 CFU/mL). The obtained results revealed that CWPNC had an in vitro antibacterial activity against S. agalactiae. Moreover, S. agalactiae infection caused a significant elevation (p

Circadian rhythm of preferred temperature in fish: Behavioural thermoregulation linked to daily photocycles in zebrafish and Nile tilapia - Luisa M. Vera; Gonzalo de Alba; Silvere Santos; Tim M. Szewczyk; Simon A. Mackenzie; Francisco J. Sánchez-Vázquez; Sònia Rey Planellas (Journal of Thermal Biology, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Pre-eruptive rhyolite magma ascent rate is rapid and independent of eruption size: a case study from Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Madison L. Myers; Alexander R. L. Nichols; Paul J. Wallace; Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier (Bulletin of Volcanology, 2023)
Volatile measurements in mineral-hosted sealed melt inclusions, and open-ended embayments, have previously been used to study magma ascent dynamics in large rhyolitic eruptions. However, despite occurring more frequently, smaller-volume explosive events remain under-studied. We present magmatic volatile data from quartz-hosted melt inclusions and embayments for eight post-25.4 ka rhyolitic eruptions at Ōkataina Volcanic Centre, Aotearoa New Zealand. Seven originated from within the main caldera, and the other erupted from the associated Ōkareka Structural Embayment. Melt inclusions preserve volatile contents of 2.92–5.82 wt% H 2 O and 13–126 ppm CO 2 , indicating pre-eruptive storage depths of 4.5–7.4 km, with younger eruptions being more shallow. The lack of correlation between H 2 O, CO 2 , inclusion size or distance to the crystal rim suggests magma bodies experienced variable degrees of degassing during magma storage, with some amount of post-entrapment volatile modification prior to and concurrent with final magma ascent. Diffusion modelling of measured H 2 O gradients in melt embayments indicates ascent rates of 0.10–1.67 m.s −1 over time spans of 20–230 min for the intra-caldera events. In contrast, ascent rates for the eruption from the Ōkareka Structural Embayment may be more rapid, at 1.59–4.4 m.s −1 over a time span of 22–34 min. Our findings imply that the final, pre-eruptive magma movement towards the surface could be less than a few hours. Comparisons with published data for caldera-forming explosive events reveal no clear relationships between final ascent rate, eruption size or initial volatile content, implying that other factors besides eruption volume control rhyolite magma ascent.

Response to Merritts et al. (2023): The Anthropocene is complex. Defining it is not - Colin N. Waters; Martin J. Head; Jan Zalasiewicz; Francine M.G. McCarthy; Scott L. Wing; Peter K. Haff; Mark Williams; Anthony D. Barnosky; Barbara Fiałkiewicz-Kozieł; Reinhold Leinfelder; J.R. McNeill; Neil L. Rose; et al. (Earth-Science Reviews, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Can Ingoing Contact Chains and other cattle movement network metrics help predict herd-level bovine tuberculosis in Irish cattle herds? - Jamie A. Tratalos; Helen R. Fielding; Jamie M. Madden; Miriam Casey; Simon J. More (Preventive Veterinary Medicine, 2023)

Petrogenesis of Meso-Neoarchean granitoids from the Chitradurga Greenstone Belt: Implications on crustal growth and reworking of the Dharwar Craton, southern India - M. Ram Mohan; Neal J. McNaughton; D. Srinivasa Sarma; M. Rajamanickam; Ian R. Fletcher; Simon A. Wilde; Birger Rasmussen; Bryan Krapež; S. Balakrishnan (Journal of Asian Earth Sciences, 2023)

Immunostimulatory effect of mannan-oligosaccharides supplementation diet in milkfish (Chanos chanos) - Ramasamy Harikrishnan; Gunapathy Devi; Paramaraj Balamurugan; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Hien Van Doan; Chellam Balasundaram; Simon J. Davies; Ehab El-Haroun (Fish & Shellfish Immunology, 2023)

Distribution of the reef manta ray Mobula alfredi and the oceanic manta ray Mobula birostris in the Philippines: a collaborative effort for conservation - Joshua Rambahiniarison; Ariana Agustines; Konstantinos Alexopoulos; Gonzalo Araujo; Asia O. Armstrong; Shannon Arnold; Aldrin Barruga; Titus Cañete; Segundo Conales; Kymry Delijero; Nonie P. Enolva; Anna L. Flam; et al. (Journal of Fish Biology, 2023)
Little is known about manta ray population size, structure and connectivity in the Philippines. In collaboration with dive operators, non‐governmental organizations and authorities, sightings of manta rays were collated into a single national database. Using in‐water photographs and videos gathered through citizen science and dedicated research efforts, this study compiled sightings between 2004 and 2020, showing 22 separate sites throughout the archipelago with manta rays present. A total of 392 individual reef manta rays ( Mobula alfredi ) and 107 oceanic manta rays ( Mobula birostris ) were identified from the collected footage. Four specific sites in the provinces of Masbate and Palawan together hosted 89% of all identified individuals and accounted for 95% of sightings, highlighting these areas are key aggregation sites. This study also reports the movements of M. birostris within the Philippines, based on photo‐identification of three individuals moving 150 km between Cebu and Masbate. Despite the growing number of recreational divers in Daanbantayan and San Jacinto, an 80% decline in M. birostris sightings was observed at these sites. To ensure effective future conservation, it is recommended that efforts focus on the identification and protection of manta ray hotspots and migratory corridors, the creation of a sustainable tourism framework and, most important, the implementation of mitigation strategies to reduce fisheries interactions.

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

Mass falls of crustacean carcasses link surface waters and the deep seafloor - Erik Simon‐Lledó; Brian J. Bett; Noëlie M. A. Benoist; Henk‐Jan Hoving; Dmitry Aleynik; Tammy Horton; Daniel O. B. Jones (Ecology, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Consequences of in vitro benzyl butyl phthalate exposure for blubber gene expression and insulin-induced Akt activation in juvenile grey seals - Alexandra Tranganida; Ailsa J. Hall; Holly C. Armstrong; Simon E.W. Moss; Kimberley A. Bennett (Environmental Pollution, 2023)

The influence of tDCS on perceived bouncing/streaming - Maximilian A. Friehs; Marlena J. Stegemann; Simon Merz; Christoph Geißler; Hauke S. Meyerhoff; Christian Frings (Experimental Brain Research, 2023)
Processing ambiguous situations is a constant challenge in everyday life and sensory input from different modalities needs to be integrated to form a coherent mental representation on the environment. The bouncing/streaming illusion can be studied to provide insights into the ambiguous perception and processing of multi-modal environments. In short, the likelihood of reporting bouncing rather than streaming impressions increases when a sound coincides with the moment of overlap between two moving disks. Neuroimaging studies revealed that the right posterior parietal cortex is crucial in cross-modal integration and is active during the bouncing/streaming illusion. Consequently, in the present study, we used transcranial direct current stimulation to stimulate this brain area. In the active stimulation conditions, a 9 cm 2 electrode was positioned over the P4-EEG position and the 35 cm 2 reference positioned over the left upper arm. The stimulation lasted 15 min. Each participant did the bouncing/streaming task three times: before, during and after anodal or sham stimulation. In a sample of N = 60 healthy, young adults, we found no influence of anodal tDCS. Bayesian analysis showed strong evidence against tDCS effects. There are two possible explanations for the finding that anodal tDCS over perceptual areas did not modulate multimodal integration. First, upregulation of multimodal integration is not possible using tDCS over the PPC as the integration process already functions at maximum capacity. Second, prefrontal decision-making areas may have overruled any modulated input from the PPC as it may not have matched their decision-making criterion and compensated for the modulation.

Chronic Nitrogen Deposition Induces Phosphorus Limitation of Aquatic, But Not Terrestrial, Decomposition - Kevin S. Simon; Dennis S. Anderson; Ivan J. Fernandez; Stephen A. Norton (Ecosystems, 2023)
Elevated deposition of atmospheric nitrogen (N) has shifted nutrient availability in terrestrial and aquatic habitats of ecosystems, but rarely are ecosystem processes in those components examined simultaneously. We used a multi-decadal, whole, paired watershed experiment to determine how chronic N enrichment with (NH 4 ) 2 SO 4 alters litter decomposition in terrestrial and stream systems. We also used short-term phosphorus (P) enrichment experiments within both watersheds to determine whether chronic N enrichment enhances P limitation of decomposition. Leaves from N-treated and reference watersheds were used in a reciprocal design to parse effects of altered nutrient availability in leaves and in the environment. We found divergent responses of terrestrial and stream decomposition to altered nutrient regimes. Chronic experimental N enrichment increased N and P concentrations in post-abscission leaves which decayed faster than leaves from the reference watershed in the terrestrial environment. Experimental N enrichment also did not induce P limitation of terrestrial decomposition. In contrast, litter decomposition rate in the two streams was not enhanced by elevated N in stream water or by altered leaf chemistry. Instead, chronic experimental N enrichment shifted decomposition in streams from co-limitation to strong P limitation. Microbial respiration and extracellular enzyme production responded to altered nutrient availability in a manner consistent with resource allocation models. Divergent responses of terrestrial and aquatic decomposition to elevated N deposition likely arise from differences in water bioavailability. Our work highlights the value of simultaneously considering ecosystem processes in terrestrial and aquatic systems to understand the consequences of integrated landscape processes operating on large spatial scales.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Wild boar visits to commercial pig farms in southwest England: implications for disease transmission - Sonny A. Bacigalupo; Linda K. Dixon; Simon Gubbins; Adam J. Kucharski; Julian A. Drewe (European Journal of Wildlife Research, 2022)
Contact between wild animals and farmed livestock may result in disease transmission with huge financial, welfare and ethical consequences. Conflicts between people and wildlife can also arise when species such as wild boar (Sus scrofa) consume crops or dig up pasture. This is a relatively recent problem in England where wild boar populations have become re-established in the last 20 years following a 500-year absence. The aim of this pilot study was to determine if and how often free-living wild boar visited two commercial pig farms near the Forest of Dean in southwest England. We placed 20 motion-sensitive camera traps at potential entry points to, and trails surrounding, the perimeter of two farmyards housing domestic pigs between August 2019 and February 2021, covering a total of 6030 trap nights. Forty wild boar detections were recorded on one farm spread across 27 nights, with a median (range) of 1 (0 to 7) night of wild boar activity per calendar month. Most of these wild boar detections occurred between ten and twenty metres of housed domestic pigs. No wild boar was detected at the other farm. These results confirm wild boar do visit commercial pig farms, and therefore, there is potential for contact and pathogen exchange between wild boar and domestic pigs. The visitation rates derived from this study could be used to parameterise disease transmission models of pathogens common to domestic pigs and wild boars, such as the African swine fever virus, and subsequently to develop mitigation strategies to reduce unwanted contacts.

Dispersal syndromes in challenging environments: A cross‐species experiment - Julien Cote; Maxime Dahirel; Nicolas Schtickzelle; Florian Altermatt; Armelle Ansart; Simon Blanchet; Alexis S. Chaine; Frederik De Laender; Jonathan De Raedt; Bart Haegeman; Staffan Jacob; Oliver Kaltz; et al. (Ecology Letters, 2022)
Dispersal is a central biological process tightly integrated into life‐histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. As for dispersal on its own, these syndromes are likely neither fixed nor random, but conditional on the experienced environment. We experimentally studied how dispersal propensity varies with individuals' phenotype and local environmental harshness using 15 species ranging from protists to vertebrates. We reveal a general phenotypic dispersal syndrome across studied species, with dispersers being larger, more active and having a marked locomotion‐oriented morphology and a strengthening of the link between dispersal and some phenotypic traits with environmental harshness. Our proof‐of‐concept metacommunity model further reveals cascading effects of context‐dependent syndromes on the local and regional organisation of functional diversity. Our study opens new avenues to advance our understanding of the functioning of spatially structured populations, communities and ecosystems.

Turning a lost reef ecosystem into a national restoration program - Dominic McAfee; Ian M. McLeod; Heidi K. Alleway; Melanie J. Bishop; Simon Branigan; Sean D. Connell; Craig Copeland; Christine M. Crawford; Ben K. Diggles; James A. Fitzsimons; Ben L. Gilby; Paul Hamer; et al. (Conservation Biology, 2022)
Achieving a sustainable socioecological future now requires large‐scale environmental repair across legislative borders. Yet, enabling large‐scale conservation is complicated by policy‐making processes that are disconnected from socioeconomic interests, multiple sources of knowledge, and differing applications of policy. We considered how a multidisciplinary approach to marine habitat restoration generated the scientific evidence base, community support, and funding needed to begin the restoration of a forgotten, functionally extinct shellfish reef ecosystem. The key actors came together as a multidisciplinary community of researchers, conservation practitioners, recreational fisher communities, and government bodies that collaborated across sectors to rediscover Australia's lost shellfish reefs and communicate the value of its restoration. Actions undertaken to build a case for large‐scale marine restoration included synthesizing current knowledge on Australian shellfish reefs and their historical decline, using this history to tell a compelling story to spark public and political interest, integrating restoration into government policy, and rallying local support through community engagement. Clearly articulating the social, economic, and environmental business case for restoration led to state and national funding for reef restoration to meet diverse sustainability goals (e.g., enhanced biodiversity and fisheries productivity) and socioeconomic goals (e.g., job creation and recreational opportunities). A key lesson learned was the importance of aligning project goals with public and industry interests so that projects could address multiple political obligations. This process culminated in Australia's largest marine restoration initiative and shows that solutions for large‐scale ecosystem repair can rapidly occur when socially valued science acts on political opportunities.

Reconstruction of short-term storm surge-driven increases in shallow coastal lake salinity using ostracod shell chemistry - Lucy R. Roberts; Jonathan A. Holmes; David J. Horne; Melanie J. Leng; Carl D. Sayer; Rhys G. O. Timms; Katy Flowers; Simon P. M. Blockley; Andrea Kelly (Natural Hazards, 2022)

Unusual early peaks of airborne ragweed (Ambrosia L.) pollen in the Pannonian Biogeographical Region - D. Magyar; R. Novák; O. Udvardy; A. Páldy; T. Szigeti; B. Stjepanović; I. Hrga; A. Večenaj; A. Vucić; D. Peroš Pucar; B. Šikoparija; P. Radišić; et al. (International Journal of Biometeorology, 2022)

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

A regional (land–ocean) comparison of the seasonal to decadal variability of the Northern Hemisphere jet stream 1871–2011 - Samantha Hallam; Simon A. Josey; Gerard D. McCarthy; Joël J.-M. Hirschi (Climate Dynamics, 2022)
Seasonal to decadal variations in Northern Hemisphere jet stream latitude and speed over land (Eurasia, North America) and oceanic (North Atlantic, North Pacific) regions are presented for the period 1871–2011 from the Twentieth Century Reanalysis dataset. Significant regional differences are seen on seasonal to decadal timescales. Seasonally, the jet latitude range is lower over the oceans compared to land, reduced from 20° over Eurasia to 10° over the North Atlantic where the ocean meridional heat transport is greatest. The mean jet latitude range is at a minimum in winter (DJF), particularly along the western boundary of the North Pacific and North Atlantic, where the land-sea contrast and SST gradients are strongest. The 141-year trends in jet latitude and speed show differences on a regional basis. The North Atlantic has significant increasing jet latitude trends in all seasons, up to 3° in winter. Eurasia has significant increasing trends in winter and summer, however, no increase is seen across the North Pacific or North America. Jet speed shows significant increases evident in winter (up to 4.7 ms −1 ), spring and autumn over the North Atlantic, Eurasia and North America however, over the North Pacific no increase is observed. Long term trends are generally overlaid by multidecadal variability, particularly evident in the North Pacific, where 20-year variability in jet latitude and jet speed are seen, associated with the Pacific Decadal Oscillation which explains 50% of the winter variance in jet latitude since 1940. The results highlight that northern hemisphere jet variability and trends differ on a regional basis (North Atlantic, North Pacific, Eurasia and North America) on seasonal to decadal timescales, suggesting that different mechanisms are influencing the jet latitude and speed. This is important from a climate modelling perspective and for climate predictions in the near and longer term.

Classification of new morbillivirus and jeilongvirus sequences from bats sampled in Brazil and Malaysia - Heather L. Wells; Elizabeth Loh; Alessandra Nava; Mónica Romero Solorio; Mei Ho Lee; Jimmy Lee; Jum R. A. Sukor; Isamara Navarrete-Macias; Eliza Liang; Cadhla Firth; Jonathan H. Epstein; Melinda K. Rostal; et al. (Archives of Virology, 2022)
As part of a broad One Health surveillance effort to detect novel viruses in wildlife and people, we report several paramyxovirus sequences sampled primarily from bats during 2013 and 2014 in Brazil and Malaysia, including seven from which we recovered full-length genomes. Of these, six represent the first full-length paramyxovirid genomes sequenced from the Americas, including two that are the first full-length bat morbillivirus genome sequences published to date. Our findings add to the vast number of viral sequences in public repositories, which have been increasing considerably in recent years due to the rising accessibility of metagenomics. Taxonomic classification of these sequences in the absence of phenotypic data has been a significant challenge, particularly in the subfamily Orthoparamyxovirinae , where the rate of discovery of novel sequences has been substantial. Using pairwise amino acid sequence classification (PAASC), we propose that five of these sequences belong to members of the genus Jeilongvirus and two belong to members of the genus Morbillivirus . We also highlight inconsistencies in the classification of Tupaia virus and Mòjiāng virus using the same demarcation criteria and suggest reclassification of these viruses into new genera. Importantly, this study underscores the critical importance of sequence length in PAASC analysis as well as the importance of biological characteristics such as genome organization in the taxonomic classification of viral sequences.

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Krill biomass estimation: Sampling and measurement variability - Fiona Bairstow; Sven Gastauer; Simon Wotherspoon; C. Tom A. Brown; So Kawaguchi; Tom Edwards; Martin J. Cox (Frontiers in Marine Science, 2022)
Krill are the subject of growing commercial fisheries and therefore fisheries management is necessary to ensure long-term sustainability. Krill catch limits, set by Commission for the Conservation of Antarctic Marine Living Resources, are based on absolute krill biomass, estimated from acoustic-trawl surveys. In this work, we develop a method for determining an error budget for acoustic-trawl surveys of krill which includes sampling and measurement variability. We use our error budget method to examine the sensitivity of biomass estimates to parameters in acoustic target strength (TS) models, length frequency distribution and length to wetmass relationships derived from net data. We determined that the average coefficient of variation ( CV ) of estimated biomass was 17.7% and the average CV due from scaling acoustic observations to biomass density was 5.3%. We found that a large proportion of the variability of biomass estimates is due to the krill orientation distribution, a parameter in the TS model. Orientation distributions with narrow standard deviations were found to emphasise the results of nulls in the TS to length relationship, which has to potential to lead to biologically implausible results.

Barriers to coastal planning and policy use of environmental research in Aotearoa-New Zealand - Judi E. Hewitt; Carolyn J. Lundquist; Conrad A. Pilditch; Simon F. Thrush; Stephen C. Urlich (Frontiers in Marine Science, 2022)
Identifying barriers to the effective use of science in coastal management of Aotearoa-New Zealand is easy, due to the present lack of complicated governance and management structures, coupled with an emphasis on funding science that includes pathways to implementation. This opinion piece discusses four areas that still hinder effective use of science, all of which are likely to be problematic for other countries. We initially focus on why the science may not be used related to: misunderstandings (linguistic and conceptual differences including indigenous world views); timing of information delivery; uncertainty surrounding the information (knowledge limitations and funding); and top-down constraints (legal systems, politics and institutional objectives). We use Aotearoa-New Zealand examples to demonstrate the barriers operating within each area and discuss three potential solutions. Importantly our analysis indicates that researchers alone cannot transcend these barriers; rather, we need to work as part of an ecosystem, requiring commitment from all society, extending beyond the usual suspects (management agencies). We believe that ecological and systems education from junior school levels through to universities have an important role to play in setting the context to overcome current barriers.

Coralline Hills: high complexity reef habitats on seamount summits of the Vitória-Trindade Chain - Helder Coelho Guabiroba; Luiz A. Rocha; Jean-Christophe Joyeux; Caio R. Pimentel; João Batista Teixeira; Raphael M. Macieira; João Luiz Gasparini; Ronaldo Bastos Francini-Filho; Ryan Andrades; Eric Mazzei; Thiony Simon; Marina Sissini; et al. (Coral Reefs, 2022)

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Genomic erosion in a demographically recovered bird species during conservation rescue - Hazel A. Jackson; Lawrence Percival‐Alwyn; Camilla Ryan; Mohammed F. Albeshr; Luca Venturi; Hernán E. Morales; Thomas C. Mathers; Jonathan Cocker; Samuel A. Speak; Gonzalo G. Accinelli; Tom Barker; Darren Heavens; et al. (Conservation Biology, 2022)
The pink pigeon ( Nesoenas mayeri ) is an endemic species of Mauritius that has made a remarkable recovery after a severe population bottleneck in the 1970s to early 1990s. Prior to this bottleneck, an ex situ population was established from which captive‐bred individuals were released into free‐living subpopulations to increase population size and genetic variation. This conservation rescue led to rapid population recovery to 400–480 individuals, and the species was twice downlisted on the International Union for the Conservation of Nature (IUCN) Red List. We analyzed the impacts of the bottleneck and genetic rescue on neutral genetic variation during and after population recovery (1993–2008) with restriction site‐associated sequencing, microsatellite analyses, and quantitative genetic analysis of studbook data of 1112 birds from zoos in Europe and the United States. We used computer simulations to study the predicted changes in genetic variation and population viability from the past into the future. Genetic variation declined rapidly, despite the population rebound, and the effective population size was approximately an order of magnitude smaller than census size. The species carried a high genetic load of circa 15 lethal equivalents for longevity. Our computer simulations predicted continued inbreeding will likely result in increased expression of deleterious mutations (i.e., a high realized load) and severe inbreeding depression. Without continued conservation actions, it is likely that the pink pigeon will go extinct in the wild within 100 years. Conservation rescue of the pink pigeon has been instrumental in the recovery of the free‐living population. However, further genetic rescue with captive‐bred birds from zoos is required to recover lost variation, reduce expression of harmful deleterious variation, and prevent extinction. The use of genomics and modeling data can inform IUCN assessments of the viability and extinction risk of species, and it helps in assessments of the conservation dependency of populations.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Expression of Human Immunodeficiency Virus Transactivator of Transcription (HIV-Tat1-86) Protein Alters Nociceptive Processing that is Sensitive to Anti-Oxidant and Anti-Inflammatory Interventions - Thomas J. Cirino; Amy R. Alleyne; Vinicius Duarte; Ariana Figueroa; Chloe A. Simons; Emet M. Anceaume; Justin Kendrick; Olivia Wallman; Shainnel O. Eans; Heather M. Stacy; Jessica M. Medina; Jay P. McLaughlin (Journal of Neuroimmune Pharmacology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Assessing rates of parasite coinfection and spatiotemporal strain variation via metabarcoding: Insights for the conservation of European turtle doves Streptopelia turtur - Rebecca C. Thomas; Jenny C. Dunn; Deborah A. Dawson; Helen Hipperson; Gavin J. Horsburgh; Antony J. Morris; Chris Orsman; John Mallord; Philip V. Grice; Keith C. Hamer; Cyril Eraud; Lormée Hervé; et al. (Molecular Ecology, 2022)
Understanding the frequency, spatiotemporal dynamics and impacts of parasite coinfections is fundamental to developing control measures and predicting disease impacts. The European turtle dove ( Streptopelia turtur ) is one of Europe's most threatened bird species. High prevalence of infection by the protozoan parasite Trichomonas gallinae has previously been identified, but the role of this and other coinfecting parasites in turtle dove declines remains unclear. Using a high‐throughput sequencing approach, we identified seven strains of T . gallinae , including two novel strains, from ITS1/5.8S/ITS2 ribosomal sequences in turtle doves on breeding and wintering grounds, with further intrastrain variation and four novel subtypes revealed by the iron‐hydrogenase gene. High spatiotemporal turnover was observed in T . gallinae strain composition, and infection was prevalent in all populations (89%–100%). Coinfection by multiple Trichomonas strains was rarer than expected (1% observed compared to 38.6% expected), suggesting either within‐host competition, or high mortality of coinfected individuals. In contrast, coinfection by multiple haemosporidians was common (43%), as was coinfection by haemosporidians and T . gallinae (90%), with positive associations between strains of T . gallinae and Leucocytozoon suggesting a mechanism such as parasite‐induced immune modulation. We found no evidence for negative associations between coinfections and host body condition. We suggest that longitudinal studies involving the recapture and investigation of infection status of individuals over their lifespan are crucial to understand the epidemiology of coinfections in natural populations.

Rapid Site Selection to Prioritize Coastal Seascapes for Nature-Based Solutions With Multiple Benefits - Simon J. Pittman; Kostantinos A. Stamoulis; Marina Antonopoulou; Himansu S. Das; Mohammad Shahid; Jade M. S. Delevaux; Lisa M. Wedding; Daniel Mateos-Molina (Frontiers in Marine Science, 2022)
Coastal seascapes are productive and diverse land-sea systems that provide many valuable benefits yet are increasingly threatened by human activity. Scaling up of nature-based solutions (NbS) to effectively protect, sustainably manage, and restore coastal seascapes is urgently required for mitigation of climate change and biodiversity loss while also providing socio-economic benefits. Evidence-based site selection is an important first step to improve the outcomes and avoid negative impacts when prioritizing NbS investments at national level. We developed a spatially explicit, integrative and culturally relevant ecosystem-based site selection process to identify a portfolio of seascapes for NbS consideration in the United Arab Emirates (UAE). The primary goal was to rank planning units based on potential for climate change mitigation action, positive impact to biodiversity and socio-economic benefits to people. The multi-criteria site-selection framework provided a rapid, transparent, repeatable and scalable tool. The highest weightings were assigned to blue carbon storage value, biodiversity conservation features, and local stakeholder preferred areas. Spatial proxies for benefits to people were represented by population density and accessibility to coastal seascapes, relative tourism and recreation potential, and importance of fish habitat and fishing grounds for food security. Participatory mapping of local knowledge and review of existing data ensured that both qualitative and quantitative criteria were reliable, up-to-date and locally relevant. Two distinct clusters of high suitability planning units were identified in the Abu Dhabi region and four along the north-western coast of the UAE. Most high suitability sites were located outside of existing marine protected areas. Alternative spatial scenarios without stakeholder bias underscored the suitability of sites identified through participatory mapping and highlighted additional priority sites for future scaling-up of NbS. A spatial corridor of medium and high suitability planning units across the region offers potential for designing well-connected NbS investments to accelerate and boost synergistic outcomes and increase resilience. The site selection framework provides a rapid tool that integrates local and global open access data at a range of scales with great potential for transferability to other regions worldwide.

Comparative associations of baseline frailty status and age with postoperative mortality and duration of hospital stay following metastatic brain tumor resection - Alis J. Dicpinigaitis; Simon Hanft; Jared B. Cooper; Chirag D. Gandhi; Syed Faraz Kazim; Meic H. Schmidt; Fawaz Al-Mufti; Christian A. Bowers (Clinical & Experimental Metastasis, 2022)

Variation in δ 13 C and δ 15 N values of mothers and their calves across southern right whale nursery grounds: The effects of nutritional stress? - Emma L. Carroll; Glenn Dunshea; Paulo H. Ott; Luciano O. Valenzuela; C. Scott Baker; Simon J. Childerhouse; Oscar E. Gaggiotti; Paulo A. C. Flores; Karina Groch; Darren R. Gröcke; Mark A. Hindell; David Lundquist; et al. (Marine Mammal Science, 2022)
Southern right whales (SRW) are capital breeders that use stored energy reserves to sustain themselves and their calves on nursery areas. With successful calving events declining in some SRW populations, it has been hypothesized that nutritional stress in adult females causes reproductive failure or death of calves shortly after birth. Here we compared offsets in carbon and nitrogen isotope values of mothers and their offspring (Δ 13 C calf‐cow and Δ 15 N calf‐cow ) among three SRW populations. SRW from Aotearoa New Zealand, with high population growth rates and body conditions scores, have negative Δ 13 C calf‐cow suggesting calves are utilizing 13 C‐depleted lipid carbon in milk to fuel the synthesis of nonessential amino acids used to build new tissues and rapidly grow. In contrast, a significantly positive Δ 13 C calf‐cow offset previously reported for SRW from Argentina during a mass die‐off event was hypothesized to be due to calves consuming milk with low lipid content. Patterns in Δ 15 N calf‐cow were more difficult to interpret and highlight the complexity in nitrogen transfer between mother and offspring. When combined with similar data collected from Brazil and during a low mortality year in Argentina, we hypothesize this approach provides a way to retrospectively compare nutritional condition of breeding adult female SRW across nursery areas.

First satellite‐tracked movements of pygmy blue whales ( Balaenoptera musculus brevicauda ) in New Zealand waters - Kimberly T. Goetz; Simon J. Childerhouse; David Paton; Mike Ogle; Krista van der Linde; Rochelle Constantine; Michael C. Double; Virginia Andrews‐Goff; Alexandre N. Zerbini; Paula A. Olson (Marine Mammal Science, 2022)

Strong and lasting impacts of past global warming on baleen whales and their prey - Andrea A. Cabrera; Elena Schall; Martine Bérubé; Pia Anderwald; Lutz Bachmann; Simon Berrow; Peter B. Best; Phillip J. Clapham; Haydée A. Cunha; Luciano Dalla Rosa; Carolina Dias; Kenneth P. Findlay; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real‐time effects into their long‐term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long‐term responses of natural populations to periods with global warming. The effects of this post‐LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large‐scale climate fluctuations during the post‐LGM affected baleen whales and their prey, we conducted an extensive, large‐scale analysis of the long‐term effects of the post‐LGM warming on abundance and inter‐ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome‐wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post‐LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean‐wide expansions and decreases in abundance that were initiated by the post‐LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long‐lasting impacts of global warming on marine fauna.

Prediction of glomerular filtration rate maturation across preterm and term neonates and young infants using inulin as marker - Yunjiao Wu; Karel Allegaert; Robert B. Flint; Sinno H. P. Simons; Elke H. J. Krekels; Catherijne A. J. Knibbe; Swantje Völler (The AAPS Journal, 2022)
Describing glomerular filtration rate (GFR) maturation across the heterogeneous population of preterm and term neonates and infants is important to predict the clearance of renally cleared drugs. This study aims to describe the GFR maturation in (pre)term neonates and young infants (PNA < 90 days) using individual inulin clearance data (CL inulin ). To this end, published GFR maturation models were evaluated by comparing their predicted GFR with CL inulin retrieved from literature. The best model was subsequently optimized in NONMEM V7.4.3 to better fit the CL inulin values. Our study evaluated seven models and collected 381 individual CL inulin values from 333 subjects with median (range) birthweight (BWb) 1880 g (580–4950), gestational age (GA) 34 weeks (25–43), current weight (CW) 1890 g (480–6200), postnatal age (PNA) 3 days (0–75), and CL inulin 2.20 ml/min (0.43–17.90). The De Cock 2014 model (covariates: BWb and PNA) performed the best in predicting CL inulin , followed by the Rhodin 2009 model (covariates: CW and postmenstrual age). The final optimized model shows that GFR at birth is determined by BWb, thereafter the maturation rate of GFR is dependent on PNA and GA, with a higher GA showing an overall faster maturation. To conclude, using individual CL inulin data, we found that a model for neonatal GFR requires a distinction between prenatal maturation quantified by BWb and postnatal maturation. To capture postnatal GFR maturation in (pre)term neonates and young infants, we developed an optimized model in which PNA-related maturation was dependent on GA. Graphical abstract

Rifting and recharge as triggers of the mixed basalt–rhyolite Halarauður ignimbrite eruption (Krafla, Iceland) - Shane M. Rooyakkers; John Stix; Kim Berlo; Daniele Morgavi; Maurizio Petrelli; Monika K. Rusiecka; Simon J. Barker; Bruce L. A. Charlier; David A. Neave; Francesco P. Vetere; Diego Perugini (Contributions to Mineralogy and Petrology, 2022)

Evaluating methods for estimating shark natural mortality rate and management reference points using life‐history parameters - Shijie Zhou; Roy A. Deng; Matthew R. Dunn; Simon D. Hoyle; Yeming Lei; Ashley J. Williams (Fish and Fisheries, 2022)
Sharks (class Chondrichthyes, subclass Elasmobranchii) typically have a long lifespan, slow growth rate and low fecundity, leading to low productivity and hence relatively high vulnerability to fishing. Information for managing fisheries catches of elasmobranchs is often lacking, because elasmobranchs are usually non‐target species, often with low abundance. It is more feasible to develop management reference points for elasmobranchs based on their life‐history information than through traditional stock assessments. The natural mortality rate ( M ) is the leading life‐history parameter (LHP) required by many methods for developing reference points and is itself often derived indirectly from other LHPs. In this paper, we evaluate nine M estimators, using 15 shark stocks in the Western and Central Pacific Ocean as examples. We then compare four methods for developing fishing mortality reference points F msy , including empirical modelling, the Euler‐Lotka equation, an M ‐productivity‐based method and the spawning potential rate converted method. Our analyses show that popular M estimators developed mainly from teleost data resulted in large deviations from the average and were not suitable for elasmobranchs. All four methods for estimating F msy performed similarly. However, the empirical method is very simple and cost‐effective and tended to produce smaller deviations from the average than the other three methods. Nonetheless, it is recommended that multiple methods should be used to minimize possible bias and reflect uncertainty, if the required LHPs are available.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

The Extremes of Disturbance Reduce Functional Redundancy: Functional Trait Assessment of the Shallow Antarctic Benthos - Ben J. O. Robinson; David K. A. Barnes; Laura J. Grange; Simon A. Morley (Frontiers in Marine Science, 2022)
Climate-driven changes in disturbance are a major threat to ecosystem Functional diversity. The selective mechanisms underlying ecosystem response to disturbance are far from universal and remain the subject of scientific debate. Ice scouring of the shallow Antarctic benthos is one of the largest disturbance gradients in the natural environment and thus provides an opportunity to investigate how disturbance gradients influence functional structure of a biological assemblage. The Western Antarctic Peninsula, in particular, is a hotspot of climate-driven environmental change. Addressing how this system might respond to species loss is critical. Previous surveys across the shallowest 100 m of the seabed, detected unimodal changes in diversity and a shift in assemblage composition in response to disturbance gradients. This study investigated how functional traits and associated functional diversity change across the depth gradient. Our results revealed that selective mechanisms, such as disturbance filtering and inter-species competition, reduce functional redundancy at the extremes of the disturbance gradient. Our study highlights areas of potential vulnerability to future environmental change due to low functional redundancy. Threatening the important negative (mitigating) feedbacks on climate change, through blue carbon, currently provided by Antarctic continental shelf benthic assemblages.

Assessment of Australian Sea Lion Bycatch Mortality in a Gillnet Fishery, and Implementation and Evaluation of an Effective Mitigation Strategy - Simon D. Goldsworthy; Brad Page; Derek J. Hamer; Andrew D. Lowther; Peter D. Shaughnessy; Mark A. Hindell; Paul Burch; Daniel P. Costa; Shannon L. Fowler; Kristian Peters; Rebecca R. McIntosh; Frederic Bailleul; et al. (Frontiers in Marine Science, 2022)
Globally, the bycatch of marine mammals in fisheries represents the greatest source of human-caused mortality that threatens the sustainability of many populations and species. The Australian sea lion ( Neophoca cinerea ) is an endangered species, whose populations off South Australia (SA) have been subject to bycatch in a demersal gillnet fishery targeting sharks since the 1960s. A comprehensive assessment was undertaken of sea lion bycatch mortality that combined independent fishery observer data with species distribution models (underpinned by satellite tracking, abundance data and population modeling) to model the relationship between at-sea foraging effort and bycatch rate. Combined with the distribution of fishing effort, these models enabled the overall level of bycatch mortality to be estimated by age, sex and subpopulation, facilitating population viability analyses that indicated most subpopulations were declining, and subject to unsustainable levels of bycatch mortality. To reduce this mortality, the Australian Fisheries Management Authority implemented an Australian Sea Lion Management Strategy that included an independent observer program (ultimately 100% electronic monitoring of gillnet fishing off SA), permanent spatial gillnet closures around all sea lion breeding sites, bycatch mortality limits that triggered temporal (18 months) spatial closures when zone-specific bycatch trigger limits were reached, and incentives for gillnet fishers to switch to an alternate fishing method (longlines). The Strategy had immediate impacts on the fishery: it resulted in significant reductions in gillnet fishing effort and on the reported bycatch of sea lions. In the next decade, there was an estimated 98% reduction in sea lion bycatch mortality from gillnet interactions and an apparent stabilization of the decline in sea lion pup abundances at some impacted breeding sites. There was an almost complete transition in the fishery from gillnets to longlines, and fishing catches returned to pre-management levels. The successful implementation of management measures to mitigate sea lion bycatch mortality in the gillnet fishery off SA was rapid, science informed, adaptive, comprehensive, and backed by strong compliance and monitoring of the fishery. It provides an important case study which demonstrates how management measures can be effectively applied to mitigate bycatch mortality of marine mammals and other marine protected species.

Carbon dynamics and sequestration by urban mangrove forests of Dar es Salaam, Tanzania - Grace J. Maseta; Simon Mwansasu; Marco A. Njana (Western Indian Ocean Journal of Marine Science, 2022)
This study intended to 1) determine spatial and temporal changes of mangrove forests, 2) identify drivers of mangrove deforestation and forest degradation, 3) determine historical carbon storage, sequestration and deforestation emissions by mangrove forests, and 4) determine whether mangrove forests are a source or sink of CO2 in Dar es Salaam, Tanzania. Mangrove forests have decreased from 4,813 hectares in 1986 to 1961 hectares in 2016. The following were prominent drivers of deforestation in descending order: clearing mangrove forests for salt pans; hotel construction; settlement; and charcoal making. Tree removals for firewood and building poles were also prominent drivers of mangrove forest degradation. Similarly, carbon stored in mangrove forests has decreased from 1,131,055 tonnes CO2e in 1986 to 460,835 tonnes CO2e in 2016. Sequestration of CO2 by mangrove forests is estimated at 133,516 (1986-1995); 106,110 (1995-2006) and 69,616 (2006-2016) tonnes CO2e year-1. Conversely, mangrove deforestation has resulted in emissions of about 27,400, 16,500 and 24,000 tonnes CO2e year-1 in 1986-1995, 1995- 2006 and 2006-2016, respectively. Urban mangrove forests play an important environmental role in mitigating climate change and amelioration of local weather through the large carbon stocks they store and sequester. Mangrove forests in the study area remain a net carbon sink, however, the sink role played by mangrove forests in the study area is decreasing rapidly. The declining spatial and temporal trends of urban mangrove forest cover has resulted in a systematic decrease in the total carbon stored and sequestered by mangrove forests. In the absence of timely measures of preserving and rehabilitating degraded mangrove areas, the mangrove forests of Dar es Salaam may become the source of CO2. The study recommends effective urban land use planning and effective law enforcement to ensure a win-win situation through sustained ecosystem services offered by urban mangrove forests to support economic growth.

Range expansion and complete mitochondrial genome of the highfin blenny (Lupinoblennius nicholsi) - Logan Turner; Nathan J. C. Backenstose; Simon Brandl; Moisés A. Bernal (Molecular Biology Reports, 2022)

Prevalence and polymorphism of a mussel transmissible cancer in Europe - Maurine Hammel; Alexis Simon; Christine Arbiol; Antonio Villalba; Erika A. V. Burioli; Jean‐François Pépin; Jean‐Baptiste Lamy; Abdellah Benabdelmouna; Ismael Bernard; Maryline Houssin; Guillaume M. Charrière; Delphine Destoumieux‐Garzon; et al. (Molecular Ecology, 2022)
Transmissible cancers are parasitic malignant cell lineages that have acquired the ability to infect new hosts from the same species, or sometimes related species. First described in dogs and Tasmanian devils, transmissible cancers were later discovered in some marine bivalves affected by a leukaemia‐like disease. In Mytilus mussels, two lineages of bivalve transmissible neoplasia (BTN) have been described to date (MtrBTN1 and MtrBTN2), both of which emerged in a Mytilus trossulus founder individual. Here, we performed extensive screening of genetic chimerism, a hallmark of transmissible cancer, by genotyping 106 single nucleotide polymorphisms of 5,907 European Mytilus mussels. Genetic analysis allowed us to simultaneously obtain the genotype of hosts – Mytilus edulis , M . galloprovincialis or hybrids – and the genotype of tumours of heavily infected individuals. In addition, a subset of 222 individuals were systematically genotyped and analysed by histology to screen for possible nontransmissible cancers. We detected MtrBTN2 at low prevalence in M . edulis , and also in M . galloprovincialis and hybrids although at a much lower prevalence. No MtrBTN1 or new BTN were found, but eight individuals with nontransmissible neoplasia were observed at a single polluted site on the same sampling date. We observed a diversity of MtrBTN2 genotypes that appeared more introgressed or more ancestral than MtrBTN1 and reference healthy M . trossulus individuals. The observed polymorphism is probably due to somatic null alleles caused by structural variations or point mutations in primer‐binding sites leading to enhanced detection of the host alleles. Despite low prevalence, two sublineages divergent by 10% fixed somatic null alleles and one nonsynonymous mtCOI (mitochondrial cytochrome oxidase I) substitution are cospreading in the same geographical area, suggesting a complex diversification of MtrBTN2 since its emergence and host species shift.

Small Blubber Samples (50 mg) Sufficient for Analyses of 10 Stress and Reproductive Steroid Hormones in Gray and Fin Whales via Liquid Chromatography Mass Spectrometry - Christiana Wittmaack; Jorge Urbán Ramírez; Daniela Bernot-Simon; Sergio Martínez-Aguilar; Seenivasan Subbiah; James G. Surles; Mary Looney; Naveen Kumar; Barbie Halaska; Pádraig J. Duignan; Madelyn Knauss; Kristen Burns; et al. (Frontiers in Marine Science, 2022)
Information on stress, reproductive fitness, and health is difficult to obtain in wild cetaceans but critical for conservation and management. The goal of this study was to develop a methodology requiring minimal blubber mass for analysis of reproductive and stress steroid hormones and, hence, suitable for cetacean biopsies. Blubber biopsies and samples were collected from free-ranging and stranded gray and fin whales. Steroid hormones were extracted from blubber samples as small as 50 mg using liquid-liquid extraction methodology developed to handle the high fat content of blubber. Samples were analyzed via liquid chromatography with tandem mass spectrometry for 10 hormones: aldosterone, androstenedione, cortisol, cortisone, corticosterone, 17β-estradiol, estrone, 17α-hydroxyprogesterone, progesterone, and testosterone. As part of the optimization, homogenization via bead beating and blade dispersion were compared, and the former found superior. To investigate optimal yet minimal tissue mass required, hormone panels were compared among paired 50, 150, and 400 mg samples, the latter two being commonly reported masses for hormone blubber analysis. Results indicated that 50 mg of blubber was suitable and sometimes superior. Additionally, significant differences in precision values were observed between species, possibly stemming from differences in blubber composition, and relevant to homogenization technique selection and calibration methods that use blubber matrix matches obtained from a species other than the study species. Based on recovery and precision values, our methodology was accurate and precise in the measurement of spiked known quantities for all 10 hormones, confirming the methodology capabilities in 50 mg blubber mass in both species. Altogether, and in our specific sample sets, all endogenous hormones, except corticosterone, were identified above the detection limit in 50 mg gray whale blubber samples while all endogenous hormones, except aldosterone, cortisone, estrone, and progesterone, were detected in 50 mg fin whale blubber samples. We present a robust methodology for the analysis of multiple reproductive and stress steroid hormones in minimal masses of cetacean blubber compatible with small biopsies. Finally, we identified statistically significant differences in corticosteroid concentrations between stranded and free ranging animals.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ambrein: a minor, but common constituent of mammalian faeces? - Steven J. Rowland; Paul A. Sutton; Barbara von der Lühe; John K. Volkman; Christopher H. Vane; Simon N. Ingram; Charlotte Dunn; Diane Claridge (Natural Product Research, 2021)

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

A comment on: magma residence and eruption at the Taupō Volcanic Center (Taupō Volcanic Zone, New Zealand)—insights from rhyolite-MELTS geobarometry, diffusion chronometry, and crystal textures, by AS Pamukçu et al., Contrib Mineral Petrol 175:48 (2020) - Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier; Madison L. Myers; Kristian F. Hansen (Contributions to Mineralogy and Petrology, 2021)

Lake microbial communities are not resistant or resilient to repeated large‐scale natural pulse disturbances - Katie A. Brasell; Jamie Howarth; John K. Pearman; Sean J. Fitzsimons; Anastasija Zaiko; Xavier Pochon; Marcus J. Vandergoes; Kevin S. Simon; Susanna A. Wood (Molecular Ecology, 2021)
Opportunities to study community‐level responses to extreme natural pulse disturbances in unaltered ecosystems are rare. Lake sediment records that span thousands of years can contain well‐resolved sediment pulses, triggered by earthquakes. These palaeorecords provide a means to study repeated pulse disturbances and processes of resistance (insensitivity to disturbance) and ecological resilience (capacity to regain structure, function and process). In this study, sedimentary DNA was extracted from a sediment core from Lake Paringa (New Zealand) that is situated in a near natural catchment. Metabarcoding and inferred functions were used to assess the lake microbial community over the past 1100 years – a period that included four major earthquakes. Microbial community composition and function differed significantly between highly perturbed (postseismic, ~50 years) phases directly after the earthquakes and more stable (interseismic, ~250 years) phases, indicating a lack of community resistance. Although community structure differed significantly in successive postseismic phases, function did not, suggesting potential functional redundancy. Significant differences in composition and function in successive interseismic phases demonstrate that communities are not resilient to large‐scale natural pulse disturbances. The clear difference in structure and function, and high number of indicator taxa (responsible for driving differences in communities between phases) in the fourth interseismic phase probably represents a regime shift, possibly due to the two‐fold increase in sediment and terrestrial biospheric organic carbon fluxes recorded following the fourth earthquake. Large pulse disturbances that enhance sediment inputs into lake systems may produce an underappreciated mechanism that destabilises lake ecosystem processes.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Compound-Specific Stable Isotope Analysis of Amino Acids in Pelagic Shark Vertebrae Reveals Baseline, Trophic, and Physiological Effects on Bulk Protein Isotope Records - Sarah Magozzi; Simon R. Thorrold; Leah Houghton; Victoria A. Bendall; Stuart Hetherington; Gonzalo Mucientes; Lisa J. Natanson; Nuno Queiroz; Miguel N. Santos; Clive N. Trueman (Frontiers in Marine Science, 2021)
Variations in stable carbon and nitrogen isotope compositions in incremental tissues of pelagic sharks can be used to infer aspects of their spatial and trophic ecology across life-histories. Interpretations from bulk tissue isotopic compositions are complicated, however, because multiple processes influence these values, including variations in primary producer isotope ratios and consumer diets and physiological processing of metabolites. Here we challenge inferences about shark tropho-spatial ecology drawn from bulk tissue isotope data using data for amino acids. Stable isotope compositions of individual amino acids can partition the isotopic variance in bulk tissue into components associated with primary production on the one hand, and diet and physiology on the other. The carbon framework of essential amino acids (EAAs) can be synthesised de novo only by plants, fungi and bacteria and must be acquired by consumers through the diet. Consequently, the carbon isotopic composition of EAAs in consumers reflects that of primary producers in the location of feeding, whereas that of non-essential amino acids (non-EAAs) is additionally influenced by trophic fractionation and isotope dynamics of metabolic processing. We determined isotope chronologies from vertebrae of individual blue sharks and porbeagles from the North Atlantic. We measured carbon and nitrogen isotope compositions in bulk collagen and carbon isotope compositions of amino acids. Despite variability among individuals, common ontogenetic patterns in bulk isotope compositions were seen in both species. However, while life-history movement inferences from bulk analyses for blue sharks were supported by carbon isotope data from essential amino acids, inferences for porbeagles were not, implying that the observed trends in bulk protein isotope compositions in porbeagles have a trophic or physiological explanation, or are suprious effects. We explored variations in carbon isotope compositions of non-essential amino acids, searching for systematic variations that might imply ontogenetic changes in physiological processing, but patterns were highly variable and did not explain variance in bulk protein δ 13 C values. Isotopic effects associated with metabolite processing may overwhelm spatial influences that are weak or inconsistently developed in bulk tissue isotope values, but interpreting mechanisms underpinning isotopic variation in patterns in non-essential amino acids remains challenging.

Movement ecology of black marlin Istiompax indica in the Western Indian Ocean - Christoph A. Rohner; Roy Bealey; Bernerd M. Fulanda; Jason D. Everett; Anthony J. Richardson; Simon J. Pierce (Journal of Fish Biology, 2021)
The black marlin Istiompax indica is an apex marine predator and is susceptible to overfishing. The movement ecology of the species remains poorly known, particularly within the Indian Ocean, which has hampered assessment of their conservation status and fisheries management requirements. Here, we used pop‐up archival satellite tags to track I. indica movement and examine their dispersal. Forty‐nine tags were deployed off Kenya during both the north‐east (November–April) and south‐west (August–September) monsoon seasons, providing locations from every month of the year. Individual I. indica were highly mobile and track distance correlated with the duration of tag attachment. Mean track duration was 38 days and mean track distance was >1800 km. Individuals dispersed in several directions: north‐east into Somalian waters and up to northern Oman, east towards the Seychelles, and south into the Mozambique Channel. Their core habitat shifted seasonally and overlapped with areas of high productivity off Kenya, Somalia and Oman during the first half of the year. A second annual aggregation off the Kenyan coast, during August and September, did not coincide with high chlorophyll‐ a (chl‐ a ) concentrations or thermal fronts, and the drivers of the species' presence and movement from this second aggregation was unclear. We tested their habitat preferences by comparing environmental conditions at track locations to the conditions at locations along simulated tracks based on the empirical data. Observed I. indica preferred cooler water with higher chl‐ a concentrations and stayed closer to the coast than simulated tracks. The rapid and extensive dispersal of I. indica from Kenya suggests that there is likely a single stock in the Western Indian Ocean, with individuals swimming between areas of high commercial catches off northern Somalia and Oman, and artisanal and recreational fisheries catches throughout East Africa and Mozambique.

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Taphonomy of an excavated striped hyena (Hyaena hyaena) den in Arabia: implications for paleoecology and prehistory - Mathew Stewart; Eric Andrieux; Richard Clark-Wilson; Nils Vanwezer; James Blinkhorn; Simon J. Armitage; Abdulaziz al Omari; Badr Zahrani; Mesfer Alqahtani; Mahmoud Al-Shanti; Iyad Zalmout; Yahya S. A. Al-Mufarreh; et al. (Archaeological and Anthropological Sciences, 2021)
Studies of modern carnivore accumulations of bone (i.e., neo-taphonomy) are crucial for interpreting fossil accumulations in the archaeological and paleontological records. Yet, studies in arid regions have been limited in both number and detailed taphonomic data, prohibiting our understanding of carnivore bone-accumulating and -modifying behavior in dry regions. Here, we present a taphonomic analysis of an impressive carnivore-accumulated bone assemblage from the Umm Jirsan lava tube in the Harrat Khaybar region, Saudi Arabia. The size and composition of the bone accumulation, as well as the presence of hyena skeletal remains and coprolites, suggest that the assemblage was primarily accumulated by striped hyena ( Hyaena hyaena ). Our findings (1) identify potentially useful criteria for distinguishing between accumulations generated by different species of hyenas; (2) emphasize the need for neo-taphonomic studies for capturing the full variation in carnivore bone-accumulating and modifying behavior; (3) suggest that under the right settings, striped hyena accumulations can serve as good proxies for (paleo)ecology and livestock practices; and (4) highlight the potential for future research at Umm Jirsan, as well as at the numerous nearby lava tube systems. We encourage continued neo-taphonomic efforts in regions important in human prehistory, particularly in arid zones, which have received little research attention.

High throughput shotgun sequencing of eRNA reveals taxonomic and derived functional shifts across a benthic productivity gradient - Elias Broman; Stefano Bonaglia; Alf Norkko; Simon Creer; Francisco J. A. Nascimento (Molecular Ecology, 2021)
Benthic macrofauna is regularly used in monitoring programmes, however the vast majority of benthic eukaryotic biodiversity lies mostly in microscopic organisms, such as meiofauna (invertebrates Sabatieria and foraminifera Elphidium in high OC, and Cryptocaryon ‐like ciliates in low OC sediments. Considering that future sequencing technologies are likely to decrease in cost, the use of eRNA shotgun sequencing to assess biodiversity of benthic microeukaryotes could be a powerful tool in recurring monitoring programmes.

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

The influence of seafloor terrain on fish and fisheries: A global synthesis - Hayden P. Borland; Ben L. Gilby; Christopher J. Henderson; Javier X. Leon; Thomas A. Schlacher; Rod M. Connolly; Simon J. Pittman; Marcus Sheaves; Andrew D. Olds (Fish and Fisheries, 2021)
The structure of seafloor terrain affects the distribution and diversity of animals in all seascapes. Effects of terrain on fish assemblages have been reported from most ecosystems, but it is unclear whether bathymetric effects vary among seascapes or change in response to seafloor modification by humans. We reviewed the global literature linking seafloor terrain to fish species and assemblages (96 studies) and determined that relief (e.g. depth), complexity (e.g. roughness), feature classes (e.g. substrate types) and morphology (e.g. curvature), have widespread effects on fish assemblages. Research on the ecological consequences of terrain have focused on coral reefs, rocky reefs, continental shelves and the deep sea ( n ≥ 20 studies), but are rarely tested in estuaries ( n = 7). Fish associate with a variety of terrain attributes, and assemblages change with variation in the depth and aspect of bathymetric features in reef and shelf seascapes, and in the deep sea. Fish from different seascapes also respond to distinct metrics, with fluctuations in slope of slope (coral reefs), rugosity (rocky reefs) and slope (continental shelves, deep sea) each linked to changes in assemblage composition. Terrain simplification from coastal urbanization (e.g. dredging) and resource extraction (e.g. trawling) can reduce fish diversity and abundance, but assemblages can also recover inside effective marine reserves. The consequences of these terrain changes for fish and fisheries are, however, rarely measured in most seascapes. The key challenge now is to examine how terrain modification and conservation combine to alter fish distributions and fisheries productivity across diverse coastal seascapes.

Evaluation of a laboratory-based high-throughput SARS-CoV-2 antigen assay for non-COVID-19 patient screening at hospital admission - Friederike Häuser; Martin F. Sprinzl; Kim J. Dreis; Angelique Renzaho; Simon Youhanen; Wolfgang M. Kremer; Jürgen Podlech; Peter R. Galle; Karl J. Lackner; Heidi Rossmann; Niels A. Lemmermann (Medical Microbiology and Immunology, 2021)
Several rapid antigen tests (RATs) for the detection of SARS-CoV-2 were evaluated recently. However, reliable performance data for laboratory-based, high-throughput antigen tests are lacking. Therefore and in response to a short-term shortage of PCR reagents, we evaluated DiaSorin's LIAISON SARS-CoV-2 antigen test in comparison to RT-qPCR, and concerning the application of screening non-COVID-19 patients on hospital admission. Applying the manufacturer-recommended cut-off of 200 arbitrary units (AU/mL) the specificity of the LIAISON Test was 100%, the overall analytical sensitivity 40.2%. Lowering the cut-off to 100 AU/mL increased the sensitivity to 49.7% and decreased the specificity to 98.3%. Confining the analysis to samples with an RT-qPCR result < 25 Ct resulted in a sensitivity of 91.2%. The quality of the LIAISON test is very similar to that of good RATs described in the literature with the advantage of high throughput and the disadvantage of relatively long analysis time. It passes the WHO quality criteria for rapid antigen tests and is characterized by particularly high specificity. The LIAISON test can therefore be used for the same applications as recommended for RATs by the WHO. Due to limited sensitivity, the LIAISON test should only be used for screening, if PCR-based assays are not available.

Is impaired dopaminergic function associated with mobility capacity in older adults? - Simon Moskowitz; David W. Russ; Leatha A. Clark; Nathan P. Wages; Dustin R. Grooms; Adam J. Woods; Julie Suhr; Janet E. Simon; Andrew O’Shea; Cody R. Criss; Paolo Fadda; Brian C. Clark (GeroScience, 2021)

Protective measures for patients with advanced cancer during the Sars-CoV-2 pandemic: Quo vadis? - P. Ivanyi; T. Park-Simon; H. Christiansen; R. Gutzmer; A. Vogel; M. Heuser; H. Golpon; P. Hillemanns; J. Haier (Clinical & Experimental Metastasis, 2021)
Cancer patients represent a vulnerable cohort during the Sars-CoV-2 pandemic. Oncological societies have generated a plethora of recommendations, but precise instructions about routine oncological procedures remain scarce. Here, we report on local COVID-19 protection measures established in an interdisciplinary approach at a tertiary care center during the first wave of the pandemia in Germany. Following these measures, no additional morbidity or mortality during oncological procedures was observed, and no nosocomial infections were registered. However, Validation of our measures is outstanding and regional SARS-CoV-2 prevalence was low. However, specific oncological measures might be important to ensure optimal oncological results, especially for advanced cancer stages during this and future pandemia. In the future, communication about these measures might be crucial to a cancer patient´s assigned network to reduce the danger of excess mortality within the second wave of the COVID-19 pandemic.

Brain function associated with reaction time after sport-related concussion - Nathan W. Churchill; Michael G. Hutchison; Simon J. Graham; Tom A. Schweizer (Brain Imaging and Behavior, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

A rapid benchtop method to assess biofilm on marine fouling control coatings - Simon P. J. Dennington; Alexandra Jackson; Alistair A. Finnie; Julian A. Wharton; Jennifer E. Longyear; Paul Stoodley (Biofouling, 2021)

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

Loss of Large Animals Differentially Influences Nutrient Fluxes Across a Heterogeneous Marine Intertidal Soft-Sediment Ecosystem - Jenny R. Hillman; Carolyn J. Lundquist; Theresa A. O’Meara; Simon F. Thrush (Ecosystems, 2021)

Electric Field Stimulation for the Functional Assessment of Isolated Dorsal Root Ganglion Neuron Excitability - Ian M. Berke; Tom M. McGrath; J. Jordan Stivers; Chang Gui; Marcos N. Barcellona; Matthew G. Gayoso; Simon Y. Tang; Yu-Qing Cao; Munish C. Gupta; Lori A. Setton (Annals of Biomedical Engineering, 2021)

An Evolving Clinical Need: Discordant Oxygenation Measurements of Intubated COVID-19 Patients - Jerry A. Rubano; Lauren M. Maloney; Jessica Simon; Daniel N. Rutigliano; Isadora Botwinick; Randeep S. Jawa; Marc J. Shapiro; James A. Vosswinkel; Mark Talamini; Kenneth Kaushansky (Annals of Biomedical Engineering, 2021)

Recommendations for the Standardisation of Open Taxonomic Nomenclature for Image-Based Identifications - Tammy Horton; Leigh Marsh; Brian J. Bett; Andrew R. Gates; Daniel O. B. Jones; Noëlie M. A. Benoist; Simone Pfeifer; Erik Simon-Lledó; Jennifer M. Durden; Leen Vandepitte; Ward Appeltans (Frontiers in Marine Science, 2021)
This paper recommends best practice for the use of open nomenclature (ON) signs applicable to image-based faunal analyses. It is one of numerous initiatives to improve biodiversity data input to improve the reliability of biological datasets and their utility in informing policy and management. Image-based faunal analyses are increasingly common but have limitations in the level of taxonomic precision that can be achieved, which varies among groups and imaging methods. This is particularly critical for deep-sea studies owing to the difficulties in reaching confident species-level identifications of unknown taxa. ON signs indicate a standard level of identification and improve clarity, precision and comparability of biodiversity data. Here we provide examples of recommended usage of these terms for input to online databases and preparation of morphospecies catalogues. Because the processes of identification differ when working with physical specimens and with images of the taxa, we build upon previously provided recommendations for specific use with image-based identifications.

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

What causes the spread of model projections of ocean dynamic sea-level change in response to greenhouse gas forcing? - Matthew P. Couldrey; Jonathan M. Gregory; Fabio Boeira Dias; Peter Dobrohotoff; Catia M. Domingues; Oluwayemi Garuba; Stephen M. Griffies; Helmuth Haak; Aixue Hu; Masayoshi Ishii; Johann Jungclaus; Armin Köhl; et al. (Climate Dynamics, 2021)
Sea levels of different atmosphere–ocean general circulation models (AOGCMs) respond to climate change forcing in different ways, representing a crucial uncertainty in climate change research. We isolate the role of the ocean dynamics in setting the spatial pattern of dynamic sea-level ( ζ ) change by forcing several AOGCMs with prescribed identical heat, momentum (wind) and freshwater flux perturbations. This method produces a ζ projection spread comparable in magnitude to the spread that results from greenhouse gas forcing, indicating that the differences in ocean model formulation are the cause, rather than diversity in surface flux change. The heat flux change drives most of the global pattern of ζ change, while the momentum and water flux changes cause locally confined features. North Atlantic heat uptake causes large temperature and salinity driven density changes, altering local ocean transport and ζ . The spread between AOGCMs here is caused largely by differences in their regional transport adjustment, which redistributes heat that was already in the ocean prior to perturbation. The geographic details of the ζ change in the North Atlantic are diverse across models, but the underlying dynamic change is similar. In contrast, the heat absorbed by the Southern Ocean does not strongly alter the vertically coherent circulation. The Arctic ζ change is dissimilar across models, owing to differences in passive heat uptake and circulation change. Only the Arctic is strongly affected by nonlinear interactions between the three air-sea flux changes, and these are model specific.

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Global Drivers on Southern Ocean Ecosystems: Changing Physical Environments and Anthropogenic Pressures in an Earth System - Simon A. Morley; Doris Abele; David K. A. Barnes; César A. Cárdenas; Cedric Cotté; Julian Gutt; Sian F. Henley; Juan Höfer; Kevin A. Hughes; Stephanie M. Martin; Carlos Moffat; Marilyn Raphael; et al. (Frontiers in Marine Science, 2020)
The manuscript assesses the current and expected future global drivers of Southern Ocean (SO) ecosystems. Atmospheric ozone depletion over the Antarctic since the 1970s, has been a key driver, resulting in springtime cooling of the stratosphere and intensification of the polar vortex, increasing the frequency of positive phases of the Southern Annular Mode (SAM). This increases warm air-flow over the East Pacific sector (Western Antarctic Peninsula) and cold air flow over the West Pacific sector. SAM as well as El Niño Southern Oscillation events also affect the Amundsen Sea Low leading to either positive or negative sea ice anomalies in the west and east Pacific sectors, respectively. The strengthening of westerly winds is also linked to shoaling of deep warmer water onto the continental shelves, particularly in the East Pacific and Atlantic sectors. Air and ocean warming has led to changes in the cryosphere, with glacial and ice sheet melting in both sectors, opening up new ice free areas to biological productivity, but increasing seafloor disturbance by icebergs. The increased melting is correlated with a salinity decrease particularly in the surface 100 m. Such processes could increase the availability of iron, which is currently limiting primary production over much of the SO. Increasing CO 2 is one of the most important SO anthropogenic drivers and is likely to affect marine ecosystems in the coming decades. While levels of many pollutants are lower than elsewhere, persistent organic pollutants (POPs) and plastics have been detected in the SO, with concentrations likely enhanced by migratory species. With increased marine traffic and weakening of ocean barriers the risk of the establishment of non-indigenous species is increased. The continued recovery of the ozone hole creates uncertainty over the reversal in sea ice trends, especially in the light of the abrupt transition from record high to record low Antarctic sea ice extent since spring 2016. The current rate of change in physical and anthropogenic drivers is certain to impact the Marine Ecosystem Assessment of the Southern Ocean (MEASO) region in the near future and will have a wide range of impacts across the marine ecosystem.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Assessing the Potential Impact of Changes to the Argo and Moored Buoy Arrays in an Operational Ocean Analysis System - Chongyuan Mao; Robert R. King; Rebecca Reid; Matthew J. Martin; Simon A. Good (Frontiers in Marine Science, 2020)

Spatiotemporal variations in eruption style and magnitude at Yasur volcano, Vanuatu: part 2—extending Strombolian eruption classifications - Benjamin Clifford Simons; S. J. Cronin; J. D. Eccles; A. D. Jolly; E. Garaebiti; S. Cevuard (Bulletin of Volcanology, 2020)

Rapid homoploid hybrid speciation in British gardens: The origin of Oxford ragwort ( Senecio squalidus ) - Bruno Nevado; Stephen A. Harris; Mark A. Beaumont; Simon J. Hiscock (Molecular Ecology, 2020)
Hybridisation can lead to homoploid hybrid speciation, i.e., the origin of new species without change in chromosome number between parents and offspring. Central to homoploid hybrid speciation is the role of hybridisation in the establishment of reproductive isolation between the hybrid and the parental species in the early stages of speciation, when typically all species occur at least partly in sympatry. In this work we analyse genome‐wide polymorphism data obtained by transcriptome sequencing of the British hybrid species Oxford ragwort ( Senecio squalidus, Asteraceae), its two Italian parental species ( S. aethnensis and S. chrysanthemifolius) and their naturally occurring hybrids on Mt Etna (Italy). We show that Oxford ragwort most likely originated from de novo hybridisation between its two Italian parental species whilst they were in cultivation in British gardens at the turn of the 18th century. Reproductive isolation between the new hybrid species and its parental species probably resulted from inheritance of genetic incompatibilities between the two parental species and subsequent ecological segregation – both of which have been shown in previous studies. Our results imply that S. squalidus meets the most stringent criteria set forth to identify homoploid hybrid speciation, and call attention to the creative role of hybridisation in responding to novel environmental conditions.

Movement and habitat use of striped marlin Kajikia audax in the Western Indian Ocean - Christoph A. Rohner; Roy Bealey; Bernerd M. Fulanda; Simon J. Pierce (Journal of Fish Biology, 2020)
Striped marlin Kajikia audax are globally Near Threatened and their stock in the Indian Ocean was last assessed as “overfished and subject to overfishing”. Significant gaps in our understanding of their ecology remain, hampering the efforts of fisheries managers to ensure stock sustainability. There is a particular lack of fisheries‐independent data. Here we present the results from the first large‐scale satellite tracking study of K. audax in the Indian Ocean. We tagged 49 K. audax with pop‐up archival satellite‐linked tags off the Kenyan coast from 2015 to 2019. Individuals were highly mobile, covering horizontal distances of up to 9187 km over periods ranging up to 183 days, with a mean daily distance of ~48 km. Long‐distance movements were recorded to the east and north of East Africa, with the most distant tracks extending north to the Arabian Sea and east to near the Maldives. None of the K. audax swam south of East Africa. Kernel utilization distributions of fish locations demonstrated their shifting seasonal activity hotspots. Over the sport‐fishing season (and tagging period) in Kenya, from December to March, K. audax typically stayed off the East African coast. After March, the activity hotspot shifted north to a region close to the Horn of Africa and Socotra Island. Remotely sensed sea surface temperature and chlorophyll‐ a maps indicated that this seasonal movement could be driven by a shift in prey availability. Our results show the high mobility of K. audax in the Western Indian Ocean, and that individuals seasonally range between two major fishing areas.

Effect of introduced parasites on the survival and microbiota of nestling cactus finches (Geospiza scandens) in the Galápagos Islands - Alyssa M. Addesso; Johanna A. Harvey; Grace J. Vaziri; Taylor B. Verrett; Lauren Albert; Corinne Arthur; Kiley Chernicky; Shelby R. Simons; Jaime Chaves; Sarah A. Knutie (Journal of Ornithology, 2020)

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Recognizing animal personhood in compassionate conservation - Arian D. Wallach; Chelsea Batavia; Marc Bekoff; Shelley Alexander; Liv Baker; Dror Ben‐Ami; Louise Boronyak; Adam P. A. Cardilin; Yohay Carmel; Danielle Celermajer; Simon Coghlan; Yara Dahdal; et al. (Conservation Biology, 2020)
Compassionate conservation is based on the ethical position that actions taken to protect biodiversity should be guided by compassion for all sentient beings. Critics argue that there are 3 core reasons harming animals is acceptable in conservation programs: the primary purpose of conservation is biodiversity protection; conservation is already compassionate to animals; and conservation should prioritize compassion to humans. We used argument analysis to clarify the values and logics underlying the debate around compassionate conservation. We found that objections to compassionate conservation are expressions of human exceptionalism, the view that humans are of a categorically separate and higher moral status than all other species. In contrast, compassionate conservationists believe that conservation should expand its moral community by recognizing all sentient beings as persons. Personhood, in an ethical sense, implies the individual is owed respect and should not be treated merely as a means to other ends. On scientific and ethical grounds, there are good reasons to extend personhood to sentient animals, particularly in conservation. The moral exclusion or subordination of members of other species legitimates the ongoing manipulation and exploitation of the living worlds, the very reason conservation was needed in the first place. Embracing compassion can help dismantle human exceptionalism, recognize nonhuman personhood, and navigate a more expansive moral space.

Blue Restoration – Building Confidence and Overcoming Barriers - Phoebe J. Stewart-Sinclair; Jemma Purandare; Elisa Bayraktarov; Nathan Waltham; Simon Reeves; John Statton; Elizabeth A. Sinclair; Benjamin M. Brown; Zoë I. Shribman; Catherine E. Lovelock (Frontiers in Marine Science, 2020)

Denitrification and the Role of Macrofauna Across Estuarine Gradients in Nutrient and Sediment Loading - Theresa A. O’Meara; Judi E. Hewitt; Simon F. Thrush; Emily J. Douglas; Andrew M. Lohrer (Estuaries and Coasts, 2020)

Comparison of freshwater monitoring approaches: strengths, opportunities, and recommendations - Elaine Ho; Andrew J. Trant; Michelle A. Gray; Simon C. Courtenay (Environmental Monitoring and Assessment, 2020)

Combined Isoflurane-Remifentanil Anaesthesia Permits Resting-State fMRI in Children with Severe Epilepsy and Intellectual Disability - Aaron E. L. Warren; Andrew Davidson; Simon J. Vogrin; A. Simon Harvey; Catherine Bailey; Linda J. Dalic; David F. Abbott; John S. Archer (Brain Topography, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Making Breast Screening Convenient: a Community-Based Breast Screening Event During a Historically Black University’s Homecoming Festivities - Michelle S. Williams; Catherine Young; Shawn McKinney; Odessa S. Simon Hawkins; Cara Roberson; Chigozie Udemgba; Deirdre B. Rogers; Jimmie Wells; Deborah A. Lake; Dorothy Davis; Tiffanie Young; Deborah Donnell; et al. (Journal of Cancer Education, 2020)

Spatiotemporal variations in eruption style, magnitude and vent morphology at Yasur volcano, Vanuatu: insights into the conduit system - B. C. Simons; S. J. Cronin; J. D. Eccles; M. S. Bebbington; A. D. Jolly (Bulletin of Volcanology, 2020)

Competition influences tree growth, but not mortality, across environmental gradients in Amazonia and tropical Africa - Danaë M. A. Rozendaal; Oliver L. Phillips; Simon L. Lewis; Kofi Affum‐Baffoe; Esteban Alvarez-Davila; Ana Andrade; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Timothy R. Baker; Olaf Bánki; Roel J. W. Brienen; José Luis C. Camargo; et al. (Ecology, 2020)
Competition among trees is an important driver of community structure and dynamics in tropical forests. Neighboring trees may impact an individual tree’s growth rate and probability of mortality, but large‐scale geographic and environmental variation in these competitive effects has yet to be evaluated across the tropical forest biome. We quantified effects of competition on tree‐level basal area growth and mortality for trees ≥10‐cm diameter across 151 ~1‐ha plots in mature tropical forests in Amazonia and tropical Africa by developing nonlinear models that accounted for wood density, tree size, and neighborhood crowding. Using these models, we assessed how water availability (i.e., climatic water deficit) and soil fertility influenced the predicted plot‐level strength of competition (i.e., the extent to which growth is reduced, or mortality is increased, by competition across all individual trees). On both continents, tree basal area growth decreased with wood density and increased with tree size. Growth decreased with neighborhood crowding, which suggests that competition is important. Tree mortality decreased with wood density and generally increased with tree size, but was apparently unaffected by neighborhood crowding. Across plots, variation in the plot‐level strength of competition was most strongly related to plot basal area (i.e., the sum of the basal area of all trees in a plot), with greater reductions in growth occurring in forests with high basal area, but in Amazonia, the strength of competition also varied with plot‐level wood density. In Amazonia, the strength of competition increased with water availability because of the greater basal area of wetter forests, but was only weakly related to soil fertility. In Africa, competition was weakly related to soil fertility and invariant across the shorter water availability gradient. Overall, our results suggest that competition influences the structure and dynamics of tropical forests primarily through effects on individual tree growth rather than mortality and that the strength of competition largely depends on environment‐mediated variation in basal area.

No Place Like Home? High Residency and Predictable Seasonal Movement of Whale Sharks Off Tanzania - Christoph A. Rohner; Jesse E. M. Cochran; E. Fernando Cagua; Clare E. M. Prebble; Stephanie K. Venables; Michael L. Berumen; Baraka L. Kuguru; Jason Rubens; Juerg M. Brunnschweiler; Simon J. Pierce (Frontiers in Marine Science, 2020)

A Mass-Balance Tool for Monitoring Potential Dissolved Sulfur Oxidation Risks in Mining Impacted Waters - Kelly Whaley-Martin; Stephanie Marshall; Tara E. Colenbrander Nelson; Lauren Twible; Chad V. Jarolimek; Josh J. King; Simon C. Apte; Lesley A. Warren (Mine Water and the Environment, 2020)

Increased yield and CO 2 sequestration potential with the C 4 cereal Sorghum bicolor cultivated in basaltic rock dust‐amended agricultural soil - Mike E. Kelland; Peter W. Wade; Amy L. Lewis; Lyla L. Taylor; Binoy Sarkar; M. Grace Andrews; Mark R. Lomas; T. E. Anne Cotton; Simon J. Kemp; Rachael H. James; Christopher R. Pearce; Sue E. Hartley; et al. (Global Change Biology, 2020)
Land‐based enhanced rock weathering (ERW) is a biogeochemical carbon dioxide removal (CDR) strategy aiming to accelerate natural geological processes of carbon sequestration through application of crushed silicate rocks, such as basalt, to croplands and forested landscapes. However, the efficacy of the approach when undertaken with basalt, and its potential co‐benefits for agriculture, require experimental and field evaluation. Here we report that amending a UK clay‐loam agricultural soil with a high loading (10 kg/m 2 ) of relatively coarse‐grained crushed basalt significantly increased the yield (21 ± 9.4%, SE ) of the important C 4 cereal Sorghum bicolor under controlled environmental conditions, without accumulation of potentially toxic trace elements in the seeds. Yield increases resulted from the basalt treatment after 120 days without P‐ and K‐fertilizer addition. Shoot silicon concentrations also increased significantly (26 ± 5.4%, SE ), with potential benefits for crop resistance to biotic and abiotic stress. Elemental budgets indicate substantial release of base cations important for inorganic carbon removal and their accumulation mainly in the soil exchangeable pools. Geochemical reactive transport modelling, constrained by elemental budgets, indicated CO 2 sequestration rates of 2–4 t CO 2 /ha, 1–5 years after a single application of basaltic rock dust, including via newly formed soil carbonate minerals whose long‐term fate requires assessment through field trials. This represents an approximately fourfold increase in carbon capture compared to control plant–soil systems without basalt. Our results build support for ERW deployment as a CDR technique compatible with spreading basalt powder on acidic loamy soils common across millions of hectares of western European and North American agriculture.

Assessing ecological function in the context of species recovery - H. Resit Akçakaya; Ana S. L. Rodrigues; David A. Keith; E. J. Milner‐Gulland; Eric W. Sanderson; Simon Hedges; David P. Mallon; Molly K. Grace; Barney Long; Erik Meijaard; P. J. Stephenson (Conservation Biology, 2020)
Species interactions matter to conservation. Setting an ambitious recovery target for a species requires considering the size, density, and demographic structure of its populations such that they fulfill the interactions, roles, and functions of the species in the ecosystems in which they are embedded. A recently proposed framework for an International Union for Conservation of Nature Green List of Species formalizes this requirement by defining a fully recovered species in terms of representation, viability, and functionality. Defining and quantifying ecological function from the viewpoint of species recovery is challenging in concept and application, but also an opportunity to insert ecological theory into conservation practice. We propose 2 complementary approaches to assessing a species’ ecological functions: confirmation (listing interactions of the species, identifying ecological processes and other species involved in these interactions, and quantifying the extent to which the species contributes to the identified ecological process) and elimination (inferring functionality by ruling out symptoms of reduced functionality, analogous to the red‐list approach that focuses on symptoms of reduced viability). Despite the challenges, incorporation of functionality into species recovery planning is possible in most cases and it is essential to a conservation vision that goes beyond preventing extinctions and aims to restore a species to levels beyond what is required for its viability. This vision focuses on conservation and recovery at the species level and sees species as embedded in ecosystems, influencing and being influenced by the processes in those ecosystems. Thus, it connects and integrates conservation at the species and ecosystem levels.

Environmental and Anthropogenic Factors Affect Fish Abundance: Relationships Revealed by Automated Cameras Deployed by Fishers - Michael A. Brooker; Simon de Lestang; David V. Fairclough; Dianne McLean; Dirk Slawinski; Matthew B. Pember; Tim J. Langlois (Frontiers in Marine Science, 2020)

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Exercise training changes mitochondrial function and its vulnerability to reactive oxygen species exposure differently in male and female silver European eels - F. Farhat; B. Simon; A. Amérand; J. Devaux; M. Belhomme; P. Calves; C. Moisan (Environmental Biology of Fishes, 2020)

Conservation assessment of cassava wild relatives in central Brazil - Marcelo F. Simon; Talita S. Reis; J. Moises Mendoza F.; Thalyssa K. M. Arquelão; João B. A. Bringel; Sérgio E. Noronha; Márcio L. L. Martins; Carlos A. S. Ledo; Marcos J. Silva; Alexandre B. Sampaio; Eraldo T. Matricardi; Aldicir Scariot (Biodiversity and Conservation, 2020)

The role of large macrofauna in mediating sediment erodibility across sedimentary habitats - Jenny R. Hillman; Carolyn J. Lundquist; Conrad A. Pilditch; Simon F. Thrush (Limnology and Oceanography, 2020)
Large macrofauna influence sediment erodibility via their activity and presence in the sediment. This article explores how the depletion of large animals from macrobenthic communities influences sediment erodibility across a natural grain size gradient of poorly sorted habitats within an estuary. We sampled seven sites in Mahurangi Harbour, New Zealand, to investigate how heterogeneity within and among these habitats influences sediment stability. We depleted the large macrofauna in the sediment to determine how changes in community structure will affect ecosystem functioning in the context of sediment stability. A core‐based erosion device (EROMES) was used to measure three different parameters associated with sediment resuspension potential: surface erosion threshold ( τ c ; N m −2 ); erosion rate (ER; g m −2 s −1 ); and the subsurface erosion constant ( m e ; g N −1 s −1 ). Multiple regression models were developed for each parameter to identify important drivers of change. Sediment grain size, as a proxy for habitat type, explained 53% of the total variation in both the early surface erosion measures, τ c and ER. Once the surface layers had been eroded, m e was best defined by a site‐specific combination of biological, chemical, and physical variables that explained 40% of the subsurface erosion. Our results demonstrate that at all sites reducing the abundance of large animals within the macrofaunal community contributed to substantial impacts on erosion and thus ecosystem functioning associated with sediment composition and water clarity.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota - Robert A. McConnaughey; Jan G. Hiddink; Simon Jennings; C. Roland Pitcher; Michel J. Kaiser; Petri Suuronen; Marija Sciberras; Adriaan D. Rijnsdorp; Jeremy S. Collie; Tessa Mazor; Ricardo O Amoroso; Ana M. Parma; et al. (Fish and Fisheries, 2020)
Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.

Renal cell carcinoma in young FH mutation carriers: case series and review of the literature - J. A. Hol; M. C. J. Jongmans; A. S. Littooij; R. R. de Krijger; R. P. Kuiper; J. J. T. van Harssel; A. Mensenkamp; M. Simons; G. A. M. Tytgat; M. M. van den Heuvel-Eibrink; M. van Grotel (Familial Cancer, 2020)
Hereditary Leiomyomatosis and Renal Cell Cancer (HLRCC) is an autosomal dominant syndrome caused by heterozygous pathogenic germline variants in the fumarate hydratase ( FH ) gene. It is characterized by cutaneous and uterine leiomyomas and an increased risk of developing renal cell carcinoma (RCC), which is usually adult-onset. HLRCC-related RCC tends to be aggressive and can metastasize even when the primary tumor is small. Data on children and adolescents are scarce. Herein, we report two patients from unrelated Dutch families, with HLRCC-related RCC at the ages of 15 and 18 years, and a third patient with an FH mutation and complex renal cysts at the age of 13. Both RCC’s were localized and successfully resected, and careful MRI surveillance was initiated to monitor the renal cysts. One of the patients with RCC subsequently developed an ovarian Leydig cell tumor. A review of the literature identified 10 previously reported cases of HLRCC-related RCC in patients aged younger than 20 years, five of them presenting with metastatic disease. These data emphasize the importance of recognizing HLRCC in young patients to enable early detection of RCC, albeit rare. They support the recommendations from the 2014 consensus guideline, in which genetic testing for FH mutations, and renal MRI surveillance, is advised for HLRCC family members from the age of 8–10 years onwards.

Strong divergent selection at multiple loci in two closely related species of ragworts adapted to high and low elevations on Mount Etna - Edgar L. Y. Wong; Bruno Nevado; Owen G. Osborne; Alexander S. T. Papadopulos; Jon R. Bridle; Simon J. Hiscock; Dmitry A. Filatov (Molecular Ecology, 2020)
Recently diverged species present particularly informative systems for studying speciation and maintenance of genetic divergence in the face of gene flow. We investigated speciation in two closely related Senecio species, S. aethnensis and S. chrysanthemifolius , which grow at high and low elevations, respectively, on Mount Etna, Sicily and form a hybrid zone at intermediate elevations. We used a newly generated genome‐wide single nucleotide polymorphism (SNP) dataset from 192 individuals collected over 18 localities along an elevational gradient to reconstruct the likely history of speciation, identify highly differentiated SNPs, and estimate the strength of divergent selection. We found that speciation in this system involved heterogeneous and bidirectional gene flow along the genome, and species experienced marked population size changes in the past. Furthermore, we identified highly‐differentiated SNPs between the species, some of which are located in genes potentially involved in ecological differences between species (such as photosynthesis and UV response). We analysed the shape of these SNPs’ allele frequency clines along the elevational gradient. These clines show significantly variable coincidence and concordance, indicative of the presence of multifarious selective forces. Selection against hybrids is estimated to be very strong (0.16–0.78) and one of the highest reported in literature. The combination of strong cumulative selection across the genome and previously identified intrinsic incompatibilities probably work together to maintain the genetic and phenotypic differentiation between these species – pointing to the importance of considering both intrinsic and extrinsic factors when studying divergence and speciation.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Re-emergence of North Atlantic subsurface ocean temperature anomalies in a seasonal forecast system - Jeremy P. Grist; Bablu Sinha; Helene. T. Hewitt; Aurélie Duchez; Craig MacLachlan; Patrick Hyder; Simon A. Josey; Joël J.-M. Hirschi; Adam T. Blaker; Adrian. L. New; Adam A. Scaife; Chris D. Roberts (Climate Dynamics, 2019)

Streamflow response to climate change in the Greater Horn of Africa - Feyera A. Hirpa; Lorenzo Alfieri; Thomas Lees; Jian Peng; Ellen Dyer; Simon J. Dadson (Climatic Change, 2019)
The Greater Horn of Africa region increasingly experiences high risk of water scarcity. A combination of frequent droughts, rapid population growth and rising urbanisation has reduced streamflow and intensified water abstraction, causing water and food shortages. Estimates of future streamflow changes in the region have so far been highly uncertain and evaluations using ground-based measurements are still limited. Here, future streamflow changes are estimated using a distributed hydrological model forced with an ensemble of high-resolution climate simulations produced using the European community Earth-System Model v3.1. The simulated streamflow is evaluated using observed data from 29 stations from river basins across different climate zones in the region. Evaluation results show large sub-regional variations in the performance of simulated streamflow. The sign and magnitude of future streamflow changes vary between climate simulations and river basins, highlighting the uncertainties in the hydrologic projections. Overall, the streamflow projections indicate large (seasonal, long-term mean and extreme) streamflow decreases for all major rivers in Ethiopia and increases in the equatorial parts of the region at the end of the century. The ensemble mean shows a 10 to 25% decrease in the long-term mean flow in Ethiopia and a 10% increase in the equatorial part of the region in 2080s. Similarly, there is a substantial change in high flows in 2080s, with up to − 50% reduction in the northern and 50% increase in the equatorial parts of the region. These findings are critical because the rivers provide water supply to a rapidly changing socio-economy of the region.

Male aggression varies with consortship rate and habitat in a dolphin social network - Rebecca A. Hamilton; Teresa Borcuch; Simon J. Allen; William R. Cioffi; Vanni Bucci; Michael Krützen; Richard C. Connor (Behavioral Ecology and Sociobiology, 2019)

Linking scales and disciplines: an interdisciplinary cross-scale approach to supporting climate-relevant ecosystem management - Christian Berger; Mari Bieri; Karen Bradshaw; Christian Brümmer; Thomas Clemen; Thomas Hickler; Werner Leo Kutsch; Ulfia A. Lenfers; Carola Martens; Guy F. Midgley; Kanisios Mukwashi; Victor Odipo; et al. (Climatic Change, 2019)

Ecology of a polymetallic nodule occurrence gradient: Implications for deep‐sea mining - Erik Simon‐Lledó; Brian J. Bett; Veerle A. I. Huvenne; Timm Schoening; Noelie M. A. Benoist; Daniel O. B. Jones (Limnology and Oceanography, 2019)
Abyssal polymetallic nodule fields constitute an unusual deep‐sea habitat. The mix of soft sediment and the hard substratum provided by nodules increases the complexity of these environments. Hard substrata typically support a very distinct fauna to that of seabed sediments, and its presence can play a major role in the structuring of benthic assemblages. We assessed the influence of seafloor nodule cover on the megabenthos of a marine conservation area (area of particular environmental interest 6) in the Clarion Clipperton Zone (3950–4250 m water depth) using extensive photographic surveys from an autonomous underwater vehicle. Variations in nodule cover (1–20%) appeared to exert statistically significant differences in faunal standing stocks, some biological diversity attributes, faunal composition, functional group composition, and the distribution of individual species. The standing stock of both the metazoan fauna and the giant protists (xenophyophores) doubled with a very modest initial increase in nodule cover (from 1% to 3%). Perhaps contrary to expectation, we detected little if any substantive variation in biological diversity along the nodule cover gradient. Faunal composition varied continuously along the nodule cover gradient. We discuss these results in the context of potential seabed‐mining operations and the associated sustainable management and conservation plans. We note in particular that successful conservation actions will likely require the preservation of areas comprising the full range of nodule cover and not just the low cover areas that are least attractive to mining.

Queen–worker aggression in the facultatively eusocial bee Megalopta genalis - A. R. Smith; M. Simons; V. Bazarko; J. Harach; M. A. Seid (Insectes Sociaux, 2019)

Salinity drives meiofaunal community structure dynamics across the Baltic ecosystem - Elias Broman; Caroline Raymond; Christian Sommer; Jonas S. Gunnarsson; Simon Creer; Francisco J. A. Nascimento (Molecular Ecology, 2019)
Coastal benthic biodiversity is under increased pressure from climate change, eutrophication, hypoxia, and changes in salinity due to increase in river runoff. The Baltic Sea is a large brackish system characterized by steep environmental gradients that experiences all of the mentioned stressors. As such it provides an ideal model system for studying the impact of on‐going and future climate change on biodiversity and function of benthic ecosystems. Meiofauna (animals

Thermal stress induces persistently altered coral reef fish assemblages - James P. W. Robinson; Shaun K. Wilson; Simon Jennings; Nicholas A. J. Graham (Global Change Biology, 2019)
Ecological communities are reorganizing in response to warming temperatures. For continuous ocean habitats this reorganization is characterized by large‐scale species redistribution, but for tropical discontinuous habitats such as coral reefs, spatial isolation coupled with strong habitat dependence of fish species imply that turnover and local extinctions are more significant mechanisms. In these systems, transient marine heatwaves are causing coral bleaching and profoundly altering habitat structure, yet despite severe bleaching events becoming more frequent and projections indicating annual severe bleaching by the 2050s at most reefs, long‐term effects on the diversity and structure of fish assemblages remain unclear. Using a 23‐year time series spanning a thermal stress event, we describe and model structural changes and recovery trajectories of fish communities after mass bleaching. Communities changed fundamentally, with the new emergent communities dominated by herbivores and persisting for >15 years, a period exceeding realized and projected intervals between thermal stress events on coral reefs. Reefs which shifted to macroalgal states had the lowest species richness and highest compositional dissimilarity, whereas reefs where live coral recovered exceeded prebleaching fish richness, but remained dissimilar to prebleaching compositions. Given realized and projected frequencies of bleaching events, our results show that fish communities historically associated with coral reefs will not re‐establish, requiring substantial adaptation by managers and resource users.

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Air-Sea Fluxes With a Focus on Heat and Momentum - Meghan F. Cronin; Chelle L. Gentemann; James Edson; Iwao Ueki; Mark Bourassa; Shannon Brown; Carol Anne Clayson; Chris W. Fairall; J. Thomas Farrar; Sarah T. Gille; Sergey Gulev; Simon A. Josey; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Landscape patterns in top‐down control of decomposition: omnivory disrupts a tropical detrital‐based trophic cascade - Troy N. Simon; Andrew J. Binderup; Alex S. Flecker; James F. Gilliam; Michael C. Marshall; Steven A. Thomas; Joseph Travis; David N. Reznick; Catherine M. Pringle (Ecology, 2019)
Detrital‐based trophic cascades are often considered weak or absent in tropical stream ecosystems because of the prevalence of omnivorous macroconsumers and the dearth of leaf‐shredding insects. In this study, we isolate top‐down effects of three macroconsumer species on detrital processing in headwater streams draining Trinidad's northern mountains. We separated effects of different macroconsumers by experimentally manipulating their temporal access to isolated benthic habitat over the diel cycle. We found no evidence that omnivorous macroconsumers, including a freshwater crab ( Eudaniela garmani ) and guppy ( Poecilia reticulata ), increased leaf decomposition via consumption. By contrast, above a waterfall excluding guppies, the insectivorous killifish, Anablepsoides hartii , reduced the biomass of the leaf‐shredding insect Phylloicus hansoni 4‐fold, which consequently reduced leaf decomposition rates 1.6‐fold. This detrital cascade did not occur below the barrier waterfall, where omnivorous guppies join the assemblage and reduce killifish densities; here killifish had no significant effects on Phylloicus or decomposition rates. These patterns of detrital processing were also observed in upstream–downstream comparisons in a landscape study across paired reaches of six streams. Above waterfalls, where killifish were present, but guppies absent, leaf decomposition rates and Phylloicus biomass were 2.5‐ and ~35‐fold lower, respectively, compared to measurements below waterfalls. Moreover, the strength of top‐down control by killifish is reflected by the 20‐ and 5‐fold reductions in variability (± SE ) surrounding mean Phylloicus biomass and leaf decomposition rates in upstream relative to downstream reaches where no top‐down control was detected. Findings show a clear, detrital‐based trophic cascade among killifish, a leaf‐shredding insect, and leaf decomposition rates. Results also show how omnivorous guppies disrupt this cascade by depressing killifish densities, thereby releasing invertebrate shredders from predation, and significantly increasing decomposition rates. Moreover, this combination of direct and indirect trophic interactions drives patterns in decomposition rates in stream networks at a landscape scale, resulting in significantly lower rates of decomposition above vs. below barrier waterfalls. Our findings reveal that omnivory can result in significant indirect effects on a key ecosystem process, illustrating the importance of these hidden trophic pathways in detrital‐based systems and suggesting that resource control in tropical systems may be even more complex than previously envisioned.

Special issue of theoretical ecology to honor Alan Hastings’ 65th birthday - Stephen P. Ellner; Louis J. Gross; Simon A. Levin; Mark Lewis (Theoretical Ecology, 2019)

The European Association for Clinical Pharmacology and Therapeutics—25 years’ young and going strong - Jamie J. Coleman; Caroline Samer; Markus Zeitlinger; Michiel van Agtmael; Gerard A. Rongen; Pierre Marquet; Tabassome Simon; Donald Singer; Vangelis G. Manolopoulos; Ylva Böttiger (European Journal of Clinical Pharmacology, 2019)

Effect of flowering on physical and mechanical properties of Dendrocalamus brandisii (Munro) Kurz - A. K. Sethy; S. K. Sharma; J. Simon (Journal of the Indian Academy of Wood Science, 2019)

Chitinozoans and scolecodonts from the Silurian and Devonian of Japan - Thijs R. A. Vandenbroucke; Olle Hints; Mark Williams; Simon Wallis; Jules Velleman; Toshiyuki Kurihara; Gengo Tanaka; Toshifumi Komatsu; Peep Männik; David J. Siveter; Tim de Backer (Island Arc, 2019)
Silurian and Devonian chitinozoans and scolecodonts are recorded from strata of the Hida‐Gaien Terrane, central Honshu. Silurian chitinozoans include Eisenackitina , Bursachitina , and the species Angochitina elongata . The latter provides a precise biostratigraphical tie between the Japanese succession and the Type Ludlow Series of the Welsh Borderland, UK, and indicates a Ludlow age (Gorstian or early Ludfordian) for the upper member of the Yoshiki Formation in the Ichinotani Valley. Chitinozoans from other Yoshiki Formation localities contain other specimens of Lagenochitinidae. Scolecodonts are more common than chitinozoans in the palynological residues, but are mostly represented by fragments or minor apparatus elements with a low biostratigraphical value. However, material from the Yoshiki and Fukuji Formations includes several species of Mochtyella as well as representatives of Oenonites , Kettnerites , Lunoprionella , Vistulella ? and possibly other placognath taxa. Scolecodonts are also present in the Silurian Middle Member of the Gionyama Formation, Kyushu, including a well‐preserved jaw of Pistoprion , and fragments of putative Kettnerites and Oenonites . These finds of scolecodonts suggest close similarity in assemblages between Paleozoic polychaete faunas of Japanese terranes and those of Baltica‐Laurentia.

Accounting for interspecific competition and age structure in demographic analyses of density dependence improves predictions of fluctuations in population size - Marlène Gamelon; Stefan J. G. Vriend; Steinar Engen; Frank Adriaensen; André A. Dhondt; Simon R. Evans; Erik Matthysen; Ben C. Sheldon; Bernt‐Erik Sæther (Ecology Letters, 2019)
Understanding species coexistence has long been a major goal of ecology. Coexistence theory for two competing species posits that intraspecific density dependence should be stronger than interspecific density dependence. Great tits and blue tits are two bird species that compete for food resources and nesting cavities. On the basis of long‐term monitoring of these two competing species at sites across Europe, combining observational and manipulative approaches, we show that the strength of density regulation is similar for both species, and that individuals have contrasting abilities to compete depending on their age. For great tits, density regulation is driven mainly by intraspecific competition. In contrast, for blue tits, interspecific competition contributes as much as intraspecific competition, consistent with asymmetric competition between the two species. In addition, including age‐specific effects of intra‐ and interspecific competition in density‐dependence models improves predictions of fluctuations in population size by up to three times.

Gneiss-forming events in the Saglek Block, Labrador; a reappraisal of the Uivak gneiss - Anna Sałacińska; Monika A. Kusiak; Martin J. Whitehouse; Daniel J. Dunkley; Simon A. Wilde; Ross Kielman; Piotr Król (International Journal of Earth Sciences, 2019)

Congo Basin peatlands: threats and conservation priorities - Greta C. Dargie; Ian T. Lawson; Tim J. Rayden; Lera Miles; Edward T. A. Mitchard; Susan E. Page; Yannick E. Bocko; Suspense A. Ifo; Simon L. Lewis (Mitigation and Adaptation Strategies for Global Change, 2019)

DNA metabarcoding—Need for robust experimental designs to draw sound ecological conclusions - Lucie Zinger; Aurélie Bonin; Inger G. Alsos; Miklós Bálint; Holly Bik; Frédéric Boyer; Anthony A. Chariton; Simon Creer; Eric Coissac; Bruce E. Deagle; Marta De Barba; Ian A. Dickie; et al. (Molecular Ecology, 2019)

Environmental influences on stem borer incidence in Australian subtropical Corymbia plantations - Valerie J. Debuse; Tim E. Smith; Chris T. Holloway; Aaron N. Wiegand; Helen F. Nahrung; Simon A. Lawson (Journal of Pest Science, 2019)

Archaean phosphates: a case study of transformation processes in apatite from the Barberton greenstone belt - Łukasz Birski; E. Słaby; R. Wirth; M. Koch-Müller; K. Simon; A. Wudarska; J. Götze; A. Lepland; A. Hofmann; A. Kuras (Contributions to Mineralogy and Petrology, 2019)

The paleobiogeographical significance of the Silurian and Devonian trilobites of Japan - Christopher P. Stocker; Derek J. Siveter; Philip D. Lane; Mark Williams; Tatsuo Oji; Simon R. Wallis; Gengo Tanaka; Toshifumi Komatsu; David J. Siveter; Thijs R. A. Vandenbroucke (Island Arc, 2019)
Six major groups of trilobites from the Silurian and Devonian of Japan are evaluated for their paleobiogeographical signature. Silurian illaenids and scutelluids show four generic‐level and at least two species‐level links with the Australian segment of the Gondwana paleocontinent; encrinurids also indicate two generic‐level links with Australia and also the South China paleocontinent; whilst Devonian phacopids, and possibly proetids, suggest at least two generic‐level links with the North China paleocontinent. These different patterns may reflect the fragmentary biostratigraphical record of Japanese trilobites, but they also appear to reflect paleoenvironmental parameters associated with lithofacies, and paleoecology. Thus, Japanese assemblages of proetids and phacopids occurring in deep‐water clastic lithofacies have counterparts in similar settings in North China, and Japanese scutelluids and illaenids are strongly associated with shallow marine carbonate lithofacies that are similar to those of their occurrences in Australia. Japanese encrinurids occur in carbonate rocks indicative of shallow marine settings in the Kurosegawa Terrane, and they demonstrate a consistent paleobiogeographical affinity with Australia and South China. Larval ecology cannot be directly assessed for Japanese trilobite groups. However, proetids have consistently been shown to have planktonic protaspides, whereas illaenids, scutelluids, and encrinurids have benthic protaspides. Planktonic protaspides would have a greater propensity for distribution in ocean currents than benthic ones, and therefore may be of more limited paleobiogeographical utility. The combined data from the six different groups indicates that the complex paleobiogeographical patterns of the Japanese trilobite assemblages need to be interpreted with caution, and similarity of taxa does not necessarily denote paleogeographical proximity to other regions.

Comparative population genomics confirms little population structure in two commercially targeted carcharhinid sharks - Claudia Junge; Stephen C. Donnellan; Charlie Huveneers; Corey J. A. Bradshaw; Alexis Simon; Michael Drew; Clinton Duffy; Grant Johnson; Geremy Cliff; Matias Braccini; Scott C. Cutmore; Paul Butcher; et al. (Marine Biology, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Neural correlates of emotional valence processing in Parkinson’s disease: dysfunction in the subcortex - Peter T. Bell; Moran Gilat; James M. Shine; Katie L. McMahon; Simon J. G. Lewis; David A. Copland (Brain Imaging and Behavior, 2019)

Predicting Which Species Succeed in Climate-Forced Polar Seas - Simon A. Morley; David K. A. Barnes; Michael J. Dunn (Frontiers in Marine Science, 2019)

Tools to Enrich Vulnerability Assessment and Adaptation Planning for Coastal Communities in Data-Poor Regions: Application to a Case Study in Madagascar - K. L. Cochrane; H. Rakotondrazafy; S. Aswani; T. Chaigneau; N. Downey-Breedt; A. Lemahieu; A. Paytan; G. Pecl; E. Plagányi; E. Popova; E. I. van Putten; Warwick H. H. Sauer; et al. (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Just a FAD ? Ecosystem impacts of tuna purse‐seine fishing associated with fish aggregating devices in the western Pacific Warm Pool Province - Shane P. Griffiths; Valerie Allain; Simon D. Hoyle; Tim A. Lawson; Simon J. Nicol (Fisheries Oceanography, 2019)
The western and central Pacific Ocean supports the world's largest tuna fisheries. Since the 1990s, the purse‐seine fishery has increasingly fished in association with fish aggregating devices ( FAD s), which has increased catches of juvenile bigeye and yellowfin tunas and vulnerable bycatch species (e.g., sharks). This has raised concerns regarding the sustainability of these species’ populations and the supporting ecosystem, but may provide improved food security of Pacific Island nations through utilisation of FAD ‐associated byproduct species (e.g., wahoo). An ecosystem model of the western Pacific Warm Pool Province was used to explore the potential ecological impacts of varying FAD fishing effort (±50% or 100%) over 30 years. The ecosystem has undergone a significant change in structure since 1980 from heavy exploitation of top predators (e.g., tunas) and “fishing up the food web” of high‐trophic‐level non‐target species. The ecosystem appeared resistant to simulated fishing perturbations, with only modest changes ( FAD effort by at least 50% was predicted to increase the biomass of tuna species and sharks and return the ecosystem structure to a pre‐industrial‐fishing state within 10 years. Spatial disaggregation of the model and integration of economic information are recommended to better capture ecological and economic changes that may result from fishing and/or climate impacts and to develop appropriate management measures in response.

Modelling glacial lake outburst flood impacts in the Bolivian Andes - Ioannis Kougkoulos; Simon J. Cook; Laura A. Edwards; Leon J. Clarke; Elias Symeonakis; Jason M. Dortch; Kathleen Nesbitt (Natural Hazards, 2018)

Simulation-based suggestions to improve ibuprofen dosing for patent ductus arteriosus in preterm newborns - Robert B. Flint; Rob ter Heine; Edwin Spaans; David M. Burger; Johan C. A. de Klerk; Karel Allegaert; Catherijne A. J. Knibbe; Sinno H. P. Simons (European Journal of Clinical Pharmacology, 2018)

Storylines: an alternative approach to representing uncertainty in physical aspects of climate change - Theodore G. Shepherd; Emily Boyd; Raphael A. Calel; Sandra C. Chapman; Suraje Dessai; Ioana M. Dima-West; Hayley J. Fowler; Rachel James; Douglas Maraun; Olivia Martius; Catherine A. Senior; Adam H. Sobel; et al. (Climatic Change, 2018)

Progressive microstructural changes of the occipital cortex in Huntington’s disease - Omar F. F. Odish; Robert H. A. M. Reijntjes; Simon J. A. van den Bogaard; Raymund A. C. Roos; Alexander Leemans (Brain Imaging and Behavior, 2018)

Further spectral and chromatographic studies of ambergris - Steven J. Rowland; Paul A. Sutton; Simon T. Belt; Vera Fitzsimmons-Thoss; Alan G. Scarlett (Natural Product Research, 2018)

Response of cell-wall composition and RNA-seq transcriptome to methyl-jasmonate in Brachypodium distachyon callus - Lucy S. Hyde; Till K. Pellny; Jackie Freeman; Louise V. Michaelson; Rachael Simister; Simon J. McQueen-Mason; Rowan A. C. Mitchell (Planta, 2018)

Sedimentary Environment Influences Ecosystem Response to Nutrient Enrichment - Emily J. Douglas; Conrad A. Pilditch; Andrew M. Lohrer; Candida Savage; Louis A. Schipper; Simon F. Thrush (Estuaries and Coasts, 2018)

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Effects of program scale-up on time to resolution for patients with abnormal screening mammography results - Simon Craddock Lee; Robin T. Higashi; Joanne M. Sanders; Hong Zhu; Stephen J. Inrig; Caroline Mejias; Keith E. Argenbright; Jasmin A. Tiro (Cancer Causes & Control, 2018)

Climate change alterations to ecosystem dominance: how might sponge‐dominated reefs function? - James J. Bell; Alberto Rovellini; Simon K. Davy; Michael W. Taylor; Elizabeth A. Fulton; Matthew R. Dunn; Holly M. Bennett; Nora M. Kandler; Heidi M. Luter; Nicole S. Webster (Ecology, 2018)
Anthropogenic stressors are impacting ecological systems across the world. Of particular concern are the recent rapid changes occurring in coral reef systems. With ongoing degradation from both local and global stressors, future reefs are likely to function differently from current coral‐dominated ecosystems. Determining key attributes of future reef states is critical to reliably predict outcomes for ecosystem service provision. Here we explore the impacts of changing sponge dominance on coral reefs. Qualitative modelling of reef futures suggests that changing sponge dominance due to increased sponge abundance will have different outcomes for other trophic levels compared with increased sponge dominance as a result of declining coral abundance. By exploring uncertainty in the model outcomes we identify the need to (1) quantify changes in carbon flow through sponges, (2) determine the importance of food limitation for sponges, (3) assess the ubiquity of the recently described “sponge loop,” (4) determine the competitive relationships between sponges and other benthic taxa, particularly algae, and (5) understand how changing dominance of other organisms alters trophic pathways and energy flows through ecosystems. Addressing these knowledge gaps will facilitate development of more complex models that assess functional attributes of sponge‐dominated reef ecosystems.

Sedimentary macrofossil records reveal ecological change in English lakes: implications for conservation - Helen Bennion; Carl D. Sayer; Stewart J. Clarke; Thomas A. Davidson; Neil L. Rose; Ben Goldsmith; Ruth Rawcliffe; Amy Burgess; Gina Clarke; Simon Turner; Emma Wiik (Journal of Paleolimnology, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Genetic diversity through time and space: diversity and demographic history from natural history specimens and serially sampled contemporary populations of the threatened Gouldian finch (Erythrura gouldiae) - Peri E. Bolton; Lee A. Rollins; James Brazill-Boast; Kimberley L. Maute; Sarah Legge; Jeremy J. Austin; Simon C. Griffith (Conservation Genetics, 2018)

Ocean acidification in New Zealand waters: trends and impacts - Cliff S. Law; James J. Bell; Helen C. Bostock; Chris E. Cornwall; Vonda J. Cummings; Kim Currie; Simon K. Davy; Malindi Gammon; Christopher D. Hepburn; Catriona L. Hurd; Miles Lamare; Sara E. Mikaloff‐Fletcher; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
The threat posed by ocean acidification (OA) to the diversity and productivity of New Zealand marine ecosystems is assessed in a synthesis of published trends and impacts. A 20‐year time series in Subantarctic water, and a national coastal monitoring programme, provide insight into pH variability, and context for experimental design, modelling and projections. A review of the potential impact of changes in the carbonate system on the major phyla in New Zealand waters confirms international observations that calcifying organisms, and particularly their early life‐history stages, are vulnerable. The synthesis considers ecosystem and socio‐economic impacts, and identifies current knowledge gaps and future research directions, including mechanistic studies of OA sensitivity. Advanced ecosystem models of OA, that incorporate the indirect effects of OA and interactions with other climate stressors, are required for robust projection of the future status of New Zealand marine ecosystems.

A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack - Yves Basset; Chris Dahl; Richard Ctvrtecka; Sofia Gripenberg; Owen T. Lewis; Simon T. Segar; Petr Klimes; Héctor Barrios; John W. Brown; Sarayudh Bunyavejchewin; Buntika A. Butcher; Anthony I. Cognato; et al. (Journal of Biogeography, 2018)
Aim Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location Three Forest GEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods We surveyed 1,186 plant species and reared 1.1 ton of seeds/fruits that yielded 80,600 insects representing at least 1,678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.

Truly sedentary? The multi-range tactic as a response to resource heterogeneity and unpredictability in a large herbivore - Ophélie Couriot; A. J. Mark Hewison; Sonia Saïd; Francesca Cagnacci; Simon Chamaillé-Jammes; John D. C. Linnell; Atle Mysterud; Wibke Peters; Ferdinando Urbano; Marco Heurich; Petter Kjellander; Sandro Nicoloso; et al. (Oecologia, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Selectivity underlies the dissociation between seasonal prey availability and prey consumption in a generalist predator - Thomas D. Whitney; Michael I. Sitvarin; Edward A. Roualdes; Simon J. Bonner; James D. Harwood (Molecular Ecology, 2018)
Generalist predators are capable of selective foraging, but are predicted to feed in close proportion to prey availability to maximize energetic intake especially when overall prey availability is low. By extension, they are also expected to feed in a more frequency‐dependent manner during winter compared to the more favourable foraging conditions during spring, summer and fall seasons. For 18 months, we observed the foraging patterns of forest‐dwelling wolf spiders from the genus Schizocosa (Araneae: Lycosidae) using PCR ‐based gut‐content analysis and simultaneously monitored the activity densities of two common prey: springtails (Collembola) and flies (Diptera). Rates of prey detection within spider guts relative to rates of prey collected in traps were estimated using Roualdes’ c st model and compared using various linear contrasts to make inferences pertaining to seasonal prey selectivity. Results indicated spiders foraged selectively over the course of the study, contrary to predictions derived from optimal foraging theory. Even during winter, with overall low prey densities, the relative rates of predation compared to available prey differed significantly over time and by prey group. Moreover, these spiders appeared to diversify their diets; the least abundant prey group was consistently overrepresented in the diet within a given season. We suggest that foraging in generalist predators is not necessarily restricted to frequency dependency during winter. In fact, foraging motives other than energy maximization, such as a more nutrient‐focused strategy, may also be optimal for generalist predators during prey‐scarce winters.

Prospects for seasonal forecasting of iceberg distributions in the North Atlantic - Robert Marsh; Grant Bigg; Yifan Zhao; Matthew J. Martin; Jeffrey R. Blundell; Simon A. Josey; Edward Hanna; Vladimir Ivchenko (Natural Hazards, 2018)

Biogeographic history of subterranean isopods from groundwater calcrete islands in Western Australia - Mohammad Javidkar; Steven J. B. Cooper; William F. Humphreys; Rachael A. King; Simon Judd; Andrew D. Austin (Zoologica Scripta, 2018)
Groundwater calcretes in arid central Western Australia contain a diverse invertebrate groundwater fauna (stygofauna). Surveys have uncovered a diverse oniscidean isopod subterranean fauna above the water table (troglofauna), including species of a recently described genus Paraplatyarthrus . The aim of this study was to investigate the biogeographic history of Paraplatyarthrus and the timing of transitions from surface to subterranean habitats. Phylogenetic relationships among the isopod troglofauna from 11 groundwater calcretes along three palaeodrainage systems were assessed using one mitochondrial gene, cytochrome c oxidase subunit 1 ( COI ) , and two nuclear markers, lysyl‐ tRNA synthetase (Lys RS ) and 18S rRNA ( 18S ) genes. Phylogenetic analyses revealed multiple sister lineage relationships between troglophile and troglobite lineages and evidence for divergent mt DNA lineages within species, providing a range of nodes for dating evolutionary transitions from surface to subterranean habitats. Relaxed molecular clock analyses provided evidence that evolutionary transitions from surface to subterranean environments took place between 13.3 and 1.75 million years ago, coinciding with the onset of aridification of Australia from the late Tertiary. In cases where groundwater calcretes contained multiple species, the taxa were not closely related phylogenetically, suggesting that these calcretes were independently colonised by multiple ancestral species. The study further confirmed the role of late/post‐Miocene aridification as a key driver of the evolution of subterranean invertebrates in the calcrete islands of Western Australia, supporting the climatic relict hypothesis. Troglobites most likely evolved from the troglophile ancestors that were capable of dispersal among, and active colonisation of, calcretes.

Effect of diets supplemented with feed additives on growth, feed utilization, survival, body composition and intestinal bacterial load of early weaning European seabass, Dicentrarchus labrax post-larvae - A. M. Goda; E. A. Omar; T. M. Srour; A. M. Kotiet; E. El-Haroun; Simon J. Davies (Aquaculture International, 2018)

Scale-specific drivers of kelp forest communities - Thomas Lamy; Daniel C. Reed; Andrew Rassweiler; David A. Siegel; Li Kui; Tom W. Bell; Rachel D. Simons; Robert J. Miller (Oecologia, 2018)

Automated parameter tuning applied to sea ice in a global climate model - Lettie A. Roach; Simon F. B. Tett; Michael J. Mineter; Kuniko Yamazaki; Cameron D. Rae (Climate Dynamics, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Shelter use by large reef fishes: long-term occupancy and the impacts of disturbance - Joanna A. Khan; Christopher H. R. Goatley; Simon J. Brandl; Sterling B. Tebbett; David R. Bellwood (Coral Reefs, 2017)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Macrofaunal Functional Diversity Provides Resilience to Nutrient Enrichment in Coastal Sediments - Emily J. Douglas; Conrad A. Pilditch; Casper Kraan; Louis A. Schipper; Andrew M. Lohrer; Simon F. Thrush (Ecosystems, 2017)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Mechanisms of hepatotoxicity associated with the monocyclic β-lactam antibiotic BAL30072 - Franziska Paech; Simon Messner; Jochen Spickermann; Mathias Wind; Anne-Hortense Schmitt-Hoffmann; Anne Therese Witschi; Brett A. Howell; Rachel J. Church; Jeff Woodhead; Marc Engelhardt; Stephan Krähenbühl; Martina Maurer (Archives of Toxicology, 2017)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Quantifying deformation in North Borneo with GPS - Mohamad Asrul Mustafar; Wim J. F. Simons; Felix Tongkul; Chalermchon Satirapod; Kamaludin Mohd Omar; Pieter N. A. M. Visser (Journal of Geodesy, 2017)

Characterisation of Peptide5 systemic administration for treating traumatic spinal cord injured rats - Yilin Mao; Tara Nguyen; Ryan S. Tonkin; Justin G. Lees; Caitlyn Warren; Simon J. O’Carroll; Louise F. B. Nicholson; Colin R. Green; Gila Moalem-Taylor; Catherine A. Gorrie (Experimental Brain Research, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Cis ‐regulatory evolution in a wild primate: Infection‐associated genetic variation drives differential expression of MHC ‐ DQA 1 in vitro - Noah D. Simons; Geeta N. Eick; Maria J. Ruiz‐Lopez; Patrick A. Omeja; Colin A. Chapman; Tony L. Goldberg; Nelson Ting; Kirstin N. Sterner (Molecular Ecology, 2017)
Few studies have combined genetic association analyses with functional characterization of infection‐associated SNP s in natural populations of nonhuman primates. Here, we investigate the relationship between host genetic variation, parasitism and natural selection in a population of red colobus ( Procolobus rufomitratus tephrosceles ) in Kibale National Park, Uganda. We collected parasitological, cellular and genomic data to test the following hypotheses: (i) MHC ‐ DQA 1 regulatory genetic variation is associated with control of whipworm ( Trichuris ) infection in a natural population of red colobus; (ii) infection‐associated SNP s are functional in driving differential gene expression in vitro; and (iii) balancing selection has shaped patterns of variation in the MHC ‐ DQA 1 promoter. We identified two SNP s in the MHC ‐ DQA 1 promoter, both in transcription factor binding sites, and both of which are associated with decreased control of Trichuris infection. We characterized the function of both SNP s by testing differences in gene expression between the two alleles of each SNP in two mammalian cell lines. Alleles of one of the SNP s drove differential gene expression in both cell lines, while the other SNP drove differences in expression in one of the cell lines. Additionally, we found evidence of balancing selection acting on the MHC ‐ DQA 1 promoter, including extensive trans‐species polymorphisms between red colobus and other primates, and an excess of intermediate‐frequency alleles relative to genome‐wide, coding and noncoding RAD seq data. Our data suggest that balancing selection provides adaptive regulatory flexibility that outweighs the consequences of increased parasite infection intensity in heterozygotes.

CO2 fluid inclusions in Jack Hills zircons - Martina Menneken; Thorsten Geisler; Alexander A. Nemchin; Martin J. Whitehouse; Simon A. Wilde; Biliana Gasharova; Robert T. Pidgeon (Contributions to Mineralogy and Petrology, 2017)

Intercomparison and validation of the mixed layer depth fields of global ocean syntheses - Takahiro Toyoda; Yosuke Fujii; Tsurane Kuragano; Masafumi Kamachi; Yoichi Ishikawa; Shuhei Masuda; Kanako Sato; Toshiyuki Awaji; Fabrice Hernandez; Nicolas Ferry; Stéphanie Guinehut; Matthew J. Martin; et al. (Climate Dynamics, 2017)

Steric sea level variability (1993–2010) in an ensemble of ocean reanalyses and objective analyses - Andrea Storto; Simona Masina; Magdalena Balmaseda; Stéphanie Guinehut; Yan Xue; Tanguy Szekely; Ichiro Fukumori; Gael Forget; You-Soon Chang; Simon A. Good; Armin Köhl; Guillaume Vernieres; et al. (Climate Dynamics, 2017)

Utility of spherical human liver microtissues for prediction of clinical drug-induced liver injury - William R. Proctor; Alison J. Foster; Jennifer Vogt; Claire Summers; Brian Middleton; Mark A. Pilling; Daniel Shienson; Monika Kijanska; Simon Ströbel; Jens M. Kelm; Paul Morgan; Simon Messner; et al. (Archives of Toxicology, 2017)

Stratigraphy, age and correlation of two widespread Late Holocene tephras preserved within Lake Kutubu, Southern Highlands Province, Papua New Guinea - Larissa Schneider; Brent V. Alloway; Russell J. Blong; Geoff S. Hope; Stewart J. Fallon; Colin F. Pain; William A. Maher; Simon G. Haberle (Journal of Quaternary Science, 2017)
Sediment cores were retrieved from Lake Kutubu, the largest upland lake in Papua New Guinea, to assess palaeoenvironmental baselines. Two prominent tephra layers were encountered within the cores. Using a combination of core stratigraphy, sediment properties and geochemical characterization (electron microprobe and laser ablation inductively coupled‐plasma mass spectrometry techniques) we were able to correlate these tephras with Tibito and Olgaboli tephras, both previously described at adjacent distal localities. Glass shard compositional data of Tibito tephra from Lake Kutubu, Kuk swamp and from proximal volcaniclastic successions from Long Island are indistinguishable and this similarity strongly supports Long Island as the eruptive source. For Olgaboli tephra, the location of its eruptive source is less certain but the glass shard compositional data indicate a Karkar Island source. The occurrence of Tibito and Olgaboli tephras in Lake Kubutu sediments extends their known distributions further south‐west into the southern Highlands region and affirms their importance as inter‐regional stratigraphic markers, of late Holocene age, that have considerable potential for use in future palaeoenvironmental, archaeological and volcanic hazard and/or impact studies. Copyright © 2017 John Wiley & Sons, Ltd.

Resistin and NGAL are associated with inflammatory response, endothelial activation and clinical outcomes in sepsis - Stephen P. J. Macdonald; Erika Bosio; Claire Neil; Glenn Arendts; Sally Burrows; Lisa Smart; Simon G. A. Brown; Daniel M. Fatovich (Inflammation Research, 2017)

Diets and trophic guilds of small fishes from coastal marine habitats in western Taiwan - J. P. Egan; U.‐S. Chew; C.‐H. Kuo; V. Villarroel‐Diaz; P. J. Hundt; N. G. Iwinski; M. P. Hammer; A. M. Simons (Journal of Fish Biology, 2017)
The diets and trophic guilds of small fishes were examined along marine sandy beaches and in estuaries at depths L S ) in seven species and at the assemblage level and negatively correlated with L S in a single detritivorous species. The diet data and trophic guild scheme produced by this study contribute to an understanding of coastal marine food webs and can inform ecosystem‐based fisheries management.

Past, present and future refugia for Tasmania's palaeoendemic flora - Karel Mokany; Greg J. Jordan; Thomas D. Harwood; Peter A. Harrison; Gunnar Keppel; Louise Gilfedder; Oberon Carter; Simon Ferrier (Journal of Biogeography, 2017)
Aim Refugia under past climates have been important in structuring current patterns in diversity, while refugia under anthropogenic climate change will likely be important in retaining this diversity and shaping new patterns. However, few studies have examined the congruence of past, present and future refugia, or the spatiotemporal connectivity of these refugia. Our aim was to test the extent of overlap of refugia under Last Glacial Maximum ( LGM ), present (2015) and likely future climates (2100), for Tasmania's palaeoendemic flora. We then aimed to identify areas of high spatiotemporal refugia connectivity, as priority areas for conservation and management. Location Tasmania, Australia. Methods We developed and applied a new community‐level approach to identifying refugia, based on generalized dissimilarity modelling of compositional turnover and a set of reference sites with known biodiversity value. Using these projections of palaeoendemic plant refugia for past, present and future climates, we developed and applied a second approach to quantify the level of connectivity of these refugia over space and time. Results Although there was large overlap (85%) between current and future climates in the distribution of the highest value palaeoendemic refugia, the small congruence of these areas with refugia at the LGM resulted in only a small area ( c . 9 km 2 ) of persistent high value refugia over all three time periods. Despite this, our spatiotemporal analysis identified several areas of high connectivity in refugial environments for Tasmania's palaeoendemic flora over time. Main conclusions The community‐level approaches we demonstrate here to quantify refugia and their spatiotemporal connectivity have the potential to advance our understanding of biodiversity dynamics, particularly for taxonomic groups that are species‐rich, poorly studied or comprised of many rare species, where species‐level approaches are less suitable.

Characterisation of the DAACS Family Escherichia coli Glutamate/Aspartate-Proton Symporter GltP Using Computational, Chemical, Biochemical and Biophysical Methods - Moazur Rahman; Fouzia Ismat; Li Jiao; Jocelyn M. Baldwin; David J. Sharples; Stephen A. Baldwin; Simon G. Patching (The Journal of Membrane Biology, 2017)

Exome analysis of Smith–Magenis-like syndrome cohort identifies de novo likely pathogenic variants - Seth I. Berger; Carla Ciccone; Karen L. Simon; May Christine Malicdan; Thierry Vilboux; Charles Billington; Roxanne Fischer; Wendy J. Introne; Andrea Gropman; Jan K. Blancato; James C. Mullikin; William A. Gahl; et al. (Human Genetics, 2017)

Normal radial migration and lamination are maintained in dyslexia-susceptibility candidate gene homolog Kiaa0319 knockout mice - Isabel Martinez-Garay; Luiz G. Guidi; Zoe G. Holloway; Melissa A. G. Bailey; Daniel Lyngholm; Tomasz Schneider; Timothy Donnison; Simon J. B. Butt; Anthony P. Monaco; Zoltán Molnár; Antonio Velayos-Baeza (Brain Structure and Function, 2017)

Factors driving the variability in diving and movement behavior of migrating humpback whales ( Megaptera novaeangliae ): Implications for anthropogenic disturbance studies - Ailbhe S. Kavanagh; Michael J. Noad; Simon P. Blomberg; Anne W. Goldizen; Eric Kniest; Douglas H. Cato; Rebecca A. Dunlop (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) undertake one of the longest migrations of any animal and while on a broad‐scale this journey appears direct, on a fine‐scale, behaviors associated with socializing and breeding are regularly observed. However, little is known about which social and environmental factors influence behavior during this time. Here we examined the effect of multiple factors on the movement (speed and course) and diving behavior (dive and surfacing duration) of humpback whales during migration off the eastern coast of Australia. Focal data (202 h) were collected on 94 different whale groups with simultaneous social and environmental context data. The environmental factors water depth and wind speed were found to be important predictors of dive and movement behavior, whereas social factors were less influential at this site. Groups tended to dive for longer with increased water depth but traveled more slowly in increasing wind speeds. These baseline studies are crucial when examining the effect of anthropogenic disturbance. Determining which natural factors significantly affect behavior ensures any observed behavioral changes are correctly attributed to the disturbance and are not a result of other factors. In addition, any responses observed can be put into biological context and their relative magnitude determined.

Metabolic Profiling of Human Long-Term Liver Models and Hepatic Clearance Predictions from In Vitro Data Using Nonlinear Mixed-Effects Modeling - Nicole A. Kratochwil; Christophe Meille; Stephen Fowler; Florian Klammers; Aynur Ekiciler; Birgit Molitor; Sandrine Simon; Isabelle Walter; Claudia McGinnis; Johanna Walther; Brian Leonard; Miriam Triyatni; et al. (The AAPS Journal, 2017)

Modular growth vessels for the cultivation of the cyanobacterium Synechococcus sp. PCC 7002 - Simon A. Jackson; Julian J. Eaton‐Rye (New Zealand Journal of Botany, 2017)
Synechococcus sp. PCC 7002 is a euryhaline cyanobacterium that serves as a model organism for studies of photosynthesis and cellular metabolism. At high light intensity Synechococcus sp. PCC 7002 exhibits a fast growth rate and rapid biomass accumulation, making it an ideal candidate for the production of biofuels and commercially valuable secondary metabolites. To fully realise the production potential for this cyanobacterium a system is required to maintain axenic cultures under optimal growth conditions. We have designed and constructed two sizes of modular culture vessel systems, designed specifically to meet the abnormally high light penetration requirements of Synechococcus sp. PCC 7002. The smaller volume culture vessels are best suited to phenotype analysis, allowing multiple candidate strains to be screened simultaneously, whereas the larger vessels are designed to facilitate higher biomass production.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Prefrontal activation may predict working-memory training gain in normal aging and mild cognitive impairment - Anouk Vermeij; Roy P. C. Kessels; Linda Heskamp; Esther M. F. Simons; Paul L. J. Dautzenberg; Jurgen A. H. R. Claassen (Brain Imaging and Behavior, 2017)

Spatial Distribution and Residency of Green and Loggerhead Sea Turtles Using Coastal Reef Habitats in Southern Mozambique - Jessica L. Williams; Simon J. Pierce; Chris A. Rohner; Mariana M. P. B. Fuentes; Mark Hamann (Frontiers in Marine Science, 2017)

Evidence for the functions of surface‐active behaviors in humpback whales ( Megaptera novaeangliae ) - Ailbhe S. Kavanagh; Kylie Owen; Michael J. Williamson; Simon P. Blomberg; Michael J. Noad; Anne W. Goldizen; Eric Kniest; Douglas H. Cato; Rebecca A. Dunlop (Marine Mammal Science, 2017)
As part of their social sound repertoire, migrating humpback whales ( Megaptera novaeangliae ) perform a large variety of surface‐active behaviors, such as breaching and repetitive slapping of the pectoral fins and tail flukes; however, little is known about what factors influence these behaviors and what their functions might be. We investigated the potential functions of surface‐active behaviors in humpback whale groups by examining the social and environmental contexts in which they occurred. Focal observations on 94 different groups of whales were collected in conjunction with continuous acoustic monitoring, and data on the social and environmental context of each group. We propose that breaching may play a role in communication between distant groups as the probability of observing this behavior decreased significantly when the nearest whale group was within 4,000 m compared to beyond 4,000 m. Involvement in group interactions, such as the splitting of a group or a group joining with other whales, was an important factor in predicting the occurrence of pectoral, fluke, and peduncle slapping, and we suggest that they play a role in close‐range or within‐group communication. This study highlights the potentially important and diverse roles of surface‐active behaviors in the communication of migrating humpback whales.

Plenty more fish in the sea? - Reg A Watson; Tony J Pitcher; Simon Jennings (Fish and Fisheries, 2017)
Only in the last century did humans overwhelmingly accept that fisheries resources are finite. Consequently, ‘there are more fish still in the sea than ever came out of it’ served as a popular metaphor for unbounded expectations for half a millennium, expectations that also extended to use of the planet in general. By reconstructing historical fishing back 1200 years, we identify when this metaphor actually ceased to be true. For some of our most important stocks, it has not been true for centuries, although surprisingly, for fishes globally, it applied until the last century. We demonstrate, however, that there can still be ‘plenty more fish in the sea’ and that with effective management they provide a continuous flow of benefits for our future.

Human centromere repositioning within euchromatin after partial chromosome deletion - Lori L. Sullivan; Kristin A. Maloney; Aaron J. Towers; Simon G. Gregory; Beth A. Sullivan (Chromosome Research, 2016)

Microsatellite discovery in an insular amphibian (Grandisonia alternans) with comments on cross-species utility and the accuracy of locus identification from unassembled Illumina data - Eleanor A. S. Adamson; Anwesha Saha; Simon T. Maddock; Ronald A. Nussbaum; David J. Gower; Jeffrey W. Streicher (Conservation Genetics Resources, 2016)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Rectal prolapse in Winnie mice with spontaneous chronic colitis: changes in intrinsic and extrinsic innervation of the rectum - Ahmed A. Rahman; Ainsley M. Robinson; Simon J. H. Brookes; Rajaraman Eri; Kulmira Nurgali (Cell and Tissue Research, 2016)

Handaxe and non‐handaxe assemblages during Marine Isotope Stage 11 in northern Europe: recent investigations at Barnham, Suffolk, UK - Nick Ashton; Simon G. Lewis; Simon A. Parfitt; Rob J. Davis; Chris Stringer (Journal of Quaternary Science, 2016)
Britain has an important geological, environmental and archaeological record for Marine Isotope Stage 11 (MIS 11), which makes a major contribution to understanding of the human occupation of northern Europe. New fieldwork at Barnham, Suffolk, UK, has identified through improved geological resolution the change in assemblages from simple core and flake working to those with handaxe technology. The two assemblages are argued to reflect distinct human populations from different source areas in Europe. The paper examines the European record and puts forward a new model of how the complex mosaic of lithic assemblages reflects local, habitual practices during stable environments, but changes in climate and environment led to larger scale shifts in population, resulting in new human groups arriving in Britain.

Habitat availability and geographic isolation as potential drivers of population structure in an oceanic dolphin in the Southwest Indian Ocean - Amélia Viricel; Benoit Simon-Bouhet; Laura Ceyrac; Violaine Dulau-Drouot; Per Berggren; Omar A. Amir; Narriman S. Jiddawi; Philippe Mongin; Jeremy J. Kiszka (Marine Biology, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Mulualem T. Kassa; Sabrina Haas; Edgar Schliephake; Clare Lewis; Frank M. You; Curtis J. Pozniak; Ilona Krämer; Dragan Perovic; Andrew G. Sharpe; Pierre R. Fobert; Michael Koch; Ian L. Wise; et al. (Theoretical and Applied Genetics, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Brain white matter structure and information processing speed in healthy older age - Ksenia A. Kuznetsova; Susana Muñoz Maniega; Stuart J. Ritchie; Simon R. Cox; Amos J. Storkey; John M. Starr; Joanna M. Wardlaw; Ian J. Deary; Mark E. Bastin (Brain Structure and Function, 2016)

Mesophotic fishes of the Abrolhos Shelf, the largest reef ecosystem in the South Atlantic - T. Simon; H. T. Pinheiro; R. L. Moura; A. Carvalho‐Filho; L. A. Rocha; A. S. Martins; E. Mazzei; R. B. Francini‐Filho; G. M. Amado‐Filho; J.‐C. Joyeux (Journal of Fish Biology, 2016)
Fishes inhabiting rhodolith beds and reefs at mesophotic depths on the Abrolhos Shelf, which encompasses the largest and richest coral reef formation in the South Atlantic Ocean, were assessed through technical diving and remotely operated vehicles ( ROVs ). A total of 74 fish species were recorded, including at least one new species, one new record for the south‐western Atlantic and six new records for the Abrolhos region. Overfishing, mining and port activities are already threatening many endangered and commercially important species recorded on the mesophotic reefs of Abrolhos Shelf, and the establishment of marine protected areas and off‐reserve fisheries regulations are urgently needed.

A mouse model of the 15q13.3 microdeletion syndrome shows prefrontal neurophysiological dysfunctions and attentional impairment - Simon R. O. Nilsson; Pau Celada; Kim Fejgin; Jonas Thelin; Jacob Nielsen; Noemí Santana; Christopher J. Heath; Peter H. Larsen; Vibeke Nielsen; Brianne A. Kent; Lisa M. Saksida; Tine B. Stensbøl; et al. (Psychopharmacology, 2016)

Roles of nitrogen and phosphorus in growth responses and toxin production (using LC-MS/MS) of tropical Microcystis ichthyoblabe and M. flos-aquae - Maxine A. D. Mowe; Feras Abbas; Cristina Porojan; Simon M. Mitrovic; Richard P. Lim; Ambrose Furey; Darren C. J. Yeo (Journal of Applied Phycology, 2016)

Formal modelling of predator preferences using molecular gut-content analysis - Edward A. Roualdes; Simon J. Bonner; Thomas D. Whitney; James D. Harwood (Environmental and Ecological Statistics, 2016)

Genetic isolation between coastal and fishery‐impacted, offshore bottlenose dolphin ( Tursiops spp.) populations - Simon J. Allen; Kate A. Bryant; Robert H. S. Kraus; Neil R. Loneragan; Anna M. Kopps; Alexander M. Brown; Livia Gerber; Michael Krützen (Molecular Ecology, 2016)
The identification of species and population boundaries is important in both evolutionary and conservation biology. In recent years, new population genetic and computational methods for estimating population parameters and testing hypotheses in a quantitative manner have emerged. Using a Bayesian framework and a quantitative model‐testing approach, we evaluated the species status and genetic connectedness of bottlenose dolphin ( Tursiops spp.) populations off remote northwestern Australia, with a focus on pelagic ‘offshore’ dolphins subject to incidental capture in a trawl fishery. We analysed 71 dolphin samples from three sites beyond the 50 m depth contour (the inshore boundary of the fishery) and up to 170 km offshore, including incidentally caught and free‐ranging individuals associating with trawl vessels, and 273 dolphins sampled at 12 coastal sites inshore of the 50 m depth contour and within 10 km of the coast. Results from 19 nuclear microsatellite markers showed significant population structure between dolphins from within the fishery and coastal sites, but also among dolphins from coastal sites, identifying three coastal populations. Moreover, we found no current or historic gene flow into the offshore population in the region of the fishery, indicating a complete lack of recruitment from coastal sites. Mitochondrial DNA corroborated our findings of genetic isolation between dolphins from the offshore population and coastal sites. Most offshore individuals formed a monophyletic clade with common bottlenose dolphins ( T. truncatus ), while all 273 individuals sampled coastally formed a well‐supported clade of Indo‐Pacific bottlenose dolphins ( T. aduncus ). By including a quantitative modelling approach, our study explicitly took evolutionary processes into account for informing the conservation and management of protected species. As such, it may serve as a template for other, similarly inaccessible study populations.

The microRNA-29 family in cartilage homeostasis and osteoarthritis - Linh T. T. Le; Tracey E. Swingler; Natalie Crowe; Tonia L. Vincent; Matthew J. Barter; Simon T. Donell; Anne M. Delany; Tamas Dalmay; David A. Young; Ian M. Clark (Journal of Molecular Medicine, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

A combined pharmacokinetic/pharmacodynamic model of levodopa motor response and dyskinesia in Parkinson’s disease patients - N. Simon; F. Viallet; A. Boulamery; A. Eusebio; D. Gayraud; J-P. Azulay (European Journal of Clinical Pharmacology, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Why is the South Orkney Island shelf (the world's first high seas marine protected area) a carbon immobilization hotspot? - David K. A. Barnes; Louise Ireland; Oliver T. Hogg; Simon Morley; Peter Enderlein; Chester J. Sands (Global Change Biology, 2016)
The Southern Ocean archipelago, the South Orkney Islands ( SOI ), became the world's first entirely high seas marine protected area ( MPA ) in 2010. The SOI continental shelf (~44 000 km 2 ), was less than half covered by grounded ice sheet during glaciations, is biologically rich and a key area of both sea surface warming and sea‐ice losses. Little was known of the carbon cycle there, but recent work showed it was a very important site of carbon immobilization (net annual carbon accumulation) by benthos, one of the few demonstrable negative feedbacks to climate change. Carbon immobilization by SOI bryozoans was higher, per species, unit area and ice‐free day, than anywhere‐else polar. Here, we investigate why carbon immobilization has been so high at SOI , and whether this is due to high density, longevity or high annual production in six study species of bryozoans (benthic suspension feeders). We compared benthic carbon immobilization across major regions around West Antarctica with sea‐ice and primary production, from remotely sensed and directly sampled sources. Lowest carbon immobilization was at the northernmost study regions (South Georgia) and southernmost Amundsen Sea. However, data standardized for age and density showed that only SOI was anomalous (high). High immobilization at SOI was due to very high annual production of bryozoans (rather than high densities or longevity), which were 2x, 3x and 5x higher than on the Bellingshausen, South Georgia and Amundsen shelves, respectively. We found that carbon immobilization correlated to the duration (but not peak or integrated biomass) of phytoplankton blooms, both in directly sampled, local scale data and across regions using remote‐sensed data. The long bloom at SOI seems to drive considerable carbon immobilization, but sea‐ice losses across West Antarctica mean that significant carbon sinks and negative feedbacks to climate change could also develop in the Bellingshausen and Amundsen seas.

Sex-Specific Patterns in Abundance, Temporary Emigration and Survival of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) in Coastal and Estuarine Waters - Kate R. Sprogis; Kenneth H. Pollock; Holly C. Raudino; Simon J. Allen; Anna M. Kopps; Oliver Manlik; Julian A. Tyne; Lars Bejder (Frontiers in Marine Science, 2016)

Facies analysis of the Middle and Late Quaternary sediment infill of the northern Weihe Basin, Central China - Daniël S. Rits; Maarten A. Prins; Simon R. Troelstra; Ronald T. van Balen; Yan Zheng; Christiaan J. Beets; Bin Wang; Xiaoqiang Li; Jie Zhou; Hongbo Zheng (Journal of Quaternary Science, 2016)
A detailed study of the uppermost 221 m of drill core LYH‐1 – located in the northern part of the Weihe Basin – reveals considerable environmental variety over the past 1 Myr. Studied parameters include lithofacies, sedimentological properties and micropalaeontological content of selected core‐samples. Present‐day environments in the research area have been used as analogues for past conditions. The palaeoenvironments documented in the sedimentary record are interpreted as shallow lakes, fluvial settings, soils and aeolian environments. The temporal variation of the environments indicates a rapid alternation between climate‐driven wet and dry phases, suggesting that these fluctuations are related to changes in monsoon intensity. However, on a larger temporal scale, the sedimentation and accumulation of water is also affected by local tectonics. End‐member modelling shows that the siliciclastic grain‐size distributions can be ascribed to the mixing of six distinct end‐members. Most of the sediments in core LYH‐1 have similar characteristics to the loess deposits from the Central Loess Plateau. However, the much higher sedimentation rates and sedimentary structures suggest that these sediments consist for a large part of fluvially reworked loess. A broad subdivision of the core into three main intervals can be made, tentatively dated by magnetostratigraphy. From 162 to 221 m (690–1000 ka), brackish wetland conditions with a regular influence from fluvial and/or distal alluvial fan systems prevailed. The interval 90–162 m (330–690 ka) shows more terrestrial settings with occasional hypersaline lakes. From 0 to 90 m (0–330 ka), the environment was a shallow wetland, albeit with a relatively low diversity of aquatic and terrestrial microfossils compared to the lower interval.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Perceived discrimination and cancer screening behaviors in US Hispanics: the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study - Cristina Valdovinos; Frank J. Penedo; Carmen R. Isasi; Molly Jung; Robert C. Kaplan; Rebeca Espinoza Giacinto; Patricia Gonzalez; Vanessa L. Malcarne; Krista Perreira; Hugo Salgado; Melissa A. Simon; Lisa M. Wruck; et al. (Cancer Causes & Control, 2016)

Quantifying the conservation value of seascape connectivity: a global synthesis - Andrew D. Olds; Rod M. Connolly; Kylie A. Pitt; Simon J. Pittman; Paul S. Maxwell; Chantal M. Huijbers; Brad R. Moore; Simon Albert; David Rissik; Russell C. Babcock; Thomas A. Schlacher (Global Ecology and Biogeography, 2016)
Aim Connectivity structures populations, communities and ecosystems in the sea. The extent of connectivity is, therefore, predicted to also influence the outcomes of conservation initiatives, such as marine reserves. Here we review the published evidence about how important seascape connectivity (i.e. landscape connectivity in the sea) is for marine conservation outcomes. Location Global. Methods We analysed the global literature on the effects of seascape connectivity on reserve performance. Results In the majority of cases, greater seascape connectivity inside reserves translates into better conservation outcomes (i.e. enhanced productivity and diversity). Research on reserve performance is, however, most often conducted separately from research on connectivity, resulting in few studies ( Main conclusions Given that research rarely connects the effects of connectivity and reserves, our thesis is that stronger linkages between landscape ecology and marine spatial planning are likely to improve conservation outcomes in the sea. The key science challenge is to identify the full range of ecological functions that are modulated by connectivity and the spatial scale over which these functions enhance conservation outcomes.

Elemental changes in the hippocampal formation following two different formulas of ketogenic diet: an X-ray fluorescence microscopy study - J. Chwiej; A. Patulska; A. Skoczen; K. Janeczko; M. Ciarach; R. Simon; Z. Setkowicz (JBIC Journal of Biological Inorganic Chemistry, 2015)

Time to leave? Immediate response of roe deer to experimental disturbances using playbacks - Sophie Padié; Nicolas Morellet; Bruno Cargnelutti; A. J. Mark Hewison; Jean-Louis Martin; Simon Chamaillé-Jammes (European Journal of Wildlife Research, 2015)

Infrastructure for collaborative science and societal applications in the Columbia River estuary - António M. Baptista; Charles Seaton; Michael P. Wilkin; Sarah F. Riseman; Joseph A. Needoba; David Maier; Paul J. Turner; Tuomas Kärnä; Jesse E. Lopez; Lydie Herfort; V. M. Megler; Craig McNeil; et al. (Frontiers of Earth Science, 2015)
To meet societal needs, modern estuarine science needs to be interdisciplinary and collaborative, combine discovery with hypotheses testing, and be responsive to issues facing both regional and global stakeholders. Such an approach is best conducted with the benefit of data-rich environments, where information from sensors and models is openly accessible within convenient timeframes. Here, we introduce the operational infrastructure of one such data-rich environment, a collaboratory created to support (a) interdisciplinary research in the Columbia River estuary by the multi-institutional team of investigators of the Science and Technology Center for Coastal Margin Observation & Prediction and (b) the integration of scientific knowledge into regional decision making. Core components of the operational infrastructure are an observation network, a modeling system and a cyber-infrastructure, each of which is described. The observation network is anchored on an extensive array of long-term stations, many of them interdisciplinary, and is complemented by on-demand deployment of temporary stations and mobile platforms, often in coordinated field campaigns. The modeling system is based on finiteelement unstructured-grid codes and includes operational and process-oriented simulations of circulation, sediments and ecosystem processes. The flow of information is managed through a dedicated cyber-infrastructure, conversant with regional and national observing systems.

Four-way development of microsatellite markers for the Gouldian finch (Erythrura gouldiae) - Kang-Wook Kim; Hanyuan Zhang; Gavin J. Horsburgh; Susannah Bird; Deborah A. Dawson; Simon C. Griffith; Terry Burke (Conservation Genetics Resources, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Modelling hydrological processes, crop yields and NPS pollution in a small sub-tropical catchment in South Africa using ACRU-NPS - Kipkemboi J. Kollongei; Simon A. Lorentz (Hydrological Sciences Journal, 2015)

Restoring forests: What constitutes success in the twenty-first century? - Douglass F. Jacobs; Juan A. Oliet; James Aronson; Andreas Bolte; James M. Bullock; Pablo J. Donoso; Simon M. Landhäusser; Palle Madsen; Shaolin Peng; José M. Rey-Benayas; John C. Weber (New Forests, 2015)

The mineralogy and fabric of ‘Brickearths’ in Kent, UK and their relationship to engineering behaviour - Antoni E. Milodowski; Kevin J. Northmore; Simon J. Kemp; David C. Entwisle; David A. Gunn; Peter D. Jackson; David I. Boardman; Aris Zoumpakis; Christopher D. F. Rogers; Neil Dixon; Ian Jefferson; Ian J. Smalley; et al. (Bulletin of Engineering Geology and the Environment, 2015)

Influences of extreme weather, climate and pesticide use on invertebrates in cereal fields over 42 years - Julie A. Ewald; Christopher J. Wheatley; Nicholas J. Aebischer; Stephen J. Moreby; Simon J. Duffield; Humphrey Q. P. Crick; Michael B. Morecroft (Global Change Biology, 2015)
Cereal fields are central to balancing food production and environmental health in the face of climate change. Within them, invertebrates provide key ecosystem services. Using 42 years of monitoring data collected in southern E ngland, we investigated the sensitivity and resilience of invertebrates in cereal fields to extreme weather events and examined the effect of long‐term changes in temperature, rainfall and pesticide use on invertebrate abundance. Of the 26 invertebrate groups examined, eleven proved sensitive to extreme weather events. Average abundance increased in hot/dry years and decreased in cold/wet years for A raneae, C icadellidae, adult H eteroptera, T hysanoptera, B raconidae, E nicmus and L athridiidae. The average abundance of D elphacidae, C ryptophagidae and M ycetophilidae increased in both hot/dry and cold/wet years relative to other years. The abundance of all 10 groups usually returned to their long‐term trend within a year after the extreme event. For five of them, sensitivity to cold/wet events was lowest (translating into higher abundances) at locations with a westerly aspect. Some long‐term trends in invertebrate abundance correlated with temperature and rainfall, indicating that climate change may affect them. However, pesticide use was more important in explaining the trends, suggesting that reduced pesticide use would mitigate the effects of climate change.

Surgical attenuation of spontaneous congenital portosystemic shunts in dogs resolves hepatic encephalopathy but not hypermanganesemia - Adam G. Gow; Polly E. Frowde; Clive M. Elwood; Carolyn A. Burton; Roger M. Powell; Simon W. Tappin; Rob D. Foale; Andrew Duncan; Richard J. Mellanby (Metabolic Brain Disease, 2015)

Effect-based assessment of persistent organic pollutant and pesticide dumpsite using mammalian CALUX reporter cell lines - B. Pieterse; I. J. C. Rijk; E. Simon; B. M. A. van Vugt-Lussenburg; B. F. H. Fokke; M. van der Wijk; H. Besselink; R. Weber; B. van der Burg (Environmental Science and Pollution Research, 2015)

First recorded eruption of Nabro volcano, Eritrea, 2011 - Berhe Goitom; Clive Oppenheimer; James O. S. Hammond; Raphaël Grandin; Talfan Barnie; Amy Donovan; Ghebrebrhan Ogubazghi; Ermias Yohannes; Goitom Kibrom; J- Michael Kendall; Simon A. Carn; David Fee; et al. (Bulletin of Volcanology, 2015)

Metagenomic characterization of viral communities in corals: mining biological signal from methodological noise - Elisha M. Wood‐Charlson; Karen D. Weynberg; Curtis A. Suttle; Simon Roux; Madeleine J. H. van Oppen (Environmental Microbiology, 2015)
Summary Reef‐building corals form close associations with organisms from all three domains of life and therefore have many potential viral hosts. Yet knowledge of viral communities associated with corals is barely explored. This complexity presents a number of challenges in terms of the metagenomic assessments of coral viral communities and requires specialized methods for purification and amplification of viral nucleic acids, as well as virome annotation. In this minireview, we conduct a meta‐analysis of the limited number of existing coral virome studies, as well as available coral transcriptome and metagenome data, to identify trends and potential complications inherent in different methods. The analysis shows that the method used for viral nucleic acid isolation drastically affects the observed viral assemblage and interpretation of the results. Further, the small number of viral reference genomes available, coupled with short sequence read lengths might cause errors in virus identification. Despite these limitations and potential biases, the data show that viral communities associated with corals are diverse, with double‐ and single‐stranded DNA and RNA viruses. The identified viruses are dominated by double‐stranded DNA ‐tailed bacteriophages, but there are also viruses that infect eukaryote hosts, likely the endosymbiotic dinoflagellates, Symbiodinium spp., host coral and other eukaryotes in close association.

Phylogeography of six codistributed New Zealand cicadas and their relationship to multiple biogeographical boundaries suggest a re‐evaluation of the Taupo Line - Emily A. Ellis; David C. Marshall; Kathy B. R. Hill; Christopher L. Owen; Peter J. J. Kamp; Chris Simon (Journal of Biogeography, 2015)
Aim Comparative biogeographers question the extent to which codistributed species respond similarly to environmental change. Such responses should create similar, appropriately timed patterns of cladogenesis among codistributed taxa compared to evolutionary independence, which may limit the predictions that can be made for unstudied species. Here, we compare phylogeographical patterns across ecologically divergent, codistributed taxa in the light of New Zealand's palaeohistory. Location North Island, New Zealand. Methods Mitochondrial DNA from six codistributed cicada species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta , K. scutellaris and K. dugdalei ) was analysed using phylogenetic methods and molecular dating techniques. We analysed phylogeographical distributions using analysis of molecular variance ( AMOVA ) to determine the significance of hypothesized biogeographical boundaries for clade differentiation and spatial distribution of genetic diversity. Results Five species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta and K. scutellaris ) show various degrees of intraspecific concordance with biogeographical boundaries found in previously studied taxa – the Kauri Line, the Northland Line and the newly identified Cockayne's Line. Clade splits of forest species correlate with the Kauri Line and/or Northland Line, whereas splits of scrub/hill species correlate with Cockayne's Line. Four species ( Kikihia ochrina , K. cutora , K. laneorum and K. cauta ) diversified before the Last Glacial Maximum ( LGM , 20 ka), whereas two species ( K. scutellaris and K. dugdalei ) show only post‐ LGM diversification. Main conclusions Despite species idiosyncrasies, we see the imprint of shared palaeoclimatic/geological events. We distinguish between (1) the importance of biogeographical lines as the demarcation between older genetically diverse and newer genetically depauperate populations, and (2) the importance of lines as biogeographical boundaries between sister clades. We also stress the importance of dating clade splits to ensure consistency with explanations for the biogeographical lines in question. We suggest that the Taupo Line has been overemphasized as a biogeographical boundary, whereas the importance of the mountain axis running north‐east to south‐west (‘Cockayne's Line’) has been overlooked.

Understanding fisheries credit systems: potentials and pitfalls of managing catch efficiency - Maria C Van Riel; Simon R Bush; Paul A M van Zwieten; Arthur P J Mol (Fish and Fisheries, 2015)
Following implementation in a range of other resource sectors, a number of credit‐like systems have been proposed for fisheries. But confusion exists over what constitutes these nascent ‘fisheries credit’ systems and how they operate. Based on a review of credit systems in other sectors, this study fills this gap by defining how credit systems function and what credits add to prevailing fisheries management. In doing so, we distinguish ‘mitigation’ and ‘behavioural’ fishery credits. Mitigation credits require resource users to compensate for unsustainable catches of target species, by‐catch species or damaging practices on the marine environment by investing in conservation in a biologically equivalent habitat or resource. Behavioural credit systems incentivize fishers to gradually change their fishing behaviour to more sustainable fishing methods by rewarding them with, for instance, extra fishing effort to compensate for less efficient but more sustainable fishing methods. The choice of credit system largely depends on the characteristics of specific fisheries and the management goals agreed upon by managers, scientists and the fishing industry. The study concludes that fisheries credit systems are different but complimentary to other forms of management by focusing on ‘catchability’ or gear efficiency in addition to effort or catch quota, affecting overall economic efficiency by setting specific goals as to how fish are caught. Credit systems therefore incentivize specific management interventions that can directly improve stock sustainability, conserve habitat and endangered species, or decrease by‐catch.

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Antimicrobial susceptibility of rapidly growing mycobacteria using the rapid colorimetric method - I. B. Ramis; M. Cnockaert; A. von Groll; C. L. Nogueira; S. C. Leão; E. Andre; A. Simon; J. C. Palomino; P. E. A. da Silva; P. Vandamme; A. Martin (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The RPTEC/TERT1 Cell Line as an Improved Tool for In Vitro Nephrotoxicity Assessments - Bridget R. Simon-Friedt; Mark J. Wilson; Diane A. Blake; Haini Yu; Yasmin Eriksson; Jeffrey K. Wickliffe (Biological Trace Element Research, 2015)

Characterization of a Synechocystis sp. PCC 6803 double mutant lacking the CyanoP and Ycf48 proteins of Photosystem II - Simon A. Jackson; Julian J. Eaton-Rye (Photosynthesis Research, 2015)

Resource availability affects individual niche variation and its consequences in group-living European badgers Meles meles - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (Oecologia, 2015)

Exploiting the intrinsic hydrocarbon-degrading microbial capacities in oil tank bottom sludge and waste soil for sludge bioremediation - E. M. Adetutu; C. Bird; K. K. Kadali; A. Bueti; E. Shahsavari; M. Taha; S. Patil; P. J. Sheppard; T. Makadia; K. L. Simons; A. S. Ball (International Journal of Environmental Science and Technology, 2015)

Peptide Amphiphile Micelles Self-Adjuvant Group A Streptococcal Vaccination - Amanda Trent; Bret D. Ulery; Matthew J. Black; John C. Barrett; Simon Liang; Yulia Kostenko; Natalie A. David; Matthew V. Tirrell (The AAPS Journal, 2015)

Population dynamics of Thaumastocoris peregrinus in Eucalyptus plantations of South Africa - Ryan L. Nadel; Michael J. Wingfield; Mary C. Scholes; Jeffrey R. Garnas; Simon A. Lawson; Bernard Slippers (Journal of Pest Science, 2015)

Evolutionary transitions of complex labile traits: Silk weaving and arboreal nesting in Polyrhachis ants - Simon K. A. Robson; Rudy J. Kohout; Andrew T. Beckenbach; Corrie S. Moreau (Behavioral Ecology and Sociobiology, 2015)

Species associations structured by environment and land‐use history promote beta‐diversity in a temperate forest - Stephen J. Murphy; Lívia D. Audino; James Whitacre; Jenalle L. Eck; John W. Wenzel; Simon A. Queenborough; Liza S. Comita (Ecology, 2015)
Patterns of diversity and community composition in forests are controlled by a combination of environmental factors, historical events, and stochastic or neutral mechanisms. Each of these processes has been linked to forest community assembly, but their combined contributions to alpha and beta‐diversity in forests has not been well explored. Here we use variance partitioning to analyze ~40 000 individual trees of 49 species, collected within 137 ha of sampling area spread across a 900‐ha temperate deciduous forest reserve in Pennsylvania to ask (1) To what extent is site‐to‐site variation in species richness and community composition of a temperate forest explained by measured environmental gradients and by spatial descriptors (used here to estimate dispersal‐assembly or unmeasured, spatially structured processes)? (2) How does the incorporation of land‐use history information increase the importance attributed to deterministic community assembly? and (3) How do the distributions and abundances of individual species within the community correlate with these factors? Environmental variables (i.e., topography, soils, and distance to stream), spatial descriptors (i.e., spatial eigenvectors derived from Cartesian coordinates), and land‐use history variables (i.e., land‐use type and intensity, forest age, and distance to road), explained about half of the variation in both species richness and community composition. Spatial descriptors explained the most variation, followed by measured environmental variables and then by land‐use history. Individual species revealed variable responses to each of these sets of predictor variables. Several species were associated with stream habitats, and others were strictly delimited across opposing north‐ and south‐facing slopes. Several species were also associated with areas that experienced recent (i.e.,

Time-course of extracellular nicotine and cotinine levels in rat brain following administration of nicotine: effects of route and ethanol coadministration - Simon N. Katner; Jamie E. Toalston; Michael P. Smoker; Zachary A. Rodd; William J. McBride; Eric A. Engleman (Psychopharmacology, 2015)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Genome edited sheep and cattle - Chris Proudfoot; Daniel F. Carlson; Rachel Huddart; Charles R. Long; Jane H. Pryor; Tim J. King; Simon G. Lillico; Alan J. Mileham; David G. McLaren; C. Bruce A. Whitelaw; Scott C. Fahrenkrug (Transgenic Research, 2015)

Response of beta diversity to pulses of Ordovician‐Silurian mass extinction - Simon A. F. Darroch; Peter J. Wagner (Ecology, 2015)
Ecologists are increasingly using the fossil record of mass extinction to build predictive models for the ongoing biodiversity crisis. During mass extinctions, major depletions in global (i.e., gamma) diversity may reflect decrease in alpha diversity (i.e., local assemblages support fewer taxa), and/or decrease in beta diversity (such that similar pools of taxa are common to a greater number of local areas). Contrasting the effects of extinction on alpha and beta diversity is therefore central to understanding how global richness becomes depleted over these critical events. Here we investigate the spatial effects of mass extinction by examining changes in alpha, beta, and gamma diversity in brachiopod communities over both pulses of Ordovician‐Silurian extinction (~445.2 and ~438.8 million years ago), which had dramatically different causal mechanisms. We furthermore reconstruct geographic range sizes for brachiopod genera to test competing models for drivers of beta diversity change. We find that: (1) alpha and beta diversity respond differently to extinction; (2) these responses differ between pulses of extinction; (3) changes in beta diversity associated with extinction are accompanied by changes in geographic range size; and (4) changes in global beta diversity were driven by the extinction of taxa with statistically small and large ranges, rather than range expansion/contraction in taxa that survive into the aftermath. A symptom of ongoing biotic crisis may therefore be the extinction of specific narrow‐ or wide‐ranging taxa, rather than the global proliferation of opportunistic and “disaster” forms. In addition, our results illustrate that changes in beta diversity on these longer timescales may largely be dictated by emplacement and removal of barriers to dispersal. Lastly, this study reinforces the utility of the fossil record in addressing questions surrounding the role of global‐scale processes (such as mass extinctions) in sculpting and assembling regional biotas.

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Effects of neonicotinoids and fipronil on non-target invertebrates - L. W. Pisa; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; C. A. Downs; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; M. McField; C. A. Morrissey; D. A. Noome; et al. (Environmental Science and Pollution Research, 2015)
We assessed the state of knowledge regarding the effects of large-scale pollution with neonicotinoid insecticides and fipronil on non-target invertebrate species of terrestrial, freshwater and marine environments. A large section of the assessment is dedicated to the state of knowledge on sublethal effects on honeybees ( Apis mellifera ) because this important pollinator is the most studied non-target invertebrate species. Lepidoptera (butterflies and moths), Lumbricidae (earthworms), Apoidae sensu lato (bumblebees, solitary bees) and the section “other invertebrates” review available studies on the other terrestrial species. The sections on freshwater and marine species are rather short as little is known so far about the impact of neonicotinoid insecticides and fipronil on the diverse invertebrate fauna of these widely exposed habitats. For terrestrial and aquatic invertebrate species, the known effects of neonicotinoid pesticides and fipronil are described ranging from organismal toxicology and behavioural effects to population-level effects. For earthworms, freshwater and marine species, the relation of findings to regulatory risk assessment is described. Neonicotinoid insecticides exhibit very high toxicity to a wide range of invertebrates, particularly insects, and field-realistic exposure is likely to result in both lethal and a broad range of important sublethal impacts. There is a major knowledge gap regarding impacts on the grand majority of invertebrates, many of which perform essential roles enabling healthy ecosystem functioning. The data on the few non-target species on which field tests have been performed are limited by major flaws in the outdated test protocols. Despite large knowledge gaps and uncertainties, enough knowledge exists to conclude that existing levels of pollution with neonicotinoids and fipronil resulting from presently authorized uses frequently exceed the lowest observed adverse effect concentrations and are thus likely to have large-scale and wide ranging negative biological and ecological impacts on a wide range of non-target invertebrates in terrestrial, aquatic, marine and benthic habitats.

Environmental fate and exposure; neonicotinoids and fipronil - J.-M. Bonmatin; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; E. Long; M. Marzaro; E. A. D. Mitchell; D. A. Noome; N. Simon-Delso; et al. (Environmental Science and Pollution Research, 2015)

Response to commentary by W oinarski (Critical‐weight‐range marsupials in northern A ustralia are declining: a commentary on Fisher et al . (2014) ‘The current decline of tropical marsupials in A ustralia: is history repeating?’) - Diana O. Fisher; Chris N. Johnson; Michael J. Lawes; Susanne A. Fritz; Hamish McCallum; Simon P. Blomberg; Jeremy VanDerWal; Brett Abbott; Anke Frank; Sarah Legge; Mike Letnic; Colette R. Thomas; et al. (Global Ecology and Biogeography, 2015)
The recent commentary by Woinarski (2014, Global Ecology and Biogeography , doi: 10.1111/geb.12165) disagreed with our conclusions on the correlates of decline in the marsupials of tropical A ustralia (Fisher et al., 2014, Global Ecology and Biogeography , 23 , 181–190). We compared traits of species that were associated with range decline in southern and northern A ustralia. We found that habitat structure, climate and body size were correlated with range decline. In the north, declines of marsupials were most severe in savanna with moderate rainfall. In the south, the ranges of species in open habitat with very low rainfall have declined most. Also, the association between range decline and body mass differed between north and south: this is the main concern of Woinarski, who further disagreed with our choice of the T ropic of C apricorn as a boundary between north and south, our omission of rodents, how to treat timing of extinctions, and our inference that cats are major drivers of decline. W e address these concerns in this response.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Acute leukocyte, cytokine and adipocytokine responses to maximal and hypertrophic resistance exercise bouts - Johanna Ihalainen; Simon Walker; Gøran Paulsen; Keijo Häkkinen; William J. Kraemer; Mari Hämäläinen; Katriina Vuolteenaho; Eeva Moilanen; Antti A Mero (European Journal of Applied Physiology, 2014)

Evolution of Stratocumulus Over Land: Comparison of Ground and Aircraft Observations with Numerical Weather Prediction Simulations - Simon R. Osborne; Steven J. Abel; Ian A. Boutle; Franco Marenco (Boundary-Layer Meteorology, 2014)

Individual foraging specialisation in a social mammal: the European badger (Meles meles) - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (Oecologia, 2014)

Cassava Ivorian bacilliform virus is a member of the genus Anulavirus - Simon W. Scott; Stuart A. MacFarlane; Wendy J. McGavin; Denis Fargette (Archives of Virology, 2014)

The use of synoptic climatology with general circulation model output over New Zealand - Simon Parsons; Adrian J. McDonald; James A. Renwick (International Journal of Climatology, 2014)
A cluster analysis‐based synoptic classification scheme, known as the Kidson types, was applied to reanalyses and Coupled Model Inter‐comparison Project phase 3 ( CMIP3 ) general circulation model ( GCM ) output over New Zealand to identify the potential for future changes in regional circulation. Results indicate that a number of GCM 20th century control runs reproduce the type frequencies observed in reanalysis data. Application to future scenario runs for the periods 2046–2065 and 2081–2100 displays little variation in the annual frequency of the synoptic types relative to the 20th century, especially when uncertainty associated with the model ensemble is considered. This is surprising in the context of previous work on possible future movements in jet position and subsequent impacts on weather patterns. A sensitivity analysis that mimics the movement of the jet position was performed, revealing that the annual type frequencies are relatively insensitive to change. To determine whether this is a problem with the synoptic typing scheme, a correlation‐based classification technique was also used, but showed similar results. This work highlights issues with applying synoptic classification schemes to GCM output and indicates that if such schemes are to be used they should be designed and tested with this application in mind.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Genome-wide QTL and bulked transcriptomic analysis reveals new candidate genes for the control of tuber carotenoid content in potato (Solanum tuberosum L.) - Raymond Campbell; Simon D. A. Pont; Jenny A. Morris; Gaynor McKenzie; Sanjeev Kumar Sharma; Pete E. Hedley; Gavin Ramsay; Glenn J. Bryan; Mark A. Taylor (Theoretical and Applied Genetics, 2014)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

An assessment of chemical contaminants in sediments from the St. Thomas East End Reserves, St. Thomas, USVI - Anthony S. Pait; S. Ian Hartwell; Andrew L. Mason; Robert A. Warner; Christopher F. G. Jeffrey; Anne M. Hoffman; Dennis A. Apeti; Simon J. Pittman (Environmental Monitoring and Assessment, 2014)

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Heather Moorland Vegetation and Air Pollution: A Comparison and Synthesis of Three National Gradient Studies - Richard J. Payne; Simon J. M. Caporn; Christopher D. Field; Jacky A. Carroll; Jill L. Edmondson; Andrea Britton; Nancy B. Dise (Water, Air, & Soil Pollution, 2014)

Testate amoebae as a proxy for reconstructing Holocene water table dynamics in southern Patagonian peat bogs - SIMON VAN BELLEN; DMITRI MAUQUOY; RICHARD J. PAYNE; THOMAS P. ROLAND; TIM J. DALEY; PAUL D. M. HUGHES; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; EMMA M. RICE; VERÓNICA A. PANCOTTO (Journal of Quaternary Science, 2014)
Testate amoebae are abundant and diverse in Sphagnum peat bogs and have been used extensively as indicators of past water table depths. Although these unicellular protists are widely dispersed with globally similar hydrological preferences, regional variations in communities demand region‐specific transfer functions. Here we present the first transfer function for southern Patagonian bogs, based on 154 surface samples obtained from transects in five bogs sampled in 2012 and 2013. Significant variance was explained by pH, electrical conductivity and, in particular, water table depth. Transfer functions for water table were constructed using weighted averaging and evaluated by cross‐validation and independent test sets. The optimal transfer function has predictive ability, but relatively high prediction errors given the wide range in sampled water tables. The use of independent test sets, as well as cross‐validation, allows a more rigorous assessment of model performance than most previous studies. For a subset of locations we compare surface and subsurface samples to demonstrate significant differences in community composition, possibly due to vertical zonation. Our results provide the first quantification of hydrological optima and tolerances for several rare species, which may include Southern Hemisphere endemics and pave the way for palaeohydrological reconstructions in southern Patagonian bogs.

Transcriptional profiling of G ram‐positive A rthrobacter in the phyllosphere: induction of pollutant degradation genes by natural plant phenolic compounds - Tanja R. Scheublin; Simon Deusch; Silvia K. Moreno‐Forero; Jochen A. Müller; Jan Roelof van der Meer; Johan H. J. Leveau (Environmental Microbiology, 2014)
Summary A rthrobacter chlorophenolicus A 6 is a G ram‐positive, 4‐chlorophenol‐degrading soil bacterium that was recently shown to be an effective colonizer of plant leaf surfaces. The genetic basis for this phyllosphere competency is unknown. In this paper, we describe the genome‐wide expression profile of A . chlorophenolicus on leaves of common bean ( P haseolus vulgaris ) compared with growth on agar surfaces. In phyllosphere‐grown cells, we found elevated expression of several genes known to contribute to epiphytic fitness, for example those involved in nutrient acquisition, attachment, stress response and horizontal gene transfer. A surprising result was the leaf‐induced expression of a subset of the so‐called cph genes for the degradation of 4‐chlorophenol. This subset encodes the conversion of the phenolic compound hydroquinone to 3‐oxoadipate, and was shown to be induced not only by 4‐chlorophenol but also hydroquinone, its glycosylated derivative arbutin, and phenol. Small amounts of hydroquinone, but not arbutin or phenol, were detected in leaf surface washes of P . vulgaris by gas chromatography‐mass spectrometry. Our findings illustrate the utility of genomics approaches for exploration and improved understanding of a microbial habitat. Also, they highlight the potential for phyllosphere‐based priming of bacteria to stimulate pollutant degradation, which holds promise for the application of phylloremediation.

The Wadi Zaghra metasediments of Sinai, Egypt: new constraints on the late Cryogenian–Ediacaran tectonic evolution of the northernmost Arabian–Nubian Shield - Arild Andresen; Mahrous M. Abu El-Enen; Robert J. Stern; Simon A. Wilde; Kamal A. Ali (International Geology Review, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Development of anonymous nuclear markers from Illumina paired-end data for Seychelles caecilian amphibians (Gymnophiona: Indotyphlidae) - Claire J. Lewis; Simon T. Maddock; Julia J. Day; Ronald A. Nussbaum; Charles Morel; Mark Wilkinson; Peter G. Foster; David J. Gower (Conservation Genetics Resources, 2014)
Anonymous nuclear markers were developed for Seychelles caecilian amphibians. Using a previously published bioinformatics pipeline (developed for Roche 454 data), 36 candidate anonymous nuclear loci (ANL) of at least 180 bp length were identified from Illumina MiSeq next generation sequencing data for five Seychelles species. We designed primer pairs for the 36 candidate ANL and tested these by PCR and Sanger sequencing. Seven ANL amplified and sequenced well for at least five of the six nominal Seychelles caecilian species (in three genera), and represent potentially useful markers for systematics and conservation.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genetic structure of populations of whale sharks among ocean basins and evidence for their historic rise and recent decline - Thomas M. Vignaud; Jeffrey A. Maynard; Raphael Leblois; Mark G. Meekan; Ricardo Vázquez‐Juárez; Dení Ramírez‐Macías; Simon J. Pierce; David Rowat; Michael L. Berumen; Champak Beeravolu; Sandra Baksay; Serge Planes (Molecular Ecology, 2014)
This study presents genetic evidence that whale sharks, Rhincodon typus , are comprised of at least two populations that rarely mix and is the first to document a population expansion. Relatively high genetic structure is found when comparing sharks from the Gulf of Mexico with sharks from the Indo‐Pacific. If mixing occurs between the Indian and Atlantic Oceans, it is not sufficient to counter genetic drift. This suggests whale sharks are not all part of a single global metapopulation. The significant population expansion we found was indicated by both microsatellite and mitochondrial DNA . The expansion may have happened during the Holocene, when tropical species could expand their range due to sea‐level rise, eliminating dispersal barriers and increasing plankton productivity. However, the historic trend of population increase may have reversed recently. Declines in genetic diversity are found for 6 consecutive years at Ningaloo Reef in Australia. The declines in genetic diversity being seen now in Australia may be due to commercial‐scale harvesting of whale sharks and collision with boats in past decades in other countries in the Indo‐Pacific. The study findings have implications for models of population connectivity for whale sharks and advocate for continued focus on effective protection of the world's largest fish at multiple spatial scales.

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Isolation and characterization of fifteen microsatellite loci in Leopard grouper (Mycteroperca rosacea) via 454 pyrosequencing - Alexis M. Jackson; Adrian Munguía-Vega; Avian S. Lain; Simon A. Stokes; Aneese J. Williams; Giacomo Bernardi (Conservation Genetics Resources, 2014)

Immunocytochemical localization of carbonic anhydrase in the pseudobranch tissue of the rainbow trout Oncorhynchus my-kiss - S. M. Rahim; A. G. Mazlan; K. D. Simon; J. P. Delaunoy; P. Laurent (Journal of Zhejiang University-SCIENCE B, 2014)

Limited habitat and conservation value of a young artificial reef - Simon J. Walker; Thomas A. Schlacher (Biodiversity and Conservation, 2014)

The current decline of tropical marsupials in A ustralia: is history repeating? - Diana O. Fisher; Chris N. Johnson; Michael J. Lawes; Susanne A. Fritz; Hamish McCallum; Simon P. Blomberg; Jeremy VanDerWal; Brett Abbott; Anke Frank; Sarah Legge; Mike Letnic; Colette R. Thomas; et al. (Global Ecology and Biogeography, 2014)
Aim A third of all modern (after 1500) mammal extinctions (24/77) are Australian species. These extinctions have been restricted to southern A ustralia, predominantly in species of ‘critical weight range’ (35–5500 g) in drier climate zones. Introduced red foxes ( V ulpes vulpes ) that prey on species in this range are often blamed. A new wave of declines is now affecting a globally significant proportion of marsupial species (19 species) in the fox‐free northern tropics. We aim to test plausible causes of recent declines in range and determine if mechanisms differ between current tropical declines and past declines, which were in southern (non‐tropical) regions. Location A ustralian continent Methods We used multiple regression and random forest models to analyse traits that were associated with declines in species range, and compare variables associated with past extinctions in the southern zones with current tropical (northern) declines. Results The same two key variables, body mass and habitat structure, were associated with proportion‐of‐decline in range throughout the continent, but the form of relationships differs with latitude. In the south, medium‐sized species in open habitats of lower rainfall were most likely to decline. In the tropics, small species that occupy open vegetation with moderate rainfall (savanna) are now experiencing the most severe declines. Throughout the continent, large‐bodied species and those in structurally complex habitats (rainforest) are secure. Main conclusions Our results indicate that there is no mid‐sized ‘critical weight range’ in the north. Because foxes are absent from the tropics, we suggest that northern Australian marsupial declines are associated with predation by feral cats ( F elis catus ) exacerbated by reduced ground level vegetation in non‐rainforest habitats. To test this, we recommend experiments to remove cats from some locations where tropical mammals are threatened. Our results show that comparative analysis can help to diagnose potential causes of multi‐species decline.

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Limited genetic structure among broad-scale regions for two commercially harvested, tropical deep-water snappers in New Caledonia - Kim L. Loeun; Sharyn Goldstien; Dianne Gleeson; Simon J. Nicol; Corey J. A. Bradshaw (Fisheries Science, 2014)

A systematic review of brain frontal lobe parcellation techniques in magnetic resonance imaging - Simon R. Cox; Karen J. Ferguson; Natalie A. Royle; Susan D. Shenkin; Sarah E. MacPherson; Alasdair M. J. MacLullich; Ian J. Deary; Joanna M. Wardlaw (Brain Structure and Function, 2014)

Detailed multidisciplinary monitoring reveals pre- and co-eruptive signals at Nyamulagira volcano (North Kivu, Democratic Republic of Congo) - Benoît Smets; Nicolas d’Oreye; François Kervyn; Matthieu Kervyn; Fabien Albino; Santiago R. Arellano; Montfort Bagalwa; Charles Balagizi; Simon A. Carn; Thomas H. Darrah; José Fernández; Bo Galle; et al. (Bulletin of Volcanology, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Circulating galectin-3 in infections and non-infectious inflammatory diseases - J. Oever; E. J. Giamarellos-Bourboulis; F. L. Veerdonk; F. F. Stelma; A. Simon; M. Janssen; M. Johnson; A. Pachot; B.-J. Kullberg; L. A. B. Joosten; M. G. Netea (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Predicting species distributions for conservation decisions - Antoine Guisan; Reid Tingley; John B. Baumgartner; Ilona Naujokaitis‐Lewis; Patricia R. Sutcliffe; Ayesha I. T. Tulloch; Tracey J. Regan; Lluis Brotons; Eve McDonald‐Madden; Chrystal Mantyka‐Pringle; Tara G. Martin; Jonathan R. Rhodes; et al. (Ecology Letters, 2013)
Species distribution models (SDMs) are increasingly proposed to support conservation decision making. However, evidence of SDMs supporting solutions for on‐ground conservation problems is still scarce in the scientific literature. Here, we show that successful examples exist but are still largely hidden in the grey literature, and thus less accessible for analysis and learning. Furthermore, the decision framework within which SDMs are used is rarely made explicit. Using case studies from biological invasions, identification of critical habitats, reserve selection and translocation of endangered species, we propose that SDMs may be tailored to suit a range of decision‐making contexts when used within a structured and transparent decision‐making process. To construct appropriate SDMs to more effectively guide conservation actions, modellers need to better understand the decision process, and decision makers need to provide feedback to modellers regarding the actual use of SDMs to support conservation decisions. This could be facilitated by individuals or institutions playing the role of ‘translators’ between modellers and decision makers. We encourage species distribution modellers to get involved in real decision‐making processes that will benefit from their technical input; this strategy has the potential to better bridge theory and practice, and contribute to improve both scientific knowledge and conservation outcomes.

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Pup to adult photo‐ ID : Evidence of pelage stability in gray seals - William D. Paterson; Paula Redman; Lex A. Hiby; Simon E. W. Moss; Ailsa J. Hall; Paddy Pomeroy (Marine Mammal Science, 2013)

Warming effects on greenhouse gas fluxes in peatlands are modulated by vegetation composition - Susan E. Ward; Nicholas J. Ostle; Simon Oakley; Helen Quirk; Peter A. Henrys; Richard D. Bardgett (Ecology Letters, 2013)
Understanding the effects of warming on greenhouse gas feedbacks to climate change represents a major global challenge. Most research has focused on direct effects of warming, without considering how concurrent changes in plant communities may alter such effects. Here, we combined vegetation manipulations with warming to investigate their interactive effects on greenhouse gas emissions from peatland. We found that although warming consistently increased respiration, the effect on net ecosystem CO 2 exchange depended on vegetation composition. The greatest increase in CO 2 sink strength after warming was when shrubs were present, and the greatest decrease when graminoids were present. CH 4 was more strongly controlled by vegetation composition than by warming, with largest emissions from graminoid communities. Our results show that plant community composition is a significant modulator of greenhouse gas emissions and their response to warming, and suggest that vegetation change could alter peatland carbon sink strength under future climate change.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Regime shifts in a social-ecological system - Steven J. Lade; Alessandro Tavoni; Simon A. Levin; Maja Schlüter (Theoretical Ecology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

When condition trumps location: seed consumption by fruit‐eating birds removes pathogens and predator attractants - Evan C. Fricke; Melissa J. Simon; Karen M. Reagan; Douglas J. Levey; Jeffrey A. Riffell; Tomás A. Carlo; Joshua J. Tewksbury (Ecology Letters, 2013)
Seed ingestion by frugivorous vertebrates commonly benefits plants by moving seeds to locations with fewer predators and pathogens than under the parent. For plants with high local population densities, however, movement from the parent plant is unlikely to result in ‘escape’ from predators and pathogens. Changes to seed condition caused by gut passage may also provide benefits, yet are rarely evaluated as an alternative. Here, we use a common bird‐dispersed chilli pepper ( Capsicum chacoense ) to conduct the first experimental comparison of escape‐related benefits to condition‐related benefits of animal‐mediated seed dispersal. Within chilli populations, seeds dispersed far from parent plants gained no advantage from escape alone, but seed consumption by birds increased seed survival by 370% – regardless of dispersal distance – due to removal during gut passage of fungal pathogens and chemical attractants to granivores. These results call into question the pre‐eminence of escape as the primary advantage of dispersal within populations and document two overlooked mechanisms by which frugivores can benefit fruiting plants.

Environmental Influences on Faecal Indicator Organisms in Coastal Waters and Their Accumulation in Bivalve Shellfish - Carlos J. A. Campos; Simon R. Kershaw; Ron J. Lee (Estuaries and Coasts, 2013)

Whisker growth in wild Eurasian badgers Meles meles: implications for stable isotope and bait marking studies - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (European Journal of Wildlife Research, 2013)

A Novel Acquisition Technique to Utilize Swan-Ganz Catheter data as a Surrogate for High-fidelity Micromanometry within the Right Ventricle and Pulmonary Circuit - T. N. Bachman; J. J. Bursic; M. A. Simon; H. C. Champion (Cardiovascular Engineering and Technology, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Close-range hyperspectral imaging for geological field studies: workflow and methods - Tobias H. Kurz; Simon J. Buckley; John A. Howell (International Journal of Remote Sensing, 2013)

Soil biotransformation of thiodiglycol, the hydrolysis product of mustard gas: understanding the factors governing remediation of mustard gas contaminated soil - Hong Li; Robert Muir; Neil R. McFarlane; Richard J. Soilleux; Xiaohong Yu; Ian P. Thompson; Simon A. Jackman (Biodegradation, 2013)

Decreased serum glucose and glycosylated hemoglobin levels in patients with Chuvash polycythemia: a role for HIF in glucose metabolism - Donald A. McClain; Khadega A. Abuelgasim; Mehdi Nouraie; Juan Salomon-Andonie; Xiaomei Niu; Galina Miasnikova; Lydia A. Polyakova; Adelina Sergueeva; Daniel J. Okhotin; Rabia Cherqaoui; David Okhotin; James E. Cox; et al. (Journal of Molecular Medicine, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

The use of genetic correlations to evaluate associations between SNP markers and quantitative traits - J. T. Brawner; S. K. Dillon; D. J. Lee; A. R. Meder; M. J. Dieters; Simon G. Southerton (Tree Genetics & Genomes, 2012)

Fire Accelerates Assimilation and Transfer of Photosynthetic Carbon from Plants to Soil Microbes in a Northern Peatland - Susan E. Ward; Nick J. Ostle; Simon Oakley; Helen Quirk; Andrew Stott; Peter A. Henrys; W. Andrew Scott; Richard D. Bardgett (Ecosystems, 2012)

Infectious mononucleosis and risk of breast cancer in a prospective study of women - J. Massa; A. Hamdan; K. C. Simon; K. Bertrand; G. Wulf; R. M. Tamimi; A. Ascherio (Cancer Causes & Control, 2012)

Structural dynamics of muscle protein phosphorylation - Brett A. Colson; Simon J. Gruber; David D. Thomas (Journal of Muscle Research and Cell Motility, 2012)

Viral latency drives ‘memory inflation’: a unifying hypothesis linking two hallmarks of cytomegalovirus infection - Christof K. Seckert; Marion Grießl; Julia K. Büttner; Sabine Scheller; Christian O. Simon; Kai A. Kropp; Angélique Renzaho; Birgit Kühnapfel; Natascha K. A. Grzimek; Matthias J. Reddehase (Medical Microbiology and Immunology, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Genome scans reveal candidate regions involved in the adaptation to host plant in the pea aphid complex - J. Jaquiéry; S. Stoeckel; P. Nouhaud; L. Mieuzet; F. Mahéo; F. Legeai; N. Bernard; A. Bonvoisin; R. Vitalis; J‐C. Simon (Molecular Ecology, 2012)
A major goal in evolutionary biology is to uncover the genetic basis of adaptation. Divergent selection exerted on ecological traits may result in adaptive population differentiation and reproductive isolation and affect differentially the level of genetic divergence along the genome. Genome‐wide scan of large sets of individuals from multiple populations is a powerful approach to identify loci or genomic regions under ecologically divergent selection. Here, we focused on the pea aphid, a species complex of divergent host races, to explore the organization of the genomic divergence associated with host plant adaptation and ecological speciation. We analysed 390 microsatellite markers located at variable distances from predicted genes in replicate samples of sympatric populations of the pea aphid collected on alfalfa, red clover and pea, which correspond to three common host‐adapted races reported in this species complex. Using a method that accounts for the hierarchical structure of our data set, we found a set of 11 outlier loci that show higher genetic differentiation between host races than expected under the null hypothesis of neutral evolution. Two of the outliers are close to olfactory receptor genes and three other nearby genes encoding salivary proteins. The remaining outliers are located in regions with genes of unknown functions, or which functions are unlikely to be involved in interactions with the host plant. This study reveals genetic signatures of divergent selection across the genome and provides an inventory of candidate genes responsible for plant specialization in the pea aphid, thereby setting the stage for future functional studies.

Abiotic drivers and plant traits explain landscape‐scale patterns in soil microbial communities - Franciska T. de Vries; Pete Manning; Jerry R. B. Tallowin; Simon R. Mortimer; Emma S. Pilgrim; Kathryn A. Harrison; Phil J. Hobbs; Helen Quirk; Bill Shipley; Johannes H. C. Cornelissen; Jens Kattge; Richard D. Bardgett (Ecology Letters, 2012)
The controls on aboveground community composition and diversity have been extensively studied, but our understanding of the drivers of belowground microbial communities is relatively lacking, despite their importance for ecosystem functioning. In this study, we fitted statistical models to explain landscape‐scale variation in soil microbial community composition using data from 180 sites covering a broad range of grassland types, soil and climatic conditions in England. We found that variation in soil microbial communities was explained by abiotic factors like climate, pH and soil properties. Biotic factors, namely community‐weighted means (CWM) of plant functional traits, also explained variation in soil microbial communities. In particular, more bacterial‐dominated microbial communities were associated with exploitative plant traits versus fungal‐dominated communities with resource‐conservative traits, showing that plant functional traits and soil microbial communities are closely related at the landscape scale.

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

Composition, age, and origin of the ~620 Ma Humr Akarim and Humrat Mukbid A-type granites: no evidence for pre-Neoproterozoic basement in the Eastern Desert, Egypt - Kamal A. Ali; Abdel-Kader M. Moghazi; Ayman E. Maurice; Sayed A. Omar; Qiang Wang; Simon A. Wilde; Ewais M. Moussa; William I. Manton; Robert J. Stern (International Journal of Earth Sciences, 2012)

Evaluation of PRDM9 variation as a risk factor for recurrent genomic disorders and chromosomal non-disjunction - Christelle Borel; Fanny Cheung; Helen Stewart; David A. Koolen; Christopher Phillips; N. Simon Thomas; Patricia A. Jacobs; Stephan Eliez; Andrew J. Sharp (Human Genetics, 2012)

Breaking with tradition: redefining measures for diet description with a case study of the Aleutian skate Bathyraja aleutica (Gilbert 1896) - Simon C. Brown; Joseph J. Bizzarro; Gregor M. Cailliet; David A. Ebert (Environmental Biology of Fishes, 2012)

Effects of stimulant drugs on actual and simulated driving: perspectives from four experimental studies conducted as part of the DRUID research consortium - J. G. Ramaekers; K. P. C. Kuypers; W. M. Bosker; K. A. Brookhuis; J. A. Veldstra; R. Simons; M. Martens; M. Hjälmdahl; Å. Forsman; A. Knoche (Psychopharmacology, 2012)

Use of linezolid in neonatal and pediatric inpatient facilities—results of a retrospective multicenter survey - A. Simon; E. Müllenborn; M. Prelog; W. Schenk; J. Holzapfel; F. Ebinger; A. Klabunde-Cherwon; J. Faber; A. H. Groll; K. Masjosthusmann; C. Dohna-Schwake; K. Beutel; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

International workshop on developing strategies for monitoring data-limited deepwater demersal line fisheries in the Pacific Ocean - Ashley J. Williams; Simon J. Nicol; Nokome Bentley; Paul J. Starr; Stephen J. Newman; Mike A. McCoy; Jeff Kinch; Peter G. Williams; Franck Magron; Graham M. Pilling; Ian Bertram; Mike Batty (Reviews in Fish Biology and Fisheries, 2012)

Characterisation of nine microsatellite loci in the caecilian amphibian Boulengerula uluguruensis (Gymnophiona), and their cross-species utility in three congeneric species - Christopher D. Barratt; Gavin J. Horsburgh; Deborah A. Dawson; David J. Gower; Mark Wilkinson; Simon P. Loader; Robert Jehle (Conservation Genetics Resources, 2012)

Assessing trophic position from nitrogen isotope ratios: effective calibration against spatially varying baselines - Paul Woodcock; David P. Edwards; Rob J. Newton; Felicity A. Edwards; Chey Vun Khen; Simon H. Bottrell; Keith C. Hamer (The Science of Nature, 2012)

Stable isotope ratios of a tropical marine predator: confounding effects of nutritional status during growth - Larisa Lee Cruz; Rona A. R. McGill; Simon J. Goodman; Keith C. Hamer (Marine Biology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Aspects of the reproductive biology of two archer fishes Toxotes chatareus, (Hamilton 1822) and Toxotes jaculatrix (Pallas 1767) - K. D. Simon; Y. Bakar; A. G. Mazlan; C. C. Zaidi; A. Samat; A. Arshad; S. E. Temple; N. J. Brown-Peterson (Environmental Biology of Fishes, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Yield losses in grain sorghum due to rust infection - Jodie A. White; Malcolm J. Ryley; Doug L. George; Gary A. Kong; Simon C. White (Australasian Plant Pathology, 2012)

Temporal and vertical variations of lipid biomarkers during a bottom ice diatom bloom in the Canadian Beaufort Sea: further evidence for the use of the IP25 biomarker as a proxy for spring Arctic sea ice - Thomas A. Brown; Simon T. Belt; Benoît Philippe; Christopher J. Mundy; Guillaume Massé; Michel Poulin; Michel Gosselin (Polar Biology, 2011)

Tracking and mapping sun-synchronous migrations and diel space use patterns of Haemulon sciurus and Lutjanus apodus in the U.S. Virgin Islands - Steven Hitt; Simon J. Pittman; Kerry A. Brown (Environmental Biology of Fishes, 2011)

The origin of high δ18O zircons: marbles, megacrysts, and metamorphism - Aaron J. Cavosie; John W. Valley; Noriko T. Kita; Michael J. Spicuzza; Takayuki Ushikubo; Simon A. Wilde (Contributions to Mineralogy and Petrology, 2011)

Rapid diagnosis of Clostridium difficile infection by multiplex real-time PCR - F. Barbut; M. Monot; A. Rousseau; S. Cavelot; T. Simon; B. Burghoffer; V. Lalande; J. Tankovic; J.-C. Petit; B. Dupuy; C. Eckert (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Pressure Buildup During CO2 Injection into a Closed Brine Aquifer - Simon A. Mathias; Gerardo J. González Martínez de Miguel; Kate E. Thatcher; Robert W. Zimmerman (Transport in Porous Media, 2011)

The Tyndall coastal simulator - Mustafa Mokrech; Susan Hanson; Robert J. Nicholls; Judith Wolf; Mike Walkden; Corentin M. Fontaine; Sophie Nicholson-Cole; Simon R. Jude; James Leake; Peter Stansby; Andrew R. Watkinson; Mark D. A. Rounsevell; et al. (Journal of Coastal Conservation, 2011)

Sleep and environmental context: interactive effects for memory - Scott A. Cairney; Simon J. Durrant; Hazel Musgrove; Penelope A. Lewis (Experimental Brain Research, 2011)

Hypoxia-induced oxidative DNA damage links with higher level biological effects including specific growth rate in common carp, Cyprinus carpio L. - Sanaa A. Mustafa; Sherain N. Al-Subiai; Simon J. Davies; Awadhesh N. Jha (Ecotoxicology, 2011)

Plant leaf roughness analysis by texture classification with generalized Fourier descriptors in a dimensionality reduction context - L. Journaux; J.-C. Simon; M. F. Destain; F. Cointault; J. Miteran; A. Piron (Precision Agriculture, 2011)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Germination requirements of Allanblackia parviflora seeds and early growth of seedlings - D. A. Ofori; T. Peprah; J. R. Cobbinah; H. A. Atchwerebour; F. Osabutey; Z. Tchoundjeu; A. J. Simons; R. Jamnadass (New Forests, 2011)

New tools to boost butterfly habitat quality in existing grass buffer strips - Robin J. Blake; Ben A. Woodcock; Duncan B. Westbury; Peter Sutton; Simon G. Potts (Journal of Insect Conservation, 2011)

Extinction vulnerability of coral reef fishes - Nicholas A. J. Graham; Pascale Chabanet; Richard D. Evans; Simon Jennings; Yves Letourneur; M. Aaron MacNeil; Tim R. McClanahan; Marcus C. Öhman; Nicholas V. C. Polunin; Shaun K. Wilson (Ecology Letters, 2011)

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Polymorphisms in oxidative stress and inflammation pathway genes, low-dose ionizing radiation, and the risk of breast cancer among US radiologic technologists - Sara J. Schonfeld; Parveen Bhatti; Elizabeth E. Brown; Martha S. Linet; Steven L. Simon; Robert M. Weinstock; Amy A. Hutchinson; Marilyn Stovall; Dale L. Preston; Bruce H. Alexander; Michele M. Doody; Alice J. Sigurdson (Cancer Causes & Control, 2010)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

The invasion route for an insect pest species: the tobacco aphid in the New World - F. A. ZEPEDA‐PAULO; J.‐C. SIMON; C. C. RAMÍREZ; E. FUENTES‐CONTRERAS; J. T. MARGARITOPOULOS; A. C. C. WILSON; C. E. SORENSON; L. M. BRIONES; R. AZEVEDO; D. V. OHASHI; C. LACROIX; L. GLAIS; et al. (Molecular Ecology, 2010)
Biological invasions are rapid evolutionary events in which populations are usually subject to a founder event during introduction followed by rapid adaptation to the new environment. Molecular tools and Bayesian approaches have shown their utility in exploring different evolutionary scenarios regarding the invasion routes of introduced species. We examined the situation for the tobacco aphid, Myzus persicae nicotianae , a recently introduced aphid species in Chile. Using seven microsatellite loci and approximate Bayesian computation, we studied populations of the tobacco aphid sampled from several American and European countries, identifying the most likely source populations and tracking the route of introduction to Chile. Our population genetic data are consistent with available historical information, pointing to an introduction route of the tobacco aphid from Europe and/or from other putative populations (e.g. Asia) with subsequent introduction through North America to South America. Evidence of multiple introductions to North America from different genetic pools, with successive loss of genetic diversity from Europe towards North America and a strong bottleneck during the southward introduction to South America, was also found. Additionally, we examined the special case of a widespread multilocus genotype that was found in all American countries examined. This case provides further evidence for the existence of highly successful genotypes or ‘superclones’ in asexually reproducing organisms.

Light colour influences the behaviour and stress physiology of captive tench (Tinca tinca) - Matthew A. G. Owen; Simon J. Davies; Katherine A. Sloman (Reviews in Fish Biology and Fisheries, 2010)

Synthesis of “Difficult” Fluorescence Quenched Substrates of Granzyme C - Susan E. Northfield; Kade D. Roberts; Simon J. Mountford; Richard A. Hughes; Dion Kaiserman; Matthew Mangan; Robert N. Pike; Phillip I. Bird; Philip E. Thompson (International Journal of Peptide Research and Therapeutics, 2010)

Sensory-motor equivalence: manual aiming in C6 tetraplegics following musculotendinous transfer surgery at the elbow - Mark A. Robinson; Spencer J. Hayes; Simon J. Bennett; Gabor J. Barton; Digby Elliott (Experimental Brain Research, 2010)

The structure of dopamine induced α-synuclein oligomers - Agata Rekas; Robert B. Knott; Anna Sokolova; Kevin J. Barnham; Keyla A. Perez; Colin L. Masters; Simon C. Drew; Roberto Cappai; Cyril C. Curtain; Chi L. L. Pham (European Biophysics Journal, 2010)

Effect of Local Cultural Context on the Success of Community‐Based Conservation Interventions - KERRY A. WAYLEN; ANKE FISCHER; PHILIP J. K. MCGOWAN; SIMON J. THIRGOOD; E. J. MILNER‐GULLAND (Conservation Biology, 2010)
Conservation interventions require evaluation to understand what factors predict success or failure. To date, there has been little systematic investigation of the effect of social and cultural context on conservation success, although a large body of literature argues it is important. We investigated whether local cultural context, particularly local institutions and the efforts of interventions to engage with this culture significantly influence conservation outcomes. We also tested the effects of community participation, conservation education, benefit provision, and market integration. We systematically reviewed the literature on community‐based conservation and identified 68 interventions suitable for inclusion. We used a protocol to extract and code information and evaluated a range of measures of outcome success (attitudinal, behavioral, ecological, and economic). We also examined the association of each predictor with each outcome measure and the structure of predictor covariance. Local institutional context influenced intervention outcomes, and interventions that engaged with local institutions were more likely to succeed. Nevertheless, there was limited support for the role of community participation, conservation education, benefit provision, and market integration on intervention success. We recommend that conservation interventions seek to understand the societies they work with and tailor their activities accordingly. Systematic reviews are a valuable approach for assessing conservation evidence, although sensitive to the continuing lack of high‐quality reporting on conservation interventions.

Efficacy of bacterially expressed dsRNA specific to different structural genes of white spot syndrome virus (WSSV) in protection of shrimp from WSSV infection - M Sarathi; M C Simon; C Venkatesan; J Thomas; M Ravi; N Madan; S Thiyagarajan; A S Sahul Hameed (Journal of Fish Diseases, 2010)

Ecological effects of longline fishing and climate change on the pelagic ecosystem off eastern Australia - Shane P. Griffiths; Jock W. Young; Matt J. Lansdell; Robert A. Campbell; John Hampton; Simon D. Hoyle; Adam Langley; Donald Bromhead; Michael G. Hinton (Reviews in Fish Biology and Fisheries, 2010)

Three new legumes endemic to the Marañón Valley, Perú - G. P. Lewis; C. E. Hughes; A. Daza Yomona; J. Solange Sotuyo; M. F. Simon (Kew Bulletin, 2010)

Historic fuel wood use in the Galápagos Islands: identification of charred remains - Cynthia A. Froyd; Jessica A. Lee; Atholl J. Anderson; Simon G. Haberle; Peter E. Gasson; Katherine J. Willis (Vegetation History and Archaeobotany, 2010)

Hybridization and polyploidy as drivers of continuing evolution and speciation in Sorbus - ASHLEY ROBERTSON; TIMOTHY C. G. RICH; ALEXANDRA M. ALLEN; LIBBY HOUSTON; CAT ROBERTS; JON R. BRIDLE; STEPHEN A. HARRIS; SIMON J. HISCOCK (Molecular Ecology, 2010)

Effects of acute tryptophan depletion in serotonin reuptake inhibitor-remitted patients with generalized anxiety disorder - Sean D. Hood; Dana A. Hince; Simon J. C. Davies; Spilios Argyropoulos; Hayley Robinson; John Potokar; David J. Nutt (Psychopharmacology, 2010)

Surge in sulphur and halogen degassing from Ambrym volcano, Vanuatu - Philipson Bani; Clive Oppenheimer; Vitchko I. Tsanev; Simon A. Carn; Shane J. Cronin; Rachel Crimp; Julie A. Calkins; Douglas Charley; Michel Lardy; Tjarda R. Roberts (Bulletin of Volcanology, 2009)

Major QTL for carrot color are positionally associated with carotenoid biosynthetic genes and interact epistatically in a domesticated × wild carrot cross - Brian J. Just; Carlos A. F. Santos; Brian S. Yandell; Philipp W. Simon (Theoretical and Applied Genetics, 2009)

Tracking volcanic sulfur dioxide clouds for aviation hazard mitigation - Simon A. Carn; Arlin J. Krueger; Nickolay A. Krotkov; Kai Yang; Keith Evans (Natural Hazards, 2009)

Reproductive biology and characterization of Allanblackia parviflora A. Chev. in Ghana - T. Peprah; D. A. Ofori; D. E. K. A. Siaw; S. D. Addo-Danso; J. R. Cobbinah; A. J. Simons; R. Jamnadass (Genetic Resources and Crop Evolution, 2009)

Fur seals at Macquarie Island: post-sealing colonisation, trends in abundance and hybridisation of three species - Simon David Goldsworthy; Jane McKenzie; Brad Page; Melanie L. Lancaster; Peter D. Shaughnessy; Louise P. Wynen; Susan A. Robinson; Kristian J. Peters; Alastair M. M. Baylis; Rebecca R. McIntosh (Polar Biology, 2009)

Identification of novel MHC class I sequences in pig-tailed macaques by amplicon pyrosequencing and full-length cDNA cloning and sequencing - Claire E. O’Leary; Roger W. Wiseman; Julie A. Karl; Benjamin N. Bimber; Simon M. Lank; Jennifer J. Tuscher; David H. O’Connor (Immunogenetics, 2009)

Movement signal choreography unaffected by receiver distance in the Australian Jacky lizard, Amphibolurus muricatus - Richard A. Peters; Simon J. Allen (Behavioral Ecology and Sociobiology, 2009)

Climate and agricultural context shape reproductive mode variation in an aphid crop pest - A. GILABERT; J.‐C. SIMON; L. MIEUZET; F. HALKETT; S. STOECKEL; M. PLANTEGENEST; C.‐A. DEDRYVER (Molecular Ecology, 2009)
In aphids, reproductive mode is generally assumed to be selected for by winter climate. Sexual lineages produce frost‐resistant eggs, conferring an advantage in regions with cold winters, while asexual lineages predominate in regions with mild winters. However, habitat and resource heterogeneities are known to exert a strong influence on sex maintenance and might modulate the effect of climate on aphid reproductive strategies. We carried out a hierarchical sampling in northern France to investigate whether reproductive mode variation of the aphid Rhopalosiphum padi is driven by winter climate conditions, by habitat and resource heterogeneities represented by a range of host plants or by both factors. We confirmed the coexistence in R. padi populations of two genetic clusters associated with distinct reproductive strategies. Asexual lineages predominated, whatever the surveyed year and location. However, we detected a between‐year variation in the local contribution of both clusters, presumably associated with preceding winter severity. No evidence for host‐driven niche differentiation was found in the field on six Poaceae among sexual and asexual lineages. Two dominant multilocus genotypes (∼70% of the sample), having persisted over a 10‐year period, were equally abundant on different plant species and locations, indicating their large ecological tolerance. Our results fit theoretical predictions of the influence of winter climate on the balance between sexual and asexual lineages. They also highlight the importance of current agricultural practices which seem to favour a small number of asexual generalist genotypes and their migration across large areas of monotonous environments.

Autism Overflows with Syntheses - Matthew K. Belmonte; Yoram S. Bonneh; Yael Adini; Portia E. Iversen; Natacha A. Akshoomoff; Tal Kenet; Christopher I. Moore; Helen J. Simon; John F. Houde; Michael M. Merzenich (Neuropsychology Review, 2009)

Visuomotor control of step descent: evidence of specialised role of the lower visual field - Matthew A. Timmis; Simon J. Bennett; John G. Buckley (Experimental Brain Research, 2009)

Large scale purification protocol for carnocin KZ 213 from Carnobacterium piscicola - C. Saint-Hubert; A. Durieux; E. Bodo; J.-P. Simon (Biotechnology Letters, 2009)

A comparison between CLNA and CLA effects on body fat, serum parameters and liver composition - J. Miranda; A. Fernández-Quintela; M. T. Macarulla; I. Churruca; C. García; V. M. Rodríguez; E. Simon; M. P. Portillo (Journal of Physiology and Biochemistry, 2009)

A Neisseria meningitidis NMB1966 mutant is impaired for invasion of respiratory epithelial cells, survival in human blood and for virulence in vivo - Ming-Shi Li; Noel Y. S. Chow; Sunita Sinha; Denise Halliwell; Michelle Finney; Andrew R. Gorringe; Mark W. Watson; J. Simon Kroll; Paul R. Langford; Steven A. R. Webb (Medical Microbiology and Immunology, 2009)

Diversity in Current Ecological Thinking: Implications for Environmental Management - Susan A. Moore; Tabatha J. Wallington; Richard J. Hobbs; Paul R. Ehrlich; C. S. Holling; Simon Levin; David Lindenmayer; Claudia Pahl-Wostl; Hugh Possingham; Monica G. Turner; Mark Westoby (Environmental Management, 2009)

Host range expansion of an introduced insect pest through multiple colonizations of specialized clones - J. PECCOUD; C. C. FIGUEROA; A. X. SILVA; C. C. RAMIREZ; L. MIEUZET; J. BONHOMME; S. STOECKEL; M. PLANTEGENEST; J.‐C. SIMON (Molecular Ecology, 2008)
Asexuality confers demographic advantages to invasive taxa, but generally limits adaptive potential for colonizing of new habitats. Therefore, pre‐existing adaptations and habitat tolerance are essential in the success of asexual invaders. We investigated these key factors of invasiveness by assessing reproductive modes and host‐plant adaptations in the pea aphid, Acyrthosiphon pisum , a pest recently introduced into Chile. The pea aphid encompasses lineages differing in their reproductive mode, ranging from obligatory cyclical parthenogenesis to fully asexual reproduction. This species also shows variation in host use, with distinct biotypes specialized on different species of legumes as well as more polyphagous populations. In central Chile, microsatellite genotyping of pea aphids sampled on five crops and wild legumes revealed three main clonal genotypes, which showed striking associations with particular host plants rather than sampling locations. Phenotypic analyses confirmed their strong host specialization and demonstrated parthenogenesis as their sole reproductive mode. The genetic relatedness of these clonal genotypes with corresponding host‐specialized populations from the Old World indicated that each clone descended from a particular Eurasian biotype, which involved at least three successful introduction events followed by spread on different crops. This study illustrates that multiple introductions of highly specialized clones, rather than local evolution in resource use and/or selection of generalist genotypes, can explain the demographic success of a strictly asexual invader.

Genetic structuring of important medicinal species of genus Warburgia as revealed by AFLP analysis - A. Muchugi; G. M. Muluvi; R. Kindt; C. A. C. Kadu; A. J. Simons; R. H. Jamnadass (Tree Genetics & Genomes, 2008)

Mortalities caused by off-road vehicles (ORVs) to a key member of sandy beach assemblages, the surf clam Donax deltoides - Thomas A. Schlacher; Luke M. C. Thompson; Simon J. Walker (Hydrobiologia, 2008)

Ti-in-zircon thermometry: applications and limitations - Bin Fu; F. Zeb Page; Aaron J. Cavosie; John Fournelle; Noriko T. Kita; Jade Star Lackey; Simon A. Wilde; John W. Valley (Contributions to Mineralogy and Petrology, 2008)

Polyclonal cytomegalovirus-specific antibodies not only prevent virus dissemination from the portal of entry but also inhibit focal virus spread within target tissues - Nikolaus Wirtz; Sina I. Schader; Rafaela Holtappels; Christian O. Simon; Niels A. W. Lemmermann; Matthias J. Reddehase; Jürgen Podlech (Medical Microbiology and Immunology, 2008)

Quetiapine augmentation of paroxetine CR for the treatment of refractory generalized anxiety disorder: preliminary findings - Naomi M. Simon; Kathryn M. Connor; Richard T. LeBeau; Elizabeth A. Hoge; John J. Worthington; Wei Zhang; Jonathan R. T. Davidson; Mark H. Pollack (Psychopharmacology, 2008)

A new mechanism of dominance in hypophosphatasia: the mutated protein can disturb the cell localization of the wild-type protein - A. S. Lia-Baldini; I. Brun-Heath; C. Carrion; B. Simon-Bouy; J. L. Serre; M. E. Nunes; E. Mornet (Human Genetics, 2008)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Spatial heterogeneity of epibenthos on artificial reefs: fouling communities in the early stages of colonization on an East Australian shipwreck - Simon J. Walker; Thomas A. Schlacher; Monika A. Schlacher‐Hoenlinger (Marine Ecology, 2007)
Artificial reefs are spatially complex habitats and serve as good model systems to study patterns of community succession and the response of epibiota to environmental clines over small spatial scales. Here, we quantified spatial heterogeneity in community composition and diversity of fouling communities across a number of environmental gradients that included water depth, surface orientation of habitats, exposure to currents, and shelter. Assemblage structure was quantified by spatially replicated photo transects on a recently scuttled large navy ship off the East Australian coast, lying in 27 m of water. A rich assemblage of epifauna had colonized the wreck within a year, dominated by barnacles, sponges and bryozoans. Community structure varied significantly over small spatial scales of meters to tens of meters. Depth, surface orientation and exposure were the major environmental drivers. Assemblages were substantially less diverse and abundant on the deepest (23 m near the seafloor) part of the hull with residual antifouling paint, on sheltered surfaces inside the wreck, and on the sediment‐laden horizontal surfaces. Overall, the wrecks’ habitat complexity corresponds with small‐scale heterogeneity in the fouling communities. This study supports the notion that wrecks enhance local diversity and biomass within the habitat mosaic of their location, and habitat complexity may be an important mechanism for this, as demonstrated by the large spatial variability in the assemblages documented here.

Piperacillin-tazobactam in pediatric cancer patients younger than 25 months: a retrospective multicenter survey - A. Simon; T. Lehrnbecher; U. Bode; A. H. Groll; L. Tramsen; R. Wieland; E. Molitor; G. Fleischhack; H. J. Laws (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

PIP2-dependent inhibition of M-type (Kv7.2/7.3) potassium channels: direct on-line assessment of PIP2 depletion by Gq-coupled receptors in single living neurons - Simon Hughes; Stephen J. Marsh; Andrew Tinker; David A. Brown (Pflügers Archiv - European Journal of Physiology, 2007)

Lag Effects in the Impacts of Mass Coral Bleaching on Coral Reef Fish, Fisheries, and Ecosystems - NICHOLAS A. J. GRAHAM; SHAUN K. WILSON; SIMON JENNINGS; NICHOLAS V. C. POLUNIN; JAN ROBINSON; JUDE P. BIJOUX; TIM M. DAW (Conservation Biology, 2007)
Recent episodes of coral bleaching have led to wide‐scale loss of reef corals and raised concerns over the effectiveness of existing conservation and management efforts. The 1998 bleaching event was most severe in the western Indian Ocean, where coral declined by up to 90% in some locations. Using fisheries‐independent data, we assessed the long‐term impacts of this event on fishery target species in the Seychelles, the overall size structure of the fish assemblage, and the effectiveness of two marine protected areas (MPAs) in protecting fish communities. The biomass of fished species above the size retained in fish traps changed little between 1994 and 2005, indicating no current effect on fishery yields. Biomass remained higher in MPAs, indicating they were effective in protecting fish stocks. Nevertheless, the size structure of the fish communities, as described with size‐spectra analysis, changed in both fished areas and MPAs, with a decline in smaller fish ( 45 cm). We believe this represents a time‐lag response to a reduction in reef structural complexity brought about because fishes are being lost through natural mortality and fishing, and are not being replaced by juveniles. This effect is expected to be greater in terms of fisheries productivity and, because congruent patterns are observed for herbivores, suggests that MPAs do not offer coral reefs long‐term resilience to bleaching events. Corallivores and planktivores declined strikingly in abundance, particularly in MPAs, and this decline was associated with a similar pattern of decline in their preferred corals. We suggest that climate‐mediated disturbances, such as coral bleaching, be at the fore of conservation planning for coral reefs.

Combining DNA and morphological analyses of faecal samples improves insight into trophic interactions: a case study using a generalist predator - Ruth M. Casper; Simon N. Jarman; Nicholas J. Gales; Mark A. Hindell (Marine Biology, 2007)

Lower reproductive success in hybrid fur seal males indicates fitness costs to hybridization - MELANIE L. LANCASTER; COREY J. A. BRADSHAW; SIMON D. GOLDSWORTHY; PAUL SUNNUCKS (Molecular Ecology, 2007)
Hybridization among organisms can potentially contribute to the processes of evolution, but this depends on the fitness of hybrids relative to parental species. A small, recently formed population of fur seals on subantarctic Macquarie Island contains a high proportion of hybrids (17–30%) derived from combinations of three parental species: Antarctic, subantarctic and New Zealand fur seals. Mitochondrial control‐region data (restriction fragment length polymorphisms) and nine microsatellites were used to determine the species composition of breeding adults, and hybrid male fitness was measured by comparing reproductive success (number of genetically inferred paternities) of hybrid and pure‐species territory males over 6 years. No correlations were found between male reproductive success and three genetic measures of outbreeding, but this may be due to a relatively small number of dominant males analysed. Territory males fathered 63% of pups, but hybrid males had lower reproductive success than pure‐species males despite having the same ability to hold territories. A greater proportion of females in hybrid male territories conceived extra‐territorially than those in territories of pure‐species males, and most (70 of 82) mated with conspecifics. This suggests the presence of reproductive isolating mechanisms that promote positive assortative mating and reduce the production of hybrid offspring. Although we found no evidence for male sterility in the population, mechanisms that reduce lifetime reproductive success may act to decrease the frequency of hybrids. Our study has identified a disadvantage of hybridization — reduced reproductive success of hybrid sons — that may be contributing to the persistence of pure lineages at Macquarie Island and the temporal decline in hybridization observed there.

Hypoxia tolerance associated with activity reduction is a key adaptation for Laternula elliptica seasonal energetics - Simon A. Morley; Lloyd S. Peck; Andrew J. Miller; Hans O. Pörtner (Oecologia, 2007)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Phase-reversed seabed reflections in seismic data: examples related to mud volcanoes from the South Caspian Sea - Robert J. Evans; Simon A. Stewart; Richard J. Davies (Geo-Marine Letters, 2007)

First-year growth response of cold-stored, nursery-grown aspen planting stock - Lee A. Martens; Simon M. Landhäusser; Victor J. Lieffers (New Forests, 2007)

Production, formulation and antagonistic activity of the biocontrol like-yeast Aureobasidium pullulans against Penicillium expansum - R. Mounir; A. Durieux; E. Bodo; C. Allard; J.-P. Simon; E.-H. Achbani; S. El-Jaafari; A. Douira; M.-H. Jijakli (Biotechnology Letters, 2007)

Carotenoid biosynthesis structural genes in carrot (Daucus carota): isolation, sequence-characterization, single nucleotide polymorphism (SNP) markers and genome mapping - B. J. Just; C. A. F. Santos; M. E. N. Fonseca; L. S. Boiteux; B. B. Oloizia; P. W. Simon (Theoretical and Applied Genetics, 2007)

Characterization of a cyanobacterial-like uptake [NiFe] hydrogenase: EPR and FTIR spectroscopic studies of the enzyme from Acidithiobacillus ferrooxidans - Olga Schröder; Boris Bleijlevens; Thyra E. de Jongh; Zhujun Chen; Tianshu Li; Jörg Fischer; Jochen Förster; Cornelius G. Friedrich; Kimberly A. Bagley; Simon P. J. Albracht; Wolfgang Lubitz (JBIC Journal of Biological Inorganic Chemistry, 2007)

Performance of recalibration systems for GCM forecasts for southern Africa - Mxolisi E. Shongwe; Willem A. Landman; Simon J. Mason (International Journal of Climatology, 2006)
Two regression‐based methods that recalibrate the ECHAM4.5 general circulation model (GCM) output during austral summer have been developed for southern Africa, and their performance assessed over a 12‐year retroactive period 1989/90–2000/01. A linear statistical model linking near‐global sea‐surface temperatures (SSTs) to regional rainfall has also been developed. The recalibration technique is model output statistics (MOS) using principal components regression (PCR) and canonical correlation analysis (CCA) to statistically link archived records of the GCM to regional rainfall over much of Africa, south of the equator. The predictability of anomalously dry and wet conditions over each rainfall region during December–February (DJF) using the linear statistical model and MOS models has been quantitatively evaluated. The MOS technique outperforms the raw‐GCM ensembles and the linear statistical model. Neither the PCR‐MOS nor the CCA‐MOS models show clear superiority over the other, probably because the two methods are closely related. The need to recalibrate GCM predictions at regional scales to improve their skill at smaller spatial scales is further demonstrated in this paper. Copyright © 2006 Royal Meteorological Society.

Patterns of Species Richness at Varying Scales in Western Kenya: Planning for Agroecosystem Diversification - R. Kindt; P. Van Damme; A. J. Simons (Biodiversity and Conservation, 2006)

Molecular Cloning of Echis ocellatus Disintegrins Reveals Non-Venom-Secreted Proteins and a Pathway for the Evolution of Ocellatusin - Paula Juárez; Simon C. Wagstaff; Libia Sanz; Robert A. Harrison; Juan J. Calvete (Journal of Molecular Evolution, 2006)

Predicting Pathogen Introduction: West Nile Virus Spread to Galápagos - A. MARM KILPATRICK; PETER DASZAK; SIMON J. GOODMAN; HELMUTH ROGG; LAURA D. KRAMER; VIRNA CEDEÑO; ANDREW A. CUNNINGHAM (Conservation Biology, 2006)
Emerging infectious diseases are a key threat to conservation and public health, yet predicting and preventing their emergence is notoriously difficult. We devised a predictive model for the introduction of a zoonotic vector‐borne pathogen by considering each of the pathways by which it may be introduced to a new area and comparing the relative risk of each pathway. This framework is an adaptation of pest introduction models and estimates the number of infectious individuals arriving in a location and the duration of their infectivity. We used it to determine the most likely route for the introduction of West Nile virus to Galápagos and measures that can be taken to reduce the risk of introduction. The introduction of this highly pathogenic virus to this unique World Heritage Site could have devastating consequences, similar to those seen following introductions of pathogens into other endemic island faunas. Our model identified the transport of mosquitoes on airplanes as the highest risk for West Nile virus introduction. Pathogen dissemination through avian migration and the transportation of day‐old chickens appeared to be less important pathways. Infected humans and mosquitoes transported in sea containers, in tires, or by wind all represented much lower risk. Our risk‐assessment framework has broad applicability to other pathogens and other regions and depends only on the availability of data on the transport of goods and animals and the epidemiology of the pathogen.

The first gene-based map of Lupinus angustifolius L.-location of domestication genes and conserved synteny with Medicago truncatula - Matthew N. Nelson; Huyen T. T. Phan; Simon R. Ellwood; Paula M. Moolhuijzen; James Hane; Angela Williams; Clare E. O‘Lone; John Fosu-Nyarko; Marie Scobie; Mehmet Cakir; Michael G. K. Jones; Matthew Bellgard; et al. (Theoretical and Applied Genetics, 2006)

Molecular Cloning of Disintegrin-like Transcript BA-5A from a Bitis arietans Venom Gland cDNA Library: A Putative Intermediate in the Evolution of the Long-Chain Disintegrin Bitistatin - Paula Juárez; Simon C. Wagstaff; Jenny Oliver; Libia Sanz; Robert A. Harrison; Juan J. Calvete (Journal of Molecular Evolution, 2006)

Recovery of Nuclease Produced by Lactococcus Lactis Using Expanded Bed Ion Exchange Chromatography - E. Bodo; A. Durieux; C. Saint-Hubert; R. Lavallée; J-M Boufflette; J. -P. Simon (Biotechnology Letters, 2006)

Planning tree species diversification in Kenya based on differences in tree species composition between farms. II. Analysis of tree niches. - R. Kindt; P. Van Damme; A. J. Simons; H. Beeckman (Agroforestry Systems, 2006)

Planning tree species diversification in Kenya based on differences in tree species composition between farms. I. Analysis of tree uses - R. Kindt; P. Van Damme; A. J. Simons; H. Beeckman (Agroforestry Systems, 2006)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

High resolution mapping of chromosomal regions controlling resistance to gastrointestinal nematode infections in an advanced intercross line of mice - Jerzy M. Behnke; Fuad A. Iraqi; John M. Mugambi; Simon Clifford; Sonal Nagda; Derek Wakelin; Stephen J. Kemp; R. Leyden Baker; John P. Gibson (Mammalian Genome, 2006)

Solubility and partitioning of water in synthetic forsterite and enstatite in the system MgO–SiO2–H2O±Al2O3 - Kevin J. Grant; Simon C. Kohn; Richard A. Brooker (Contributions to Mineralogy and Petrology, 2006)

Stimulus-invariant processing and spectrotemporal reverse correlation in primary auditory cortex - David J. Klein; Jonathan Z. Simon; Didier A. Depireux; Shihab A. Shamma (Journal of Computational Neuroscience, 2006)

Evidence that Soil Carbon Pool Determines Susceptibility of Semi-Natural Ecosystems to Elevated Nitrogen Leaching - Christopher D. Evans; Brian Reynolds; Alan Jenkins; Rachel C. Helliwell; Christopher J. Curtis; Christine L. Goodale; Robert C. Ferrier; Bridget A. Emmett; Michael G. Pilkington; Simon J. M. Caporn; Jacky A. Carroll; David Norris; et al. (Ecosystems, 2006)

Tree Diversity in Western Kenya: Using Profiles to Characterise Richness and Evenness - R. Kindt; P. Van Damme; A. J. Simons (Biodiversity and Conservation, 2006)

Evidence for novel loci for late-onset Parkinson’s disease in a genetic isolate from the Netherlands - Aida M. Bertoli-Avella; Marieke C. J. Dekker; Yurii S. Aulchenko; Jeanine J. Houwing-Duistermaat; Erik Simons; Leon Testers; Luba M. Pardo; Tessa A. M. Rademaker; Pieter J. L. M. Snijders; John C. van Swieten; Vincenzo Bonifati; Peter Heutink; et al. (Human Genetics, 2006)

Community Associations of Chalk Grassland Leafhoppers (Hemiptera: Auchenorrhyncha): Conclusions for Habitat Conservation - Norbert Maczey; Greg J. Masters; John A. Hollier; Simon R. Mortimer; Valerie K. Brown (Journal of Insect Conservation, 2005)

Species Review of Amphibian Extinction Risks in Madagascar: Conclusions from the Global Amphibian Assessment - FRANCO ANDREONE; JOHN E. CADLE; NEIL COX; FRANK GLAW; RONALD A. NUSSBAUM; CHRISTOPHER J. RAXWORTHY; SIMON N. STUART; DENIS VALLAN; MIGUEL VENCES (Conservation Biology, 2005)
We assessed the extinction risks of Malagasy amphibians by evaluating their distribution, occurrence in protected areas, population trends, habitat quality, and prevalence in commercial trade. We estimated and mapped the distribution of each of the 220 described Malagasy species and applied, for the first time, the IUCN Red List categories and criteria to all species described at the time of the assessment. Nine species were categorized as critically endangered, 21 as endangered, and 25 as vulnerable. The most threatened species occur on the High Plateau and/or have been subjected to overcollection for the pet trade, but restricted extent of occurrence and ongoing habitat destruction were identified as the most important factors influencing extinction threats. The two areas with the majority of threatened species were the northern Tsaratanana‐Marojejy‐Masoala highlands and the southeastern Anosy Mountains. The current system of protected areas includes 82% of the threatened amphibian species. Of the critically endangered species, 6 did not occur in any protected area. For conservation of these species we recommend the creation of a reserve for the species of the Mantella aurantiaca group, the inclusion of two Scaphiophryne species in the Convention on the International Trade in Endangered Species Appendix II, and the suspension of commercial collecting for Mantella cowani. Field surveys during the last 15 years reveal no pervasive extinction of Malagasy amphibians resulting from disease or other agents, as has been reported in some other areas of the world.

Regulation of Harvest-induced Senescence in Broccoli (Brassica oleracea var. italica) by Cytokinin, Ethylene, and Sucrose - Nigel E. Gapper; Simon A. Coupe; Marian J. McKenzie; Ben K. Sinclair; Ross E. Lill; Paula E. Jameson (Journal of Plant Growth Regulation, 2005)

Evidence for a novel glaucoma locus at chromosome 3p21-22 - Paul N. Baird; Simon J. Foote; David A. Mackey; Jamie Craig; Terence P. Speed; Alexandre Bureau (Human Genetics, 2005)

Development of anonymous cDNA microarrays to study changes to the Senecio floral transcriptome during hybrid speciation - MATTHEW J. HEGARTY; JOANNA M. JONES; IAN D. WILSON; GARY L. BARKER; JANE A. COGHILL; PATRICIA SANCHEZ‐BARACALDO; GUOQING LIU; RICHARD J. A. BUGGS; RICHARD J. ABBOTT; KEITH J. EDWARDS; SIMON J. HISCOCK (Molecular Ecology, 2005)
Interspecific hybridization is an important process through which abrupt speciation can occur. In recent years, genetic changes associated with hybrid speciation have been identified through a variety of techniques, including AFLP/SSR mapping, GISH/FISH and cDNA‐AFLP differential display. However, progress in using microarray technology to analyse whole genome/transcriptome changes associated with hybrid speciation has been limited due to the lack of extensive sequence data for many hybrid species and the difficulties in extrapolating results from commercially available microarrays for model species onto nonmodel hybrid taxa. Increasingly therefore researchers studying nonmodel systems are turning to the development of ‘anonymous’ cDNA microarrays, where the time and cost of producing microarrays is reduced by printing unsequenced cDNA clones, and sequencing only those clones that display interesting expression patterns. Here we describe the creation, testing and preliminary use of anonymous cDNA microarrays to study changes in floral transcriptome associated with allopolyploid speciation in the genus Senecio. We report a comparison of gene expression between the allohexaploid hybrid, Senecio cambrensis , its parental taxa Senecio squalidus (diploid) and Senecio vulgaris (tetraploid), and the intermediate triploid (sterile) hybrid Senecio × baxteri . Anonymous microarray analysis revealed dramatic differences in floral gene expression between these four taxa and demonstrates the power of this technique for studies of the genetic impact of hybridization in nonmodel flowering plants.

Efficient and fast targeted production of murine models based on ENU mutagenesis - M. Augustin; R. Sedlmeier; T. Peters; U. Huffstadt; E. Kochmann; D. Simon; M. Schöniger; S. Garke-Mayerthaler; J. Laufs; M. Mayhaus; S. Franke; M. Klose; et al. (Mammalian Genome, 2005)

The life history responses of the abalone pest, Terebrasabella heterouncinata, under natural and aquaculture conditions - Carol A. Simon; Horst Kaiser; Peter J. Britz (Marine Biology, 2005)

Indices of bird‐habitat preference from field surveys of birds and remote sensing of land cover: a study of south‐eastern England with wider implications for conservation and biodiversity assessment - Robin M. Fuller; Bernard J. Devereux; Simon Gillings; Gabriel S. Amable; Ross A. Hill (Global Ecology and Biogeography, 2005)
Aim This paper describes the development of novel indices of bird‐habitat preference to examine bird species’ use of habitats and their distributions relative to habitats. It assesses the implications for bird conservation regionally and the scope for biodiversity assessments generally. Location A 200 km by 400 km area of farmland with seminatural and urban areas, covering south‐eastern England. Methods Cluster analysis was used to link birds to landscapes. Cluster centroid coordinate values were processed to derive indices of bird‐habitat preference. Further developments assessed the relative values of individual habitats for birds. Results Clustering objectively linked birds to landscapes. Maps of the clusters showed strong regional patterns associated with distinctive habitat assemblages. Derived indices related bird species directly to individual habitats and habitats to birds. Even rare species and scarce habitats showed successful linkages, often to each other. Objective corroboration strongly supported the associations of coastal, wetland, urban and woodland birds and habitats; but, it suggested that farmland birds, whose numbers have nearly halved since 1977, may prefer alternative habitats. Main conclusions Land cover maps from remote sensing provide an effective way to link birds to habitats and vice versa . Thus, generalized habitat maps might be used to extrapolate localized or sample‐based bird observations or the results of autecological studies, helping to predict and understand bird distributions in the wider countryside. The weak links between farmland birds and farmland habitats in a region dominated by farming, suggests that reasons for the decline in farmland birds may be deep seated and thus hard to reverse. The procedures described are repeatable elsewhere and applicable more generally to evaluate landscapes and biodiversity. It is suggested that remote sensing could rarely be bettered as a means of assessing habitats, comprehensively, over wide areas, in most parts of the world.

Isolation and characterization of a polymorphic stigma-specific class III peroxidase gene from Senecio squalidus L. (Asteraceae) - Stephanie M. McInnis; Liliana M. Costa; José F. Gutiérrez-Marcos; Catherine A. Henderson; Simon J. Hiscock (Plant Molecular Biology, 2005)

Do Farm Characteristics Explain Differences in Tree Species Diversity among Western Kenyan Farms? - R. Kindt; A. J. Simons; P. Van Damme (Agroforestry Systems, 2004)

Differential regulation of caspase-3 by pharmacological and developmental stimuli as demonstrated using humanised caspase-3 mice - L. E. Kerr; J-L. A. Birse-Archbold; A. Simon; N. Logan; F. Scott; G. Carlson; D. W. Nicholson; J. S. Kelly; J. Sharkey (Apoptosis, 2004)

Cetirizine from topical phosphatidylcholine-hydrogenated liposomes: Evaluation of peripheral antihistaminic activity and systemic absorption in a rabbit model - Abeer A. W. Elzainy; Xiaochen Gu; F. Estelle R. Simons; Keith J. Simons (The AAPS Journal, 2004)

The activation of the [NiFe]-hydrogenase from Allochromatium vinosum. An infrared spectro-electrochemical study - Boris Bleijlevens; Fleur A. van Broekhuizen; Antonio L. De Lacey; Winfried Roseboom; Victor M. Fernandez; Simon P. J. Albracht (JBIC Journal of Biological Inorganic Chemistry, 2004)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Distribution dynamics of a great bustard metapopulation throughout a decade: influence of conspecific attraction and recruitment - Juan C. Alonso; Carlos A. Martín; Javier A. Alonso; Carlos Palacín; Marina Magaña; Simon J. Lane (Biodiversity and Conservation, 2004)

Observations on the distribution and abundance of carp and native fish, and their responses to a habitat restoration trial in the Murray River, Australia - Simon J. Nicol; Jason A. Lieschke; Jarod P. Lyon; John D. Koehn (New Zealand Journal of Marine and Freshwater Research, 2004)
A native fish strategy has been initiated to rehabilitate native fish populations in the Murray‐Darling Basin, Australia. The reintroduction of large woody debris (LWD) into the Basin's large lowland rivers is one of the restoration activities in the strategy. The results from three separate studies undertaken on the Murray River between Yarrawonga and Tocumwal are presented on the relationship between carp (Cyprinus carpio) , native species, and LWD to examine whether native species and carp compete for LWD habitat. The first study reports on the relative abundance of carp and native fish in a river reach. Since 1995 carp abundance has declined, whereas the abundance of native fish populations has remained relatively constant providing little support for the hypothesis that competition for LWD habitat is having effects at the population level effects. The second study reports on the relationship between LWD, river channel position, and its use as habitat by carp and native species. A statistically significant relationship was observed between native fish, LWD, the location within a meander, and curvature of the meander. There was no statistically significant relation between carp and any of these parameters indicating that carp utilise a variety of riverine habitats, whereas native species were strongly associated with LWD. The third study reports on an experiment that tested the response of carp to the placement of new LWD habitat. The response from carp was statistically inconclusive. The combination of these studies suggest that it is unlikely that carp and native species are directly competing for LWD habitat and it is unlikely that carp will inundate restored LWD habitats and preclude native species.

Small and intermediate conductance Ca 2+ -activated K + channels confer distinctive patterns of distribution in human tissues and differential cellular localisation in the colon and corpus cavernosum - Mao Xiang Chen; Shelby A. Gorman; Bill Benson; Kuljit Singh; J. Paul Hieble; Martin C. Michel; Simon N. Tate; Derek J. Trezise (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Immunocytochemical evidence for an NMDA1 receptor subunit in dissociated cells of Hydra vulgaris - A. A. Scappaticci; R. Jacques; J. E. Carroll; L. A. Hufnagel; G. Kass-Simon (Cell and Tissue Research, 2004)

Variation in wood density determines spatial patterns inAmazonian forest biomass - Timothy R. Baker; Oliver L. Phillips; Yadvinder Malhi; Samuel Almeida; Luzmila Arroyo; Anthony Di Fiore; Terry Erwin; Timothy J. Killeen; Susan G. Laurance; William F. Laurance; Simon L. Lewis; Jon Lloyd; et al. (Global Change Biology, 2004)
Uncertainty in biomass estimates is one of the greatest limitations to models of carbon flux in tropical forests. Previous comparisons of field‐based estimates of the aboveground biomass (AGB) of trees greater than 10 cm diameter within Amazonia have been limited by the paucity of data for western Amazon forests, and the use of site‐specific methods to estimate biomass from inventory data. In addition, the role of regional variation in stand‐level wood specific gravity has not previously been considered. Using data from 56 mature forest plots across Amazonia, we consider the relative roles of species composition (wood specific gravity) and forest structure (basal area) in determining variation in AGB. Mean stand‐level wood specific gravity, on a per stem basis, is 15.8% higher in forests in central and eastern, compared with northwestern Amazonia. This pattern is due to the higher diversity and abundance of taxa with high specific gravity values in central and eastern Amazonia, and the greater diversity and abundance of taxa with low specific gravity values in western Amazonia. For two estimates of AGB derived using different allometric equations, basal area explains 51.7% and 63.4%, and stand‐level specific gravity 45.4% and 29.7%, of the total variation in AGB. The variation in specific gravity is important because it determines the regional scale, spatial pattern of AGB. When weighting by specific gravity is included, central and eastern Amazon forests have significantly higher AGB than stands in northwest or southwest Amazonia. The regional‐scale pattern of species composition therefore defines a broad gradient of AGB across Amazonia.

The above‐ground coarse wood productivity of 104 Neotropical forest plots - Yadvinder Malhi; Timothy R. Baker; Oliver L. Phillips; Samuel Almeida; Esteban Alvarez; Luzmilla Arroyo; Jerome Chave; Claudia I. Czimczik; Anthony Di Fiore; Niro Higuchi; Timothy J. Killeen; Susan G. Laurance; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long‐lived carbon pools (wood) and shorter‐lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above‐ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree‐size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above‐ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha −1 a −1 ) across the Neotropical plots, with a mean value of 3.1 Mg C ha −1 a −1 . There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above‐ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation.

Predicting Forest Attributes in Southeast Alaska Using Artificial Neural Networks - Simon A. Corne; Stephen J. Carver; William E. Kunin; Jack J. Lennon; Willem W. S. van van Hees (Forest Science, 2004)
Artificial neural network (ANN) methods are used to predict forest characteristics. The data source is the Southeast Alaska (SEAK) Grid Inventory, a ground survey compiled by the USDA Forest Service at several thousand sites. The main objective of this article is to predict characteristics at unsurveyed locations between grid sites. A secondary objective is to evaluate the relative performance of different ANNs. Data from the grid sites are used to train six ANNs: multilayer perceptron, fuzzy ARTMAP, probabilistic, generalized regression, radial basis function, and learning vector quantization. A classification and regression tree method is used for comparison. Topographic variables are used to construct models: latitude and longitude coordinates, elevation, slope, and aspect. The models classify three forest characteristics: crown closure, species land cover, and tree size/structure. Models are constructed using n-fold cross-validation. Predictive accuracy is calculated using a method that accounts for the influence of misclassification as well as measuring correct classifications. The probabilistic and generalized regression networks are found to be the most accurate. The predictions of the ANN models are compared with a classification of the Tongass national forest in southeast Alaska based on the interpretation of satellite imagery and are found to be of similar accuracy. FOR. SCI. 50(2):259–276.

Boron isotopic variations in hydrous rhyolitic melts: a case study from Long Valley, California - A. K. Schmitt; J. I. Simon (Contributions to Mineralogy and Petrology, 2004)

Boron isotopic variations in hydrous rhyolitic melts: a case study from Long Valley, California - A. K. Schmitt; J. I. Simon (Contributions to Mineralogy and Petrology, 2004)

Hydrocarbon distribution and colony odour homogenisation in Pachycondyla apicalis - V. Soroker; C. Lucas; T. Simon; A. Hefetz; D. Fresneau; J. L. Durand (Insectes Sociaux, 2003)

Sequence variation in the CHAT locus shows no association with late-onset Alzheimer's disease - Denise Harold; Timothy Peirce; Valentina Moskvina; Simon Lovestone; John Powell; Catherine Foy; Nicola Archer; Sarah Walter; Amanda Edmonson; Stephen McIlroy; David Craig; Peter A. Passmore; et al. (Human Genetics, 2003)

In vitro regeneration of Echinacea pallida from leaf explants - A. R. Koroch; J. Kapteyn; H. R. Juliani; J. E. Simon (In Vitro Cellular & Developmental Biology - Plant, 2003)

Analysis of 15 primary open-angle glaucoma families from Australia identifies a founder effect for the Q368STOP mutation of myocilin - Paul N. Baird; Jamie E. Craig; Andrea J. Richardson; Maree A. Ring; Pamela Sim; Sue Stanwix; Simon J. Foote; David A. Mackey (Human Genetics, 2003)

Phylogenetics of rat inbred strains - Michael A. Thomas; Chin-Fu Chen; Michael I. Jensen-Seaman; Peter J. Tonellato; Simon N. Twigger (Mammalian Genome, 2003)

Assessment of Injury to Fish and Wildlife Resources in the Grand Calumet River and Indiana Harbor Area of Concern, USA - D. D. MacDonald; C. G. Ingersoll; D. E. Smorong; R. A. Lindskoog; D. W. Sparks; J. R. Smith; T. P. Simon; M. A. Hanacek (Archives of Environmental Contamination and Toxicology, 2002)

An Assessment of Injury to Sediments and Sediment-Dwelling Organisms in the Grand Calumet River and Indiana Harbor Area of Concern, USA - D. D. MacDonald; C. G. Ingersoll; D. E. Smorong; R. A. Lindskoog; D. W. Sparks; J. R. Smith; T. P. Simon; M. A. Hanacek (Archives of Environmental Contamination and Toxicology, 2002)

Agrobacterium tumefaciens-mediated transformation to alter ethylene and cytokinin biosynthesis in broccoli - Nigel E. Gapper; Marian J. McKenzie; Mary C. Christey; Robert H. Braun; Simon A. Coupe; Ross E. Lill; Paula E. Jameson (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Vegetative propagation of Prunus africana: effects of rooting medium, auxin concentrations and leaf area - Z. Tchoundjeu; M. L. Avana; R. R. B. Leakey; A. J. Simons; E. Assah; B. Duguma; J. M. Bell (Agroforestry Systems, 2002)

In vitro regeneration of Echinacea purpurea from leaf explants - A. Koroch; H.R. Juliani; J. Kapteyn; J.E. Simon (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

North African wetland lakes: characterization of nine sites included in the CASSARINA Project - Mohammed Ramdani; Roger J. Flower; Najat Elkhiati; Mohammed M. Kraïem; Adel A. Fathi; Hilary H. Birks; Simon T. Patrick (Aquatic Ecology, 2001)

Open water zooplankton communities in North African wetland lakes: the CASSARINA Project - Mohammed Ramdani; Najat Elkhiati; Roger J. Flower; Hilary H. Birks; Mejdidine M. Kraïem; Adel A. Fathi; Simon T. Patrick (Aquatic Ecology, 2001)

Metabolism of chicory fructooligosaccharides by bifidobacteria - A. Durieux; C. Fougnies; H. Jacobs; J.-P. Simon (Biotechnology Letters, 2001)

CD2F-10: a new member of the CD2 subset of the immunoglobulin superfamily - Janet A. Fennelly; Bela Tiwari; Simon J. Davis; Edward J. Evans (Immunogenetics, 2001)

A molecular approach to dominance in hypophosphatasia - A. Lia-Baldini; F. Muller; A. Taillandier; J. Gibrat; M. Mouchard; B. Robin; B. Simon-Bouy; J. Serre; A. Aylsworth; E. Bieth; S. Delanote; P. Freisinger; et al. (Human Genetics, 2001)

Influence of plant development and environment on transgene expression in potato and consequences for insect resistance - Rachel E. Down; Louise Ford; Simon J. Bedford; Laurence N. Gatehouse; Christine Newell; John A. Gatehouse; Angharad M.R. Gatehouse (Transgenic Research, 2001)

Species- and agonist-dependent differences in the deactivation-kinetics of P2X 7 receptors - Hibell A.; Thompson K.; Simon J.; Xing M.; Humphrey P.; Michel A. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Retro‐active skill of multi‐tiered forecasts of summer rainfall over southern Africa - Willem A. Landman; Simon J. Mason; Peter D. Tyson; Warren J. Tennant (International Journal of Climatology, 2001)
Sea‐surface temperature (SST) variations of the oceans surrounding southern Africa are associated with seasonal rainfall variability, especially during austral summer when the tropical atmospheric circulation is dominant over the region. Because of instabilities in the linear association between summer rainfall over southern Africa and SSTs of the tropical Indian Ocean, the skilful prediction of seasonal rainfall may best be achieved using physically based models. A two‐tiered retro‐active forecast procedure for the December–February (DJF) season is employed over a 10‐year period starting from 1987/1988. Rainfall forecasts are produced for a number of homogeneous regions over part of southern Africa. Categorized (below‐normal, near‐normal and above‐normal) statistical DJF rainfall predictions are made for the region to form the baseline skill level that has to be outscored by more elaborate methods involving general circulation models (GCMs). The GCM used here is the Centre for Ocean–Land–Atmosphere Studies (COLA) T30, with predicted global SST fields as boundary forcing and initial conditions derived from the National Centres for Environmental Prediction (NCEP) reanalysis data. Bias‐corrected GCM simulations of circulation and moisture at certain standard pressure levels are downscaled to produce rainfall forecasts at the regional level using the perfect prognosis approach. In the two‐tiered forecasting system, SST predictions for the global oceans are made first. SST anomalies of the equatorial Pacific (NIÑO3.4) and Indian oceans are predicted skilfully at 1‐ and 3‐month lead‐times using a statistical model. These retro‐active SST forecasts are accurate for pre‐1990 conditions, but predictability seems to have weakened during the 1990s. Skilful multi‐tiered rainfall forecasts are obtained when the amplitudes of large events in the global oceans (such as El Niño and La Niña episodes) are described adequately by the predicted SST fields. GCM simulations using persisted August SST anomalies instead of forecast SSTs produce skill levels similar to those of the baseline for longer lead‐times. Given high‐skill SST forecasts, the scheme has the potential to provide climate forecasts that outscore the baseline skill level substantially. Copyright © 2001 Royal Meteorological Society

Evidence for predominant clones in a cyclically parthenogenetic organism provided by combined demographic and genetic analyses - L. Haack; J.‐C. Simon; J.‐P. Gauthier; M. Plantegenest; C.‐A. Dedryver (Molecular Ecology, 2000)
Aphids are particularly interesting models in the study of genetic and demographic components of plant adaptation because of their breeding system which combines parthenogenesis and sexual reproduction (i.e. cyclical parthenogenesis), and the frequent emergence of host‐adapted races reported in this group. In this paper, patterns of host adaptation were assessed on local populations of the aphid Sitobion avenae by following their demographic and genetic structure in a maize field for two consecutive years. The existence of putative generalist (polyphagous) or specialized (host‐adapted) genotypes was also investigated by comparing the genotypic distribution of this aphid on maize and other cultivated host plants, using five microsatellite loci. Although population dynamics revealed strong variation in aphid abundance during the colonization period on maize, two genotypes identified at seven additional microsatellite loci were predominant and exhibited stable frequencies over cropping season and between years. Based on present and earlier studies, these two prevalent genotypes were shown to survive on different host plants other than maize, to colonize large geographical zones and to persist parthenogenetically for several years. All these data strongly suggest that these two genotypes are asexual generalist clones that could have been favoured by agricultural practices encountered in western Europe. Besides these two clones, a continual replacement of rare genotypes was observed on maize in both years. Hypotheses involving selection via aphid–plant interactions and natural enemies were proposed for explaining the disappearance of these genotypes on maize.

Continuous malolactic fermentation by Oenococcus Oeni entrapped in LentiKats - A. Durieux; X. Nicolay; J.-P. Simon (Biotechnology Letters, 2000)

Development of an Index of Biotic Integrity for the Little Arkansas RiverBasin, Kansas - M. J. Lydy; A. J. Strong; T. P. Simon (Archives of Environmental Contamination and Toxicology, 2000)

Informatics for mutagenesis: the design of Mutabase—a distributed data recording system for animal husbandry, mutagenesis, and phenotypic analysis - Mark A. Strivens; Rachel L. Selley; Simon J. Greenaway; Mazda Hewitt; Xinhong Liu; Kirstin Battershill; Stefan L. McCormack; Karen A. Pickford; Lucie Vizor; Patrick M. Nolan; A. Jacqueline Hunter; Josephine Peters; et al. (Mammalian Genome, 2000)

RAPD linkage map of the genomic region encompassing the root-knot nematode (Meloidogyne javanica) resistance locus in carrot - L. S. Boiteux; J. G. Belter; P. A. Roberts; P. W. Simon (Theoretical and Applied Genetics, 2000)

Red-Legged Partridges ( Alectoris rufa ) as Bioindicators for Persistent Chlorinated Chemicals in Spain - A. Herrera; A. Ariño; M. P. Conchello; R. Lazaro; S. Bayarri; C. Yagüe; J. M. Peiro; S. Aranda; M. D. Simon (Archives of Environmental Contamination and Toxicology, 2000)

Late Middle Pleistocene deposits at Norton Farm on the West Sussex coastal plain, southern England - Martin R. Bates; C. Richard Bates; Philip L. Gibbard; Richard I. Macphail; Frederick J. Owen; Simon A. Parfitt; Richard C. Preece; Mark B. Roberts; J. Eric Robinson; John E. Whittaker; Keith N. Wilkinson (Journal of Quaternary Science, 2000)

Change in the association between Indian Ocean sea-surface temperatures and summer rainfall over South Africa and Namibia - Willem A. Landman; Simon J. Mason (International Journal of Climatology, 1999)

Conformational analysis of an EP24.15 inhibitor by NMR and molecular modelling - Rosaleen J. Anderson; Brian P. Clark; Chandralal M. Hewage; A. Ian Smith; Simon P. Mackay (International Journal of Peptide Research and Therapeutics, 1999)

Operational long‐lead prediction of South African rainfall using canonical correlation analysis - Willem A. Landman; Simon J. Mason (International Journal of Climatology, 1999)

Operational long-lead prediction of South African rainfall using canonical correlation analysis - Willem A. Landman; Simon J. Mason (International Journal of Climatology, 1999)

A 5× genome coverage bovine BAC library: production, characterization, and distribution - Baoli Zhu; Judith A. Smith; Simon M. Tracey; Bernard A. Konfortov; Katrin Welzel; Leonard C. Schalkwyk; Hans Lehrach; Sonja Kollers; Julio Masabanda; Johannes Buitkamp; Ruedi Fries; John L. Williams; et al. (Mammalian Genome, 1999)

Molecular markers linked to breeding system differences in segregating and natural populations of the cereal aphid Rhopalosiphum padi L. - J.‐C. Simon; N. Leterme; A. Latorre (Molecular Ecology, 1999)
The aphid Rhopalosiphum padi shows coexistence of sexual and asexual populations, providing an opportunity to study the evolution of breeding system variation in the context of theories on the origin and maintenance of sex. However, assessments of the distribution of sexual and asexual lineages of this aphid are complicated by the difficulties in rapidly characterizing their breeding system. To facilitate this task and to gain insight into the genetic relatedness between sexual and asexual genotypes, molecular markers linked to breeding system differences were recently developed. In this study, we have successfully converted a random amplified polymorphic DNA (RAPD) marker associated with life‐cycle variation in R. padi into a codominant sequence‐characterized amplified region (SCAR). Segregating and natural populations of known breeding systems were examined to evaluate the life cycle–SCAR marker association. Complete linkage was found in segregating populations while the association averaged 94% in field populations. Detailed analysis of allelic distribution and sequence divergence of the SCAR locus among sexual and asexual populations provides further evidence for a unique and apparently ancient loss of sexuality in this aphid. It also suggests that occasional gene flow occurs between populations differing in their breeding system, mediated by males produced by ‘asexual’ lineages. This system provides the possibility for the recurrent emergence of new asexual lineages, ensuring the longer persistence of asexuality, and would have important implications for the assessment of costs and benefits of sex in aphids.

Adverse drug events in hospitalized patients - P. M. L. A. van den Bemt; A. C. G. Egberts; A. W. Lenderink; J. M. Verzijl; K. A. Simons; W. S. C. J. M. van der Pol; H. G. M. Leufkens (European Journal of Clinical Pharmacology, 1999)

Reproductive mode and population genetic structure of the cereal aphid Sitobion avenae studied using phenotypic and microsatellite markers - J.‐C. Simon; S. Baumann; P. Sunnucks; P. D. N. Hebert; J.‐S. Pierre; J.‐F. Le Gallic; C.‐A. Dedryver (Molecular Ecology, 1999)
As French populations of the aphid Sitobion avenae exhibit a range of reproductive modes, this species provides a good opportunity for studying the evolution of breeding system variation. The present analysis combined ecological and genetic investigations into the spatial distribution of variation in reproductive mode. Reproductive mode was characterized in 277 lineages of S. avenae from France, and these aphids were scored for five microsatellite loci. The analyses revealed strong geographical partitioning of breeding systems, with obligate asexuals mostly restricted to the south of France, while lineages producing sexual forms were more common in the north. Contrary to what might be anticipated for organisms with frequent parthenogenesis, there was substantial genic and genotypic diversity, even in the obligately asexual lineages. More than 120 different genotypes were detected among the 277 aphid lineages, with an average of 5.9 alleles per locus (range four to 16) and heterozygosity of 56.7%. As with previous studies of allozyme variation in aphids, most loci showed heterozygote deficits, and disequilibrium was common among allelic variants at different loci, even after removal of replicate copies of genotypes that might have been derived through clonal reproduction. Our results suggest that selection is important in structuring reproductive systems and genetic variation in French S. avenae . Canonical correspondence analysis was employed to examine the associations between genotypic and phenotypic variables, enabling the identification of alleles correlated with life‐history traits.

High-pressure behaviour and equation of state of calcite, CaCO 3 - Simon A. T. Redfern; Ross J. Angel (Contributions to Mineralogy and Petrology, 1999)

Localised Cerebral Phosphorus-31 MR Spectroscopy in Man Before and Immediately after Coronary Bypass Surgery with Hypothermic Cardiopulmonary Bypass - Jason A. Wilson; Simon D. Taylor-Robinson; David J. Bryant; Kenneth M. Taylor; David N. F. Harris (Metabolic Brain Disease, 1998)

Long-term expression and secretion of human glucocerebrosidase by primary murine and human myoblasts and differentiated myotubes - Chunming Liu; Alfred B. Bahnson; James T. Dunigan; Simon C. Watkins; J. A. Barranger (Journal of Molecular Medicine, 1998)

Inheritance and linkage of a gene for resistance to race 4 of fusarium wilt and RAPD markers in chickpea - A. Tullu; F.J. Muehlbauer; C.J. Simon; M.S. Mayer; J. Kumar; W.J. Kaiser; J.M. Kraft (Euphytica, 1998)

Identifying novel regulators of shoot meristem development - Jeffrey A. Pogany; Ephraim J. Simon; Rebecca B. Katzman; Bernadette M. De Guzman; Lita Po Yu; Amy E. Trotochaud; Steven E. Clark (Journal of Plant Research, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

Survey of Grauer's Gorillas (Gorilla gorilla graueri) and Eastern Chimpanzees (Pan troglodytes schweinfurthi) in the Kahuzi-Biega National Park Lowland Sector and Adjacent Forest in Eastern Democratic Republic of Congo - Jefferson S. Hall; Lee J. T. White; Bila-Isia Inogwabini; Ilambu Omari; Hilary Simons Morland; Elizabeth A. Williamson; Kristin Saltonstall; Peter Walsh; Claude Sikubwabo; Dumbo Bonny; Kaleme Prince Kiswele; Amy Vedder; et al. (International Journal of Primatology, 1998)

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - M. Van Roozendael; P. Peeters; H. K. Roscoe; H. De Backer; A. E. Jones; L. Bartlett; G. Vaughan; F. Goutail; J.-P. Pommereau; E. Kyro; C. Wahlstrom; G. Braathen; et al. (Journal of Atmospheric Chemistry, 1998)

The domestication and commercialization of indigenous trees in agroforestry for the alleviation of poverty - R. R. B. Leakey; A. J. Simons (Agroforestry Systems, 1997)

Conversion of highly malignant colon cancer from an aggressive to a controlled disease by oral administration of a metalloproteinase inhibitor - Zili An; Xiaoen Wang; Neville Willmott; Surinder K. Chander; Simon Tickle; Andrew J. P. Docherty; Andrew Mountain; Andrew T. Millican; Richard Morphy; John R. Porter; R. Ola Epemolu; Tetsuro Kubota; et al. (Clinical & Experimental Metastasis, 1997)

Sensors that mediate copper-specific activation and repression of gene expression - D. R. Winge; Janet A. Graden; Matthew C. Posewitz; Laura J. Martins; Laran T. Jensen; John R. Simon (JBIC Journal of Biological Inorganic Chemistry, 1997)

Novel principles in the microbial conversion of nitrogen compounds - Mike S.M. Jetten; Susanne Logemann; Gerard Muyzer; Lesley A. Robertson; Simon de Vries; Mark C.M. van Loosdrecht; J. Gijs Kuenen (Antonie van Leeuwenhoek, 1997)

Simple sequence repeats provide a direct estimate of pollen‐mediated gene dispersal in the tropical tree Gliricidia sepium - I. K. Dawson; R. Waugh; A. J. Simons; W. Powell (Molecular Ecology, 1997)
An understanding of the processes that determine the observed patterns of genetic variation in natural plant populations is an important factor in the management of biodiversity. Pollen‐mediated gene dispersal is recognized as a major determinant of population genetic structure. Here, the utility of simple sequence repeat (SSR) analysis was investigated for the measurement of pollen‐mediated gene transfer by paternity exclusion in a restricted, fragmented and endangered population of the insect‐pollinated tropical leguminous tree Gliricidia sepium located in Guatemala. Data at a single SSR locus, which revealed six allelic variants, were employed to generate minimum distance curves of pollen dispersal. Combined data from all six alleles indicated that a minimum of 1.8% of transfer events occurred over a distance of greater than 75 m. However, this value represents an underestimate because of the exclusion approach employed for analysis. Considering the four rarest alleles in the population only (combined frequency = 0.196), which provides a less biased indicator of gene transfer, a minimum of 6.1% of pollen movements could be attributed to greater than 75 m. One extreme example of gene transfer of over 275 m was recorded. Estimates of pollen transfer suggest a homogenizing effect on genetic structure over the spatial scale of the study population and provide an important indicator for the genetic management of natural and exotic stands of G. sepium . This study provides the first example of SSR analysis being employed to estimate directly pollen movement in a natural stand of any tree species.

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

Atrophy and loss of dopaminergic mesencephalic neurons in heterozygous weaver mice - Tatyana Verina; James A. Norton; Jeffrey J. Sorbel; Lazaros C. Triarhou; Donald Laferty; Judith A. Richter; Jay R. Simon; Bernardino Ghetti (Experimental Brain Research, 1997)

Properties of the menaquinol oxidase (Qox) and of qox deletion mutants of Bacillus subtilis - E. Lemma; J. Simon; H. Schgger; A. Krger (Archives of Microbiology, 1995)

Properties of the menaquinol oxidase (Qox) and of qox deletion mutants of Bacillus subtilis - E. Lemma; J. Simon; H. Schgger; A. Krger (Archives of Microbiology, 1995)

Further characterization of two different, reversible aldehyde oxidoreductases from Clostridium formicoaceticum, one containing tungsten and the other molybdenum - C. Huber; J. Caldeira; J. A. Jongejan; H. Simon (Archives of Microbiology, 1994)

Further characterization of two different, reversible aldehyde oxidoreductases from Clostridium formicoaceticum, one containing tungsten and the other molybdenum - C. Huber; J. Caldeira; J. A. Jongejan; H. Simon (Archives of Microbiology, 1994)

Genetic improvement of non-industrial trees - A. J. Simons (Agroforestry Systems, 1992)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

Worker exposure and protective clothing performance during manual seed treatment with lindane - Richard A. Fenske; Ann M. Blacker; Suzanne J. Hamburger; Glenn S. Simon (Archives of Environmental Contamination and Toxicology, 1990)

The effect of the dissolved oxygen concentration and anabolic limitations on the behaviour of Rhizobium ORS571 in chemostat cultures - W. de Vries; H. Stam; J. G. Duys; A. J. M. Ligtenberg; L. H. Simons; A. H. Stouthamer (Antonie van Leeuwenhoek, 1986)

Neurovirulence of an herpes simplex type 1 thymidine kinase negative mutant determined by virus biochemical defect and host immune system in mice - Y. J. Gordon; P. L. Simon; J. A. Armstrong (Archives of Virology, 1984)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

The automation of microbiological vitamin assays by means of a modified autoanalyser system - T. M. Birg; Agnis Phumukirs; I. M. Simons; J. van der Vils; H. A. Bihagh (Antonie van Leeuwenhoek, 1968)